Influence of pores on the corrosion and cracking of the reinforced concrete suffered by the chloride ions and stray current - Wenjun Zhu; Xinyun Yang; Fan Tang; Fei Dong (European Journal of Environmental and Civil Engineering, 2026)

Ozone-persulfate molecular energy-level matching regulates dissolved organic matter degradation and transformation in leachate aerobic effluent - Junda Lai; Jun Cui; Yechen An; Zhenbei Wang; Yunjie Liao; Fan Li; Chen Li; Yatao Liu; Fei Qi; Zhonglin Chen (Water Research, 2026)

Paddy cultivation history affects soil water dynamics and water balance by altering soil physical and hydraulic parameters - Qian Yang; Jun Yi; Chuanqin Huang; Weiwen Qiu; Shenlong Li; Yuanhang Fei; Hanjiang Nie; Peifeng Li; Jun Fan; Muxing Liu; Hailin Zhang (Soil and Tillage Research, 2026)

Virulence and resistance adaptation of Streptococcus agalactiae Ib/ST261 infecting bullfrogs in Hainan, China between 2019 and 2023 - Guiying Guo; Zihao Di; Sheng Huang; Xuesong Li; Nuo Yang; Lixia Fan; Jun Xie; Xiuqing Cai; Yuqi Meng; Fei Yan; Jiping Zheng (Brazilian Journal of Microbiology, 2026)

MDA5 associates with MAVS and its splicing variant in the antiviral response of large yellow croaker Larimichthys crocea - Ying Li; Yi Fan Zhang; Xia Ming Chen; Qiang Ma; Jiao Nan Zhang; Xiao Mei Huang; Jing Xuan Li; Yu Xuan Zhu; Tuan Yu Guo; Peng Fei Zou (Fish & Shellfish Immunology, 2026)

Temperature-influenced deformation analysis of a full-scale steel-concrete-steel cable support tower model during construction - Zhi-Li Qi; Wei-Le Chen; Jian Li; Jian-Sheng Fan; Rong Xian; Fei Tian; Yu-Fei Liu (Engineering Structures, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Emerged advantages of recirculation on continuous temperature-phased anaerobic digestion of high-solid sludge under significantly shortened retention time: Substance migration-transformation, energy balance and microbial community - Li-Jie Wu; Fei Ye; Xiao-Xiao Li; Fan Yang; Zhi-Feng Qin (Bioresource Technology, 2026)

Ultrafast kinetics and efficient PMS activation using a 2D calcined Co-MOF nanoconfined catalytic membrane for continuous tetracycline degradation - Jinsong He; Keyu Long; Fan Ni; Yongjia Lei; Wei Qu; Wei Shi; Yifeng Zhang; Fei Shen (Water Research, 2026)

Global prioritization of PFAS in groundwater based on multi-scale evaluation of national and source-level data - Yan Zhou; Jinhong Tao; Weiling Tang; Fuyang Huang; Min Fan; Fei Liu; Faqin Dong; Shen Qu (Journal of Environmental Chemical Engineering, 2026)

In-situ electrocoagulation coupled with catalytic ozonation - ceramic membrane filtration for advanced treatment of pharmaceutical secondary effluent: A pilot study - Weiqiang Rao; Yunhan Jia; Junda Lai; Yujie Li; Zizheng Huangfu; Chen Li; Zhenbei Wang; Yatao Liu; Fan Li; Fei Qi; Amir Ikhlaq (Journal of Environmental Chemical Engineering, 2026)

Recent advances in heterologous lactoprotein expression: from host engineering to downstream processing - Yu Qiu; Li Li; Linjie Feng; XiangYu Fan; Xiaolei Fan; Rongbo Guo; Kangqing Fei; Shanfei Fu (Food Bioscience, 2026)

Adaptive seasonal management after eradicating invasive Spartina: A nature-based approach - Dong-Fan Xu; Qi Yuan; Hai-Qiang Guo; Bing Tan; Fei Quan; Zhe-Xiu Yu; Dong-Yang Han; Yu-Jiao Lu; Ying-Ying Hao; Si-Qi Zhou; Guang Ge; Bin Zhao; et al. (Ecological Engineering, 2026)

Catalytic ozonation via in-situ electro-triggered slow-release iron for pharmaceutical wastewater purification: Multi-path synergistic mechanism and electrode stabilization - Yunhan Jia; Ruijun Ren; Junda Lai; Zizheng Huangfu; Zhenbei Wang; Yatao Liu; Chen Li; Fan Li; Fei Qi; Amir Ikhlaq; Jolanta Kumirska; Ewa Maria Siedlecka; et al. (Chemical Engineering Journal, 2026)

ROS-scavenging and immunomodulatory MXene-MnO₂ hydrogel nerve conduit for peripheral nerve regeneration - Tiankun Hui; Yajing Yang; Fei Diao; Haihan Fan; Jie Chen; Yan Li; Yingjie Song; Chenchen Fu; Meijie Jia; Wenwei Han; Tengbo Yu; Jianye Fu (Chemical Engineering Journal, 2026)

Steering active hydrogen in PtCu single atom alloy nanowires for efficient nitrate reduction to ammonia - Weimian Zhang; Binwen Zeng; Haoliang Huang; Fan Dang; Xin Liu; Jing Sun; Wei Liao; Mengxiang Han; Chao Song; Run Ran; Kaiyang Xu; Fei Lin; et al. (Chemical Engineering Journal, 2026)

The role of epoxide structure in elasticity and sensing performance of zein/epoxide ultrafine fibrous sensors for joint motion monitoring - Fei Liu; Lu Liu; Tong Zhang; Weisi Fan; Wanshuang Liu; Dequn Wu; Weitao Jia; Narendra Reddy; Qiuran Jiang (Chemical Engineering Journal, 2026)

Sandstone-hosted uranium mineral prospectivity mapping based on ResNet50 self-distillation - Weijian Zheng; Jianfeng He; Weidong Li; Fei Xia; Fengjun Nie; Zizheng Yu; Caijun Gong; Guoyun Zhong; Fan Diao (Computational Geosciences, 2026)

Classical swine fever virus hijacks triglyceride metabolism via the NS5B-PLIN5 axis to facilitate viral replication - Xiao-Wen Li; Liang-Chun Liu; Fei-Fan Zhao; Yan-Hong Yong; Xiang-hong Ju (Veterinary Microbiology, 2026)

Innovative evaluation framework for WWTPs: Synergistic reduction of pollutants and GHGs based on super-SBM-EWM model - Jiao Liu; Yujin Gan; Keke Zhao; Xiao Guan; Chen Li; Zhenbei Wang; Yatao Liu; Fan Li; Fei Qi; Amir Ikhlaq; Oksana Ismailova; Zuhra Kadirova (Process Safety and Environmental Protection, 2026)

Garnet and epidote chemistry of the Dulong Sn-Zn-In polymetallic deposit, SW China: Constraints on the hydrothermal fluid evolution and implications for exploration - Qing Yang; Suo-Fei Xiong; Shao-Yong Jiang; Yi Zheng; Fan Xiao; Shu-Gang Xiao (Journal of Geochemical Exploration, 2026)

Oxygen-vacancy-rich NiCo-Co-Co3C heterostructures for mild-condition hydrogenation of lignin-derived vanillin to methyl vanillyl alcohol - Xiaozhong Chen; Wei Lv; Fei Yang; Yujian Fan; Tiejun Wang; Songbai Qiu (Fuel, 2026)

Low-frequency deficit irrigation in a semi-arid vineyard of Xinjiang's Manas region: Effects on grape and wine aroma composition across three vintages - Ning Shi; Meng-Bo Tian; Hao-Cheng Lu; Yi-Fan Zhao; Ming-Yu Li; Jia-Yi Deng; Chi-Fang Cheng; Shu-De Li; Zhen-Zhen Zhang; Keji Yu; Yi-Bin Lan; Fei He; et al. (Food Research International, 2026)

A tannic acid-iron co-modified polyphenylene sulfone ultrafiltration membrane with improved surface hydrophilicity and antifouling properties - Ying Liu; Jingyu Sun; Keke Fan; Fei Yang; Weigao Zhao; Meng Zhang; Suyun Chang; Huizhong Wang; Wenshan Guo; Xinbo Zhang (Environmental Research, 2026)

Single-channel dz2 electron injection for unhindered peracetic acid activation by iron-based catalysts for cefapirin degradation in water - Shimei Yin; Lingyun Gu; Chongdan Wu; Yi Wu; Peishen Li; Zhenyu He; Boyu Huang; Fan Li; Fei Qi (Chemical Engineering Journal, 2026)

Dimension-tailored sp2 carbon-conjugated COFs: Palladium recovery from metallurgical wastewater and high-performance Suzuki catalysis - Hao Xiang; Wenjing Chen; Jiaorong Liu; Fei Zhao; Fan Lei; Chen He; Yaling Dai; Jiaxing Xiong; Shixiong Wang; Huiping Bai; Xiangjun Yang (Chemical Engineering Journal, 2026)

Electron transfer enhancement-driven Fe-nHA composite gel beads for immobilizing B10 for efficient crude oil degradation: Transcriptomic and mechanistic study - Kexin Fan; Nan Gao; Fei Wu; Yufeng Sun; Yuhua Su; Liangzhen Du; Qiyou Liu; Hailiang Yin (Chemical Engineering Journal, 2026)

Thermochromic PDMS/phase-change microcapsule–boron nitride membrane for dual-mode radiative cooling and solar heating - Fan Fei; Yang Yu; Jundie Hu; Jiafu Qu; Jianzhang Li; Yahui Cai (Chemical Engineering Journal, 2026)

Climate-smart governance for ecosystem services: synergizing carbon storage and water resource management under global change - Fan Gao; Bing He; Kun Liu; Abdul Waheed; Fei Gao (Regional Environmental Change, 2026)

Dynamic simulation of winter wheat dry matter and nitrogen diagnosis based on the Richards model and the critical nitrogen dilution curve - Yalin Gao; Liangjun Fei; Fangyuan Shen; Youliang Peng; Qian Wang; Runqiao Zheng; Qianwen Fan; Yingjie Zhou (Irrigation Science, 2026)

Species Divergence in Oxytocin-Dependent Yawning on a Conserved Glutamatergic Erection Circuit - Yan-Chu-Fei Zhang; Qing-Wu Zheng; Yang Lu; Hao-Yuan Wang; Jiao Cang; Xin-Rui Wu; Lin-Yao Fan; Liang Li; Ni-Na Zhang; Xiao-Yang Zhang; Jing-Ning Zhu; Jian Jing; et al. (Neuroscience Bulletin, 2026)
Yawning coupled with penile erection is a conserved neurobehavioral syndrome mediated by the paraventricular hypothalamus (PVH). However, the distinct roles of oxytocin and its co-transmitters remain unresolved. Using chemogenetics, we showed that activation of PVH oxytocin neurons was sufficient to elicit both responses, whereas silencing these neurons abolished them. Viral tracing revealed that these neurons project collaterally to the brainstem reticular nucleus and spinal cord to spatially coordinate autonomic and somatic motor outputs. By dissecting the molecular mechanisms using CRISPR-Cas9, we found that vesicular glutamate transporter 2 (VGLUT2)-dependent glutamatergic transmission provides the primary drive for both behaviors, whereas the oxytocin peptide is selectively required for yawning but dispensable for erection. Comparative analyses across rats, hamsters, and mice demonstrated that while the glutamatergic erectile circuit was conserved, mice lacked spontaneous yawning and were resistant to apomorphine-induced yawning. These findings suggest a hierarchical co-transmission framework in which fast glutamatergic signaling provides the core drive, while oxytocin confers behavioral specificity.

Rapid assembly of structurally diverse 3,4-dihydroquinazolines with anticancer activity via SDS-promoted aqueous synthesis - Fu-Qiang Yu; Pei-Lu Song; Yan-Rui Fan; Jun-Wei Wang; Xu-Jie Wang; Jin-Fei Yang (Molecular Diversity, 2026)

Multi-stage fuzzy Bayesian cooperative optimization for expensive large-scale problems - Ruiguang Liu; Peng Yue; Fei Ming; Yanzhan Chen; Fan Yu; Junli Liu (Swarm and Evolutionary Computation, 2026)

Rapid detection of porcine circovirus type2 using a combination of RAA isothermal amplification and Cas12a nucleic detection technology - Lejia Fan; Xueming Liu; Jiaqing Hu; Jinjin Chi; Xiaoyu Fei; Chao Qi; Enhui Wang; Feng Su (Research in Veterinary Science, 2026)

Tectonic forcing and climate modulation on the evolution of aeolian sediment provenance from the northeastern Tibetan Plateau margin to the Chinese Loess Plateau - Yuxin Fan; Minmin Gao; Fei Wang; Qingsong Cai; Chuanying Zhu; Xueyu Yan; Ke Bi; Qiang Shu; Ping Zhang (Quaternary Science Reviews, 2026)

Dynamic modelling and response analysis of variable-length mooring cables for floating offshore wind turbines within the ALE-ANCF framework - Fei Chen; Jihua Fan; Junjie Huang; Yi Zhao; Sihan Jiang (Ocean Engineering, 2026)

How clean is clean enough? Short-chain PFAS remain dominant in treated landfill leachate - Fei Chen; Zhi-Zhong Zhang; Hang Li; Si-Da Meng; Leo W.Y. Yeung; Sakhayana Danilova; Yi-Fan Li; Sheng-Qiang Fan; Zi-Feng Zhang (Journal of Environmental Management, 2026)

Mapping the effectiveness of inter-regional industrial co-processing of municipal incineration fly ash: Evidence from the capital metropolitan area in China - Xinyi Zhang; Run Shi; Fan Fei; Zongguo Wen; Hongzhi Ma; Jiayue Zhang; Liping Zhang (Journal of Environmental Management, 2026)

Synergy effect of bimetallic CuNi/Al2O3-ZrO2 catalyst Driven pathway Switching in CO2 hydrogenation to methanol - Mengyu Xu; Jiale Chang; Xinyu Jia; Fei Fan; Zhiping Chen; Wenwu Zhou (Fuel, 2026)

Transcriptomic and physiological insights into 1-MCP–mediated delay of postharvest senescence in fresh goji berries under immediate and post-transport treatments - Fei Yao; Tingting Li; Jie Shi; Yafei Li; Li Jiang; Zhicheng Yan; Caie Wu; Gongjian Fan; Xiaojing Li; Dandan Zhou; Kaiping Cong (Food Bioscience, 2026)

Construction full-process detection of geometric imperfections in complex reticulated shells with curved steel members - Hao-Ran Tang; Jian-Sheng Fan; Min Jiao; Guo-Hua Zeng; Hong-Jun Guo; Yu-Fei Liu (Engineering Structures, 2026)

Explainable machine learning-based study on the applicability of thermal indicators for university classrooms in summer - Luyao Wang; Fan Fei; Yan Wang; Yongwei Song; Yuling Xiao; Weidong Wu; Kunkun Zhao; Hiroatsu Fukuda (Building and Environment, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

Effect of muddy water and fertilizer solution characteristics on water-salt-fertilizer transport in saline soil under film hole irrigation - Qianwen Fan; Liangjun Fei; Wei Li; Yalin Gao (Journal of Soils and Sediments, 2026)

Combined toxicity and mechanism of cadmium and neonicotinoid insecticide to rice (Oryza sativa L.): reduced antioxidant defence mediated by flavonoid - Zhaoxia Fan; Na Liu; Fei Ge; Feng Li; Wenjun Zhou; Juan Gao (ENGINEERING Environment, 2026)

A genetic clash of sister groups: first-ever intergeneric and interspecific mitogenome comparisons between two close gall midge genera (Cecidomyiidae: Cecidomyiinae: Cecidomyiini): the floral and veggie-versatile Contarinia and the mango-mad Procontarinia, with phylogenetic applications - Xiu-Fang Dong; Yi-Fan Zhang; Xu-Yuan Gao; Ning-Bo Ma; Yu Ji; Yan-Fei Li; Yi-Ran Mu; Zheng-Hao Yue; De-Wei Wei; Yong-Hao Yu; Hai-Li Qiao; Wen-Jun Bu; et al. (Arthropod-Plant Interactions, 2026)

Nanotechnology-enabled precision targeting of lung cancer stem cells: Recent developments and therapeutic implications - Yi Zhang; Jiaxin Fan; Yuhan Ye; Chuang Li; Ming-Fei Lang (Stem Cell Reviews and Reports, 2026)

Transcriptomic analysis of lncRNA-miRNA-mRNA competing endogenous RNA regulatory networks in radiation-induced mouse thymic degeneration - Fei Wang; Qing-hua Yu; Xin-ming Fan; Cun-yang Guo; Si-guang Xu; Wen-bo Zhang; Ping Xu (Immunologic Research, 2026)

Two decades of methane budgets at the sub-national scale in China - Pengfei Zhao; Zhen Zhang; Guanghui Huang; Zhenxuan Wang; Josep G. Canadell; Philippe Ciais; Huilin Chen; Shengqian Chen; Jason Blake Cohen; Fan Dai; Peng Gong; Robert B. Jackson; et al. (Science Bulletin, 2026)

Is BPA only the tip of the iceberg? Occurrence and risk assessment of 32 bisphenol analogues in landfill leachate - Zhi-Zhong Zhang; Lin-Hui Zhang; Hang Li; Fei Chen; Sakhayana Nikolaevna Danilova; Ming-Han Li; Bing-Feng Liu; Yi-Fan Li; Zi-Feng Zhang (Journal of Hazardous Materials, 2026)

Glacial-interglacial rhythms regulated the dynamic groundwater, salt and dust cycles in the Asian inland sand sea - Changfan Li; Xin Liu; Zaijun Li; Baofeng Li; Yuxin Fan; Tao Yu; Shuai Luo; Wang Wang; Fei Wang (Global and Planetary Change, 2026)

Environmental impact mechanisms and circularity pathways of global pallet systems: A structured evidence synthesis - Tingting Zhang; Yuan Tao; Fan Fei; Paul Ekins (Environmental Impact Assessment Review, 2026)

Transforming pallet systems for global shipping decarbonization - Tingting Zhang; Hanmo Wang; Zongguo Wen; Lanxin Zhang; Fan Fei; Alexander Lin; Paul Ekins (Environmental Impact Assessment Review, 2026)

Nitrogen doping engineering of Ru nanoparticles/Mo2C MXene for efficient hydrogen production via NH3BH3 hydrolysis - Zhenluo Yuan; Fei Ya; Yang Shi; Shuyan Guan; Pingping Wang; Pei Liu; Shiqian Zhao; Qiuming Peng; Yanping Fan; Baozhong Liu (Chemical Engineering Journal, 2026)

Enhanced formic acid dehydrogenation over Pd-CeOx nanoparticles anchored on amine-tailored yolk-shell mesoporous silica nanospheres - Chunhui Zhou; Hao Chai; Youcheng Feng; Jinsong Hu; Zhentao Liu; Fei Fan; Wenwu Zhou; Chunming Xu; Xilong Wang (Chemical Engineering Journal, 2026)

Stage-dependent topographic controls on vegetation recovery and landscape-pattern evolution under contrasting restoration treatments in an abandoned mine from UAV multispectral time series - Lv Zhou; BoWen Shi; ZhiQiang Lin; Jie Zhang; Jun Lu; Fei Yang; Fan Jiang; Xiang Huang (CATENA, 2026)

Spatiotemporal Dynamics of Dissolved CO₂ and N₂O in Yangtze River Delta: Identifying Drivers and Environmental Controls - Yanjie Wei; Fei Sun; Xuexue Fan; Zhangmu Jing; Heran Zhang; Jiao Geng; Shengqiang Tu; Liming Xue; Peng Yuan (Water, Air, & Soil Pollution, 2026)

Paeoniflorin's role in inhibiting malignant metastasis of gastrointestinal stromal tumors via CYP3A4 modulation - Dapeng Cui; Zeyin Cui; Yansen Li; Shuang Fan; Lei Li; Cheng Yang; Ruixia Yu; Jiaxin Cui; Runjia Fu; Jiandong Fei (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Mechanical Response and Soil Arching Mechanism of Buried Pipelines in Landslide Zones - Yukun Li; Yun Chen; Qinglong Lu; Fan Fei; Shulu Feng; Mingbo Wang; Xuelong Han; Ruiyun Liu (Geotechnical and Geological Engineering, 2026)

Biophotocatalytic and bioelectrocatalytic strategies for methane production and oxidation: emerging pathways and perspectives - Zhenni Cheng; Xiaolei Fan; Rui Li; Kangqing Fei; Rongbo Guo; Shanfei Fu (Archives of Microbiology, 2026)

Estimation of the population size of the northern white-cheeked gibbon (Nomascus leucogenys) in Vu Quang National Park, Vietnam - Thinh Tien Vu; Dung Van Tran; Van Huu Nguyen; Oliver R. Wearn; Peng-Fei Fan (Primates, 2026)

Ankyrin-repeat transmembrane protein WAI-1 confers multiple disease resistance in wheat by activating autoimmunity - Qiuhong Wu; Wenling Li; Yongxing Chen; Huaizhi Zhang; Delin Li; Zhan Li; Fei Xiong; Guanghao Guo; Lei Dong; Xuejia Cui; Jingzhong Xie; Ping Lu; et al. (Science China Life Sciences, 2026)

Interface manipulation of d-band center by single-atom iron cathodic electroactive membrane to boost molecular oxygen activation for antibiotics removal in pharmaceutical tailwater - Ruijun Ren; Qingjing Zhang; Jiangqi Qu; Junda Lai; Chen Li; Zhenbei Wang; Fan Li; Yatao Liu; Fei Qi; Amir Ikhlaq; Jolanta Kumirska; Ewa Maria Siedlecka; et al. (Water Research, 2026)

Physicochemical recycling of perlite from agar extraction waste for repeated reuse and its enhancement mechanism on agar quality - Zhipeng Li; Fan Feng; Yi Liang; Danling Tang; Lifen He; Yuanfan Yang; Mingjing Zheng; Qingbiao Li; Xiping Du; Zedong Jiang; Fei Li; Yanbing Zhu; et al. (Waste Management, 2026)

Comparative study of combustion and pollutant emission characteristics of sludges with different drying methods in a simulated municipal solid waste grate furnace combustion process - Yang Xu; Xuewei Han; Hongzhao Fan; Dehua Liang; Yuhang Dong; Guojun Lv; Fei Wang (Waste Management, 2026)

Upper-crustal anisotropy in the aftershock zone of the 2021 Ms6.4 Yangbi earthquake from the S-wave splitting analysis - Fei Rao; Tuo Zheng; Haifeng Zhou; Wei Fu; Xiaoping Fan; Hui Zhang; Peng Zhang; Nan Sun (Physics of the Earth and Planetary Interiors, 2026)

Thermophilic/hyperthermophilic stage as component of temperature-phased anaerobic digestion or pretreatment of mesophilic digestion to enhance bio-methanation of oily food waste? - Xian-Xian Hu; Li-Jie Wu; Fei Ye; Zhi-Feng Qin; Fan Yang; Zhen-Yi Du (Journal of Cleaner Production, 2026)

Hybrid energy system based on co-firing municipal sludge coupled with power generation: energy balance, carbon emissions, and thermo-economic analysis - Zhaolei Meng; Zongguo Wen; Xin Meng; Fan Fei; Yanfei Mu; Gang Li; Tao Zhou; Quanjie Li; Yiqun Meng (Journal of Cleaner Production, 2026)

Synergistic graphene-aptamer coating on a flexible metasurface enables on-apple terahertz sensing of pesticides - Weinan Shi; Fei Fan; Lu Zhang; Yunyun Ji; Jia Zhang; Xiaoyu Zhu; Guohui Xiao; Juanli Zhao; Xianghui Wang; Zhong Ren; Shengjiang Chang (Food Chemistry, 2026)

Genome-wide identification of methylation markers associated with Streptococcus agalactiae resistance in cfDNA of GIFT tilapia - Ji Ping Jiao; Tao Fei Qiao; Meng Fan Dong; Zong Xian Zhu; Jin Min Pan; Jun Hong Xia (Fish & Shellfish Immunology, 2026)

DOM-mediated stability of manganese in groundwater: Deciphering the antagonistic roles of humic and fulvic acids in CaO2/biochar remediation - Zijun Ye; Meiyang Jiang; Xiaohui Sun; Zhenhao Fan; Haitao Li; Benyi Cao; Fei Wang (Chemical Engineering Journal, 2026)

Consistent intensification of extreme heavy and light precipitation events in the Tienshan Mountains, Central Asia - Xueqi Zhang; Yaning Chen; Zhenhua Xia; Zhi Li; Gonghuan Fang; Fan Sun; Yupeng Li; Fei Wang (Atmospheric Research, 2026)

Beyond the Seizure Onset Zone: Fast Ripples as Anchors for Precise Neurostimulation Therapy - Shuye Ying; Jialu Chen; Xukun Fan; Yi Wang; Fan Fei (Neuroscience Bulletin, 2026)

Antioxidant Enzyme Activities and Metabolic Responses of the Posterior Gills of Mud Crab (Scylla paramamosain) Under Long-Term Stress in Coastal Chloride-Dominated Low-Salt Saline-Alkali Water - Ziwei Fan; Kangxiang Qin; Fei Wang; Chenxi Che; Yuntao Li; Wenjun Li; Shan Gao; Chunlin Wang; Changkao Mu; Huan Wang (Journal of Ocean University of China, 2026)

Shenrong Guben Huanshao Pill enhanced stress resistance and extended the lifespan of Caenorhabditis elegans by activating the oxidative stress system via the DAF-16/FOXO signaling pathway - Yi-Nan Yang; Xin Wang; Hong-Fen Jiang; Jie Yang; Subiy Akbara; Xiao-Qin Yang; Hai-Qing Fan; Guo-Lin Chai; Dong-Qing Fei; Fang-Di Hu; Shuang-Xi Qian; Zhan-Xin Zhang (Biogerontology, 2026)

Advances, opportunities, and challenges in microbial community construction: from environmental remediation to biomanufacturing - Mengxue Li; Xiang Xing; Kangqing Fei; Zhenni Cheng; Jiayu Zhang; Rongbo Guo; Xiaokui Zhang; Shanfei Fu; Xiaolei Fan (Archives of Microbiology, 2026)

Promoter-driven enhancement of PHBV synthesis in recombinant Escherichia coli using glucose and propionate as carbon sources - Zhao-song Huang; Cheng-jiao Yu; Zi-miao Yan; Chang-feng Miao; Ling-yi Hou; Peng-fei Gu; Xiang-yu Fan; Qiang Li (Archives of Microbiology, 2026)

Effects of parachute science on local research capacity 降落伞科学对当地研究能力的影响 - Li Yang; Tao Chen; Colin A. Chapman; Paul A. Garber; Yu Xuan Fan; Tien Ming Lee; Michael Huffman; Juan Carlos Serio Silva; Carlos Peres; Onja H. Razafindratsima; Lwin Ngwe; Peng Fei Fan (Conservation Biology, 2026)
Strengthening research capacity is essential to address the global biodiversity crisis. Yet, parachute science often undermines this goal, and its prevalence, costs, and benefits are unclear. We analyzed 13,502 publications on primate research that we extracted from Scopus (1960–2022) to evaluate the effects of parachute science on local research capacity across primate‐range countries. We categorized these publications as local (LRP), collaborative (CRP), or parachute science (PSRP) research publications and categorized countries where the research took place as low‐ to middle‐income countries or high‐ to upper‐middle‐income countries. We used generalized linear mixed‐effects models to assess how parachute science influenced local research capacity. For 69% of PSRPs, the research was conducted in 59 low‐ to middle‐income countries. For 20% of LRPs, research was led by people from these 59 countries. The disparity in LRPs among country groups was large. Local research publications in high‐ to upper‐middle‐income countries were at least 3.6 times higher than those in low‐ to middle‐income countries. Before 2013, parachute science contributed to an increase in LRPs; this trend reversed after 2013, mainly resulting in a decline in LRPs across all countries and both income categories. Strengthening the capacity to share research in low‐ to middle‐income countries is urgent if international conservation commitments are to be met. We recommend establishing true collaborative and interdisciplinary research teams, expanding local research opportunities, and supporting long‐term research projects as key strategies for sustainable research capacity strengthening in low‐income countries.

Synergistic effect of IL-4 and simulated microgravity on osteogenic differentiation of periosteal stem cells - Li-Jin Liu; Fei-Xiang Lu; Xiao Yang; Yu-Bo Fan; Zhi-Hong Wu; Xin-Tong Wu; Lian-Wen Sun (Life Sciences in Space Research, 2026)

A win-win recycling strategy for spent lithium-ion batteries: Prioritized selective lithium extraction afterwards triggers intrinsic catalysis - Yifan Sui; Zeqiu Chen; Yue Chang; Yaoguang Guo; Jie Guan; Xuning Zhuang; Fei He; Zhenming Zhang; Weihua Gu; Qianqian Chen; Li Fan; Qin Xu; et al. (Journal of Hazardous Materials, 2026)

Characterization of volatile aroma profiles and identification of key stale odorants in albino green tea during accelerated shelf-life storage - Yi-Ming Yang; Bin-Hui Liao; Jin-Miao Zhao; Ying-Gou Zhao; Xiao-Gan Chen; Wen-Han Fan; Li-Qing Mei; Si-Qi Zhang; Hao-Wei Guo; Shu-Ying Gong; Jing-Fei Zhang; Fang-Yuan Fan (Food Control, 2026)

A machine vision-coupled colorimetric electrospun nanofiber film for on-site TVB-N prediction and freshness grading of pork - Tong Wan; Zhiran Liang; Fei Fan; Jingxuan Qiu; Caiyun Liu; Xin Wang (Food Control, 2026)

Multi-omics analysis and preliminary experimental validation of acetyl tributyl citrate (ATBC) promoting bladder cancer progression via the AKR1B1/EMT axis - Jirong Jie; Qiong Wang; Zhifeng Chen; Chenxi Hu; Zhuocheng Lai; Sulun Ke; Yuanchao Zhu; Fei Li; Qin Fan; Wanlong Tan (Environmental Pollution, 2026)

Regulating ion mobility for intelligent “on-off” switchable electromagnetic wave absorption of ionogels in both GHz and THz band - Ruochu Lei; Zheng Cheng; Haolin Lu; Jianbin Wang; Zhiwen Zhou; Fei Fan; Bo Shan; Yi Huang (Chemical Engineering Journal, 2026)

Multifunctional ion-conductive binders enabling HMX composites with enhanced safety, mechanical robustness, and self-healing - Hongxia Zhang; Shimin Zhang; Yibo Zhang; Fan Liao; Yanpeng Lv; Xin Ruan; Wenwen Deng; Guoqiang He; Fei Xiao; Chongwei An (Chemical Engineering Journal, 2026)

Sustainable Urban River Network: Integrating the River Ecological Sensitivity Index - Haibo Yang; Fan Wu; Tianji Dong; Fei Chen; Zheng Duan; Lan Feng; Longfei Hou (Water Resources Management, 2026)

Dehydroepiandrosterone activates ADGRG2 to regulate chloride homeostasis and sperm motility via Gs-cAMP pathways - Dan Jiang; Ji-Fei Han; Xian-Zheng Guo; Yu-Qi Ping; Fan Yang; Peng Xiao; Jin-Peng Sun; Xiao Yu; Zhao Yang; Hui Lin (Science China Life Sciences, 2026)

Observation of Concurrent Latitudinal and Longitudinal Fractionations of α- and β-HCH in Chinese Rural Surface Soil: Implications for Global Lifecycle - Shuai Hao; Yi-Fan Li; Wan-Li Ma; Li-Yan Liu; Zi-Feng Zhang; Wen-Long Li; Ning-Zheng Zhu; Pu-Fei Yang; Hong-Liang Jia; Min-Gang Cai; Roland Kallenborn; Derek CG Muir (Archives of Environmental Contamination and Toxicology, 2026)

Design, synthesis, characterization and exploration of anti-HBV activity of matrine-adenine hybrids - Meng-Fan Xie; Zhou-Fei Zheng; Jing-Lei Wang; Rong-Tao Li; Zhi-Jun Zhang (Molecular Diversity, 2026)

Improvement of the METRIC model for mapping actual evapotranspiration of irrigated vineyards: Case study of Chilean and Chinese regions - Yi Liu; Samuel Ortega-Farías; Weicai Yang; Yunfei Fan; Sufen Wang; Lei Gao; Daniel de la Fuente-Sáiz; Peng Zhao; Fei Tian (Computers and Electronics in Agriculture, 2026)

Plasma untargeted lipidomics based on UHPLC-Orbitrap-MS reveals potential biomarkers and the pathogenesis involved in Mycoplasma bovis pneumonia - Fei Yang; Fan Liu; Yufei Zhai; Shenghu He; Mengmeng Yang; Ke Li; Yanan Guo (Veterinary Microbiology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Holistic evolution of the Bohai Sea complex system: Insights from interacting drivers - Han Huang; Tao Zou; Teng Liu; Hongyu Wang; Zhixuan Wang; Ningning Tao; Yanfang Li; Hao Fan; Fei Xie; Weidong Zhai; Guizhi Wang; Yongwen Zhang; et al. (Marine Environmental Research, 2026)

Seasonal fate and removal of per- and polyfluoroalkyl substances in a wastewater treatment plant with a Bacillus bio-reactor - Sakhayana Nikolaevna Danilova; Si-Da Meng; Fei Chen; Zhi-Zhong Zhang; Bing-Feng Liu; Vasiliy Egorovich Kolodeznikov; Natalia Nikolaevna Petrova; Yi-Fan Li; Zi-Feng Zhang (Journal of Water Process Engineering, 2026)

Algal ecological dynamics tracking model for studying hydrodynamic impacts on algae transport and accumulation in a shallow lake - Fei Du; Xiaobo Liu; Shiyan Wang; Chang Liu; Aiping Huang; Weijie Wang; Budong Li; Rui Gao; Xin Tian; Zhen Han; Hao Fan; Bi Wu (Journal of Hydrology, 2026)

Sediment transport mechanisms in sediment-starved subaqueous deltas: insights from storm-induced gravity flows - Chunye Hu; Fan Zhang; Jin Li; Xiaolei Liu; Fei Xing; Renzhi Li; Hao Wu; Heyu Yu; Ya Ping Wang (Journal of Hydrology, 2026)

Per-and poly-fluoroalkyl substances in lung tissues and their association with lung cancer - Xi-Ze Min; Li Ma; Fei Chen; Ying-Hua Hu; Chao Jiang; Yi-Fan Li; Yue Han; Zi-Feng Zhang; Kurunthachalam Kannan (Journal of Hazardous Materials, 2026)

Sustainable management of plateau mountainous urban agglomerations based on the ecosystem services supply-demand balance: Application of scale and threshold effects - Xiaobao Wang; Xiaoqing Zhao; Yuju Ran; Yanmin Fan; Wentao Li; Xianmin Ye; Yuqin Zhou; Yanlin Wang; Fei Liu (Journal of Cleaner Production, 2026)

UiO-66-NH2 based metal organic framework reinforced cation exchange membrane for highly efficient monovalent ion selectivity - Ying Liu; Keke Fan; Zhimeng Li; Fei Yang; Xinbo Zhang (Journal of Environmental Chemical Engineering, 2026)

Polypeptide urea inhibits cadmium uptake by enhancing Ammonium Nitrogen absorption in rice roots - Yu Fan; Yujie Yuan; Yajun Wang; Zhiyou Gong; Xiufeng Mei; Yanqiu Chen; Zhitao Hu; Xin Ni; Fei Deng; Yong Chen; Jianfeng Hu; Youfeng Tao; et al. (Journal of Environmental Management, 2026)

The acidic deep eutectic solvent fractionation strategy mediates the co-production of lignin-containing microfibrillated cellulose and lignin nanospheres from crop straw waste - Chaojie Yang; Fan Yang; Na Pan; Hongyu Yuan; Yu Zhao; Shuanglin Chen; Jinguang Hu; Sherien Elagroudyd; Mei Huang; Yongjia Lei; Dong Tian; Fei Shen (Journal of Environmental Chemical Engineering, 2026)

The fermentation characteristics of the milk fermented by the combined starter culture of Lactobacillus delbrueckii, Lacticaseibacillus paracasei, and Kluyveromyces marxianus - Liao Deng; Fei Gao; Baosheng Cui; Jiatong Yao; Fan Zhang; Guangqing Mu; Yanfeng Tuo (Food Bioscience, 2026)

Edible bird's nest attenuates menopausal syndromes by stimulating extragonadal estrogen biosynthesis in ovariectomized rats - Daying Xia; Qunyan Fan; Ling Chen; Feifei Xu; Fei Liu; Maoshen Chen; Fang Zhong (Food Bioscience, 2026)

Prebiotic efficacy of green banana flour against antibiotic-associated diarrhea in juvenile mice - Zhengke Fu; Xiaoxia Wang; Yang Liu; Daying Xia; Yilin Song; Fan Xv; Maoshen Chen; Fang Zhong; Fei Liu (Food Bioscience, 2026)

Indole-3-propionic acid enhances intestinal health and protects against Aeromonas hydrophila infection in high-fat-diet fed Nile tilapia (Oreochromis niloticus) - Fei-Fei Ding; Shi-Qi Deng; Yu-Xin Fan; Shi-Yan Qiao; Gang Wang (Fish & Shellfish Immunology, 2026)

Unveiling fDOM dynamics in shallow lakes via a coupled “spectral-thermal” XGBoost-SHAP retrieval framework: Implications for water diversion management in Lake Honghu - Kai Yu; Yun Du; Wei Liao; Baoyin He; Fei Xiao; Xiaodong Li; Yan Ye; Yadong Zhou; Yiming Shen; Fan Yang; Xueer Geng; Qi Feng (Environmental Research, 2026)

Anodic potential and conductive carrier synergistically drive nitrite-free extracellular electron transfer-dependent anaerobic ammonium oxidation (Anammox) in mixed microbial communities - Yang-Guang Xia; Jun-Hong Zhou; Xiao-Li Yang; Fei-Fan Shi; Ru Fan; Jia-Ying Xu (Bioresource Technology, 2026)

Optimization of fermentation conditions for recombinant McXyn0243 xylanase from Malbranchea cinnamomea and its application in producing xylooligosaccharides from sugarcane bagasse - Jinghao Ma; Lin Dai; Ruiwen Cheng; Fei Xiao; Yongbo Qu; Jianshan Fu; Jianhui Wen; Rana Abdul Basit; Dafeng Yin; Guangsen Fan (Biocatalysis and Agricultural Biotechnology, 2026)

LDHA-Mediated H3K18 Lactylation Promotes the Glycolysis in Non-Small Cell Lung Cancer Through Targeting PTEN - Yufeng Shao; Xiaomin Duan; Guojian Gu; Qingfeng Zhu; Jian Shu; Fan Fei (Biochemical Genetics, 2026)

Monitoring of Oyster Reef Spatial Distribution with Thermal Infrared Band Data - Xirui Xu; Fei Wang; Weimin Quan; Ruiliang Fan; Wei Fan; Sanling Yuan (Fishes, 2026)
The spatial distribution of oyster reefs is an important indicator for assessing environmental changes in nearshore fishery habitats. However, due to tidal fluctuations, images of oyster reef distribution acquired under low-light conditions such as early morning or evening often exhibit common issues such as bright spots and shadows. Thermal infrared (TIR) images, which are unaffected by external lighting conditions, can effectively address this problem. Aerial imaging of Liya Mountain, Haimen, Jiangsu Province, China, was conducted in this study. Based on unmanned aerial vehicles (UAVs) imagery acquired in 2025 using multispectral and TIR sensors, the total oyster reef area was estimated to be 6.61 ha. When compared with the oyster reef distribution derived from visible light aerial imagery collected in 2023 under favorable environmental conditions, this represents a decrease of 0.36 ha (5.4%), with the largest individual reef measuring 3388.17 m2. To demonstrate the improvement in extraction accuracy achieved by integrating TIR data with multispectral imagery, the research team compared the extraction accuracy for oyster reefs of different sizes: a 1.91% improvement was observed for small reefs, a 9.02% improvement for middle reefs, and an 18.98% improvement for large reefs. Experimentally, the emissivity of oyster reefs was determined to be 0.982 ± 0.002 using an isothermal method in the laboratory. The emissivity derived from in situ measurements showed similar values, supporting the reliability of the laboratory result and providing a crucial parameter for the inversion of reef surface temperature. Experimental results demonstrate that the TIR band can effectively enhance the spatial accuracy of oyster reef measurements under low-light conditions.

Mechanism-guided deep learning for pest classification in tomato leaves - Mingji Wei; Fei Lyu; Shuai Lu; Weijie Liu; Zhaoxuan Fan; Ning Yang; Wenhao Hui (Computers and Electronics in Agriculture, 2026)

Development of an inactivated H9N2 subtype avian influenza serological DIVA vaccine using the chimeric A/B NA epitope approach - Jingfeng Zhang; Zhiyu Fan; Qunxing Pan; Fei Yu; Huawei Sun; Minhua Sun; Jinping Fu; Jiasheng Song (Veterinary Microbiology, 2026)

Distribution and evolution of distress in embankment-bridge transition sections of the Gonghe–Yushu Expressway in degrading permafrost regions - Bingyan Li; Minghao Liu; Yanhu Mu; Jing Luo; Xin Ju; Fei Yin; Fan Yu; Yunhui Huang (Transportation Geotechnics, 2026)

Burkholderia seminalis suppresses Fusarium wilt infection in banana by modulating cell wall integrity - Shazma Gulzar; Yaxin Xu; Fan Fiona Fei; Zan Yi; Chunxia Huang; Rahat Sharif; Zhihui Long; Yisha Lu; Huiling Zhan; Chunxiang Xu (Pesticide Biochemistry and Physiology, 2026)

Interfacial confinement surface modification (ICSM): A study on the chemical modification of external surfaces of porous powder - Dapeng Fan; Xin You; Haiqun Qi; Fei Zhao; Xupeng Li (Next Research, 2026)

Manganese acts as savior rather than accomplice of antibiotic stress: Dual cycles of ROS scavenging and Mnammox - Dong-Jun Hou; Wei-Lin Guo; Qian-Ru Liu; Hong-Wei Yang; Qiu-You Xu; Yun-Fei He; Nian-Si Fan; Ren-Cun Jin (Journal of Water Process Engineering, 2026)

A toxicity risk priority control list of FLCMs and their transformation products developed through machine-learning and deep-learning methods - Yingjie Xu; Meng Zhang; Hao Yang; Fan Fei; Tianlong Zheng; Jie Jin; Yu Li (Journal of Hazardous Materials, 2026)

Tailoring Mn d-band center and valence cycling for high-efficiency catalytic ozonation of ibuprofen in pharmaceutical wastewater treatment - Yunhan Jia; Dongyao Yue; Yizhen Cheng; Zhenbei Wang; Yatao Liu; Chen Li; Fan Li; Fei Qi; Amir Ikhlaq; Jolanta Kumirska; Ewa Maria Siedlecka; Oksana Ismailova; et al. (Journal of Hazardous Materials, 2026)

Machine learning-assisted unveiling of aroma modulation by inorganic nitrogen during cider fermentation by Pichia kluyveri - Yuxiang Zhang; Lixiang Zhang; Weiyi Fan; Fei Wang; Yitong Shen; Yahong Yuan; Jianping Wei; Tianli Yue (Food Research International, 2026)

Texture and structure of high-moisture extrudates produced from soybean protein isolates with different 7S/11S globulin ratios - Chengxin Fei; Lin Li; Ruojie Zhao; Xinrui Wang; Bei Fan; Liya Liu; Fengzhong Wang; Yatao Huang (Food Hydrocolloids, 2026)

Corrigendum to “Intestinal-derived ‘good cholesterol’ for gut health: A recombinant high-density lipoprotein/microsphere platform for refractory bacterial colitis” [Chem. Eng. J. volume 528 (2026) 172153/CEJ-D-25-37911] - Yongfeng Yu; Xin Xiang; Xuelian Fan; Yingxian Chen; Xiaolong Xu; Mengfei Xiang; Fei Chao; Jianzhong Shen; Xiaowei Ma (Chemical Engineering Journal, 2026)

Sequential drug-releasing electroactive wound dressing accelerates healing of diabetic infected wounds through microenvironmental remodeling - Dapeng Cui; Ziyuan Yang; Yupeng Zhang; Xiaopeng Suo; Ming Cheng; Shuang Fan; Cheng Yang; RuiXia Yu; Tao Wang; Lei Li; Jiaxin Cui; Zhongdi Liu; et al. (Chemical Engineering Journal, 2026)

Synergistic effects of Lewis-Brønsted dual acids on pore development of activated carbon in activation of cotton for enhanced adsorption of organic pollutants - Wenjian Liu; Fei Wu; Mengjiao Fan; Yunyu Guo; Yanmei Cai; Shu Zhang; Shuang Wang; Xun Hu (Biomass and Bioenergy, 2026)

Performance and Mechanism of Sulfathiazole Adsorption by Magnetic Biochar: Promoting Effect of Co-existing Polystyrene and Simultaneous Removal - Xilong Zhang; Zihan Tang; Fei Liu; Xiuping Hong; Yingying Zhang; Ting Fang; Rongjian Fan; Xin Wang (Water, Air, & Soil Pollution, 2026)

Stability Analysis of Deep-Buried Railway Tunnels in Inclined Layered Rock Mass - Jing Li; Qingguo Liang; Chuntan Fan; Weiyu Sun; Shicai Li; Fei Gao; Yun Han; Yuzhe Wu (Rock Mechanics and Rock Engineering, 2026)

Host-associated volatile cues drive foraging behavior of Trichopria drosophilae toward Drosophila suzukii-infested fruits - Hai-Kuan Sun; Fan Yang; Ze-Hua Wang; Ren Li; Guang-Hang Qiao; Qiu-Fei Li; Yu-Yu Wang; Shan-Ning Wang (Journal of Pest Science, 2026)

Notch1-dependent hippocampal apoptosis is associated with monocrotaline-induced anxiety-like behavior - Lai Baochang; Li Fan; Wang Fei; Yan Xianchun; Wang Zichen; Han Mengzhuan; Zhang Yiman; Kang Mengyang; Liu Bing; Wang Ying; Ma Qiang; Jia Pu; et al. (Toxicology, 2026)

Development and preliminary validation of a rapid on-site detection method for Schmallenberg virus using RT-RAA-LFD - Yiran Zhao; Ruojun Hao; Huixing Lin; Chaojian Shen; Fei Liu; Hongjie Fan; Yanke Shan (The Veterinary Journal, 2026)

Low temperature delays longan pulp breakdown through DlMYB108-DlPME17 transcriptional regulation - Qiu-yi Ye; Zhong-qi Fan; Wei Shan; Jian-fei Kuang; Jian-ye Chen; Wang-jin Lu; Hui Wang; Hetong Lin; Wei Wei (Postharvest Biology and Technology, 2026)

Overexpression of kiwifruit AcWRKY94 enhanced salt and osmotic stress tolerance in tobacco - Linghong Lu; Jing Gao; Xianbin Gu; Fei Fan; Genhua Song; Ming Xie; Huiqin Zhang (Plant Science, 2026)

East Asian monsoon and fluvial processes as joint drivers of detrital material transport along the upper Yellow River during the late Quaternary - Minmin Gao; Yuxin Fan; Fei Wang; Qingsong Cai; Ping Zhang; Chuanying Zhu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Fumaric acid restores neomycin efficacy against carbapenem-resistant Vibrio parahaemolyticus through metabolic reprogramming - Ziyi Zhang; Zhuoying Cao; Jiao Fei; Beibei Yan; Ting Zhang; Lvyuan Fan; Wenting Zhang; Chao Wang; Hao Wang; Yubin Su (Journal of Hazardous Materials, 2026)

Construction of CeO2/Bi2O3 heterojunction photocatalyst for the efficient degradation of organic dyes - Shen Hu; Qingyao Wang; Xu Gao; Shuaiqi Ren; Xiaoru Li; Ran Geng; Mengxiang Lei; Chunyan Zhang; Fan Fei; Kesheng Wang (Fuel, 2026)

Active control of autoignition inside prechamber for turbulent jet ignition regulation: An optical investigation - Jinze Li; Zhuohang Li; Yezeng Fan; Tiankui Zhu; Zhan Gao; Fei Ren; Ang Li; Lei Zhu; Zhen Huang (Fuel, 2026)

Triclosan induces spermatogenic damage via the oxidative stress-P53-apoptosis pathway in zebrafish - Fan Wang; Yiran Liu; Huiwen Yang; Ying Zhang; Fei Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Bimodal-pore hydrogel foam for multispectral electromagnetic defense with integrated environmental stability - Yawen Zhang; Jianbin Wang; Yang Wang; Zhuo Li; Fei Fan; Yi Huang (Chemical Engineering Journal, 2026)

Integrated physiological and multi-omics insights into Chlorella mutagenized by atmospheric and room temperature plasma for enhanced saline aquaculture wastewater treatment and bioresource production - Xiao-Ya Liu; Fan-Xing He; Tong-Chao Qu; Zhao-Hong Weng; Peng-Fei Li; Jie Ye; Hai-Yan Fu (Bioresource Technology, 2026)

Infiltration Characteristics of Film Hole Irrigation Under Different Soil Salinity Levels - Qianwen Fan; Liangjun Fei; Yalin Gao (Irrigation and Drainage, 2026)
With the increasingly severe shortage of agricultural water resources and the problem of land salinization, finding effective irrigation methods to improve soil conditions has become particularly important. The aim of this study was to investigate the effects of initial soil salinity on the infiltration characteristics of film hole irrigation. In this work, indoor soil box infiltration experiments were conducted to study the cumulative infiltration, the wetting front transport distance and the distributions of water–fertilizer–salt at the end of the infiltration process under film hole irrigation with clean water and muddy water with different salt contents. The results revealed that the higher the soil salinity was, the lower the cumulative infiltration per unit area, and the shorter the distance of wetting front transport. The greater the distance from the centre of the film hole was, the greater the soil electrical conductivity, and the lower the water content and nitrate nitrogen content. Compared with those under clean water irrigation, the desalination depth and horizontal desalination distance under muddy water irrigation were lower, and the salt ion content at the film hole was greater. The research results could provide a theoretical basis for further exploration of saline soil film hole irrigation.

A Review of Adaptive Mechanisms in Fish Retinal Structure and Opsins Under Light Environment Regulation - Zheng Zhang; Fan Fei; Liang Wang; Yunsong Rao; Wenyang Li; Xiaoqiang Gao; Ao Li; Baoliang Liu (Fishes, 2026)
Light, as one of the most crucial environmental factors, plays an essential role in the growth, physiology, and evolutionary survival of fish. To cope with diverse light conditions in aquatic environments, fish adapt through photosensory systems composed of both visual and non-visual pathways. The retina is a key component of the visual system of fish, capable of converting external optical signals into neural electrical signals, making it crucial for visual formation. During the process of visual signal transduction, opsins serve as the molecular foundation for vision formation. They can be divided into two major categories: visual opsins and non-visual opsins. Among these, melanopsin, as a member of the non-visual opsin family, acts as a key upstream factor in the circadian phototransduction pathway of fish. In this review, we review the adaptability of fish retinal structures to light reception and introduce in detail the gene diversity and relative expression levels of fish opsins. At the same time, we comprehensively describe the molecular mechanism by which fish adapt to changes in the underwater light environment. We also concluded that melanopsin, as a non-imaging photoreceptor, possesses not only core light-sensing functions but also non-imaging visual functions such as circadian rhythm regulation, body coloration changes, and hormone secretion. This review suggests that future research should not only elucidate the physiological functions of melanopsin in fish but also comprehensively reveal the mechanisms underlying the multi-adaptive nature of fish vision across varying light environments. Through these studies, researchers can have a deeper understanding of the physiological regulation mechanism of fish in complex light environments, and then formulate fish light environment management strategies, optimize aquaculture practices, improve economic returns, and promote the development of related fields.

A novel single-cell communication framework combining multi-omics reveals neuro-viral pathogenesis in fish - Yi-Fan Liu; Teng-Fei He; Zhi-Wen Zhao; Bao-Sheng Wu; Ying Liang; Lin-Miao Li; Jin-Ping Chen; Ye-Pin Yu (Marine Life Science & Technology, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Multi-USV cooperative encirclement strategy based on the double-layer prioritized replay mechanism in the reef sea area - Dongdong Mu; Fei Wang; Xinjie Han; Xiao Liang; Guibing Zhu; Yunsheng Fan (Ocean Engineering, 2026)

Dissection of the genetic basis of 1392 rice landraces and 770 hybrid combinations reveals great potential of rice landraces in hybrid rice improvement - Yinting Wang; Zixuan Li; Bi Wu; Xueqiang Wang; Wenyan Yang; Danjing Lou; Jinyue Ge; Ziran Liu; Wenlong Guo; Neng Zhao; Jun Yang; Weiya Fan; et al. (Molecular Plant, 2026)

Curcumin-mediated photodynamic action disturbs TOM70-depedent MIC60 import to damage mitonchondria against breast cancer - Xiang-Yi Zhao; Min Yan; Liang Zheng; Chang-Long Gou; Qi Huang; Liu-Gen Li; Xin-Ran Yu; Jing-Yu Lu; Cui Hu; Si-Han Zhang; Cunqing Kong; Fan Leng; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

A gas–liquid entrainment scrubber for fine silica dust control in an ore-crushing workshop: Industrial field testing and integrated assessment - Tao Wei; Ruhua Zhu; Bao Zhang; Linling Zhu; Simeng Fan; Huiqing Luo; Zhaoxing Li; Bulong Bu; Zhentao Li; Xiaochuan Li; Fei Gao (Journal of Cleaner Production, 2026)

β-defensin 2 enhances antiviral immunity via autophagy regulation during Micropterus salmoides rhabdovirus (MSRV) infection and promotes survival in largemouth bass - Yong-Fei Zhu; Xue-Ni Wang; Yi-Fan Hu; Chang-Hong Li; Jiong Chen (Fish & Shellfish Immunology, 2026)

Quantifying the trade-offs: Energy potential and environmental impacts of municipal landfill mining in China - Fan Fei; Xinyi Zhang; Qiaoqiao Gao; Zongguo Wen; Hongzhi Ma; Jiayue Zhang (Environmental Impact Assessment Review, 2026)

Selective control in the oxygen activation involved ROS generation over carbon nitride for long-term aerosol disinfection: Carbonyl location matters - Hanyu Zhang; Long Tan; Guochun Lv; Yaofang Fan; Munir Ahmad; Xiaojing Wang; Kai Wei; Hong Xiao; Hong Peng; Xiaohui Lu; Shihuai Deng; Fei Shen; et al. (Chemical Engineering Journal, 2026)

Intestinal-derived ‘good cholesterol’ for gut health: A recombinant high-density lipoprotein/microsphere platform for refractory bacterial colitis - Yongfeng Yu; Xin Xiang; Xuelian Fan; Yingxian Chen; Xiaolong Xu; Mengfei Xiang; Fei Chao; Jianzhong Shen; Xiaowei Ma (Chemical Engineering Journal, 2026)

Unraveling the role of stratospheric intrusion and biomass burning in springtime tropospheric ozone enhancement in Yunnan, China - Yuheng Chen; Fei Qiu; Wen Chen; Wenxuan Fan; Anjie Yin; Mingya Xie; Puyu Lian; Kaihui Zhao (Atmospheric Research, 2026)

Mutant library construction and green fluorescent protein expression in a marine fungus capable of plastics biodegradation - Rui Liu; Yani Wang; Zhenjie Su; Jun Yang; Fan Fei; Rongrong Gao; Chaomin Sun (Journal of Oceanology and Limnology, 2026)

Machine learning-assisted photoelectrochemical biosensor based on DNA-AgNCs nanowires for exosomal lncRNA intelligent diagnosis - Wenchao Geng; Jiangying Ji; Zhiyi Yan; Fan Wu; Jinyuan Chang; Jiarui Wei; Mengjiao Mei; Shang Chen; Fei Wang; Ruiying Yang (Analytica Chimica Acta, 2026)

Identifying key factors influencing the spatiotemporal variability of longline fishing activities in the Western and Central Pacific Ocean - Shenglong Yang; Wei Wang; Shengmao Zhang; Yumei Wu; Heng Zhang; Xiumei Fan; Fenghua Tang; Fei Wang (Fisheries Research, 2025)

Solid-mediated surface modification of biomass powders: A solvent-free strategy for green functionalisation of porous materials - Sixing Ning; Fei He; Guangzhen Ren; Xiaoshuo Zhu; Mingwei Li; Dapeng Fan (Sustainable Chemistry and Pharmacy, 2025)

Corrigendum to “Biochar-amended coastal wetland soil enhances growth of Suaeda salsa and alters rhizosphere soil nutrients and microbial communities” [Sci. Total Environ. 788 (2021), 147707] - Jing-Fang Cai; Fan Jiang; Xuan-Shao Liu; Kai Sun; Wei Wang; Ming-Xiang Zhang; Hong-Li Li; Wei-Jing Kong; Fei-Hai Yu (Science of The Total Environment, 2025)

Precise molecular spacer engineering for tumor-responsive pKa tuning: a pan-cancer imaging platform for evaluating tumor microenvironment reprogramming capability - Hong Zhang; Fei-Fan Xiang; Ding-Heng Zhou; Yan-Hong Liu; Zhou-Yu Wang; Shan-Yong Chen; Xiao-Qi Yu; Kun Li (Science Bulletin, 2025)

Monitoring vegetation recovery in abandoned mining areas using Sentinel-2A and UAV data: Evidence from the Hengshanli mine - BoWen Shi; Lv Zhou; Fei Yang; Fan Jiang; Jie Zhang; Xiang Huang; WenGuang Wei; Lin Jiang (Journal of Environmental Management, 2025)

Construction of a chlorophyll-mediated enhanced denitrifying sludge system and its response to imidacloprid stress - Xiao-Yan Fan; Fei Li; Ya-Bao Wang; Xing Li; Shen-Bin Cao; Jia-Wei Ren; Kai-Ling Pan (Journal of Environmental Chemical Engineering, 2025)

Green innovations and its dual impact on economic growth and environmental sustainability: Evidence from Vietnam - Ha Van Trung; Fan Fei; Patita Paban Mohanty; Muhammad Usman (Journal of Environmental Management, 2025)

Importance of inorganics in waste papers in regulating pore structures of resulting activated carbon for efficient removal of phenol and tetracycline - Fei Wu; Mengjiao Fan; Wenjian Liu; Lijun Zhang; Shu Zhang; Shuang Wang; Xun Hu (Environmental Research, 2025)

Synergetic enhancement of shear strength and ductility in reinforced concrete beams using FRP-UHPC stay-in-place formwork - Ke-Fan Weng; Ji-Xiang Zhu; Bo-Tao Huang; Jian-Guo Dai; Jian-Fei Chen (Engineering Structures, 2025)

Role of electrocoagulation-microfiltration in roof rainwater re-utilization: A novel insight into membrane fouling mechanisms through the combination of variations in interfacial properties on the membrane surface and membrane fouling model - Yaru Qiao; Zhenbei Wang; Fei Qi; Chen Li; Dezhi Sun; Yatao Liu; Fan Li; Chenxiao Shang; Jun Nan; Amir Ikhlaq (Desalination, 2025)

Site-specific substitution strategy for poisoning-resistant of ZrCo-based hydrogen isotope storage alloys - Shunrui Xiao; Jiacheng Qi; Jiapeng Bi; Fei Chu; Qianwen Zhou; Xiulin Fan; Jiahuan He; Xingwen Feng; Huaqin Kou; Xuezhang Xiao; Tao Tang; Wenhua Luo; et al. (Chemical Engineering Journal, 2025)

Engineering fast-response thermal control for dynamic gene expression design in Halomonas - Jian-Lian Wu; Ya-Ge Xiao; Bao-Wen Liu; Ling-Fan Tian; Ling-Fei Tian; Yu-Xi Li; Jia-Wen Peng; Hai-Fan Zhu; You-Yang Wang; Zhe-Yi Kuang; Jiang-Jie Tian; Shuai Zheng; et al. (Chemical Engineering Journal, 2025)

Mechanistic insights for DOM removal and membrane fouling mitigation: Optimizing Ferrate(VI)/AlCl₃ pretreatment and revealing the synergistic effect - Rui Zhang; Shaoyin Peng; Zhenbei Wang; Fei Qi; Chen Li; Yatao Liu; Fan Li; Amir Ikhlaq; Jolanta Kumirska; Ewa Maria Siedlecka; Oksana Ismailova; Zukhra Kadirova (Chemical Engineering Journal, 2025)

Structural characterization and oxidative stress modulation activity of an acidic Heteropolysaccharide from Microctis folium - Xiao-lu Liang; Yu-wen Liang; Jing Tian; Fei-fan Mo; Tian-ming Pan; Yan-feng Chen; Xiao-qi Shao; Kun-Ping Li (Carbohydrate Polymers, 2025)

The impact of triclosan exposure during the growth and development period on ovarian differentiation in female zebrafish and its mechanisms - Fan Wang; Xiangjie Meng; Xiaojiang Wang; Xiya Ma; Haiyan Zhang; Fei Liu; Haifang Liu (Aquatic Toxicology, 2025)

Transcriptome reveals carbon metabolite biosynthesis profiles related to culm solidification in Phyllostachys heteroclada f. solida - Fei Tan; Ziwu Guo; Ruicai Hu; Lili Fan; Shuanglin Chen (Planta, 2025)

Single-cell RNA-sequencing-guided reactive oxygen species-scavenging hydrogel design for regeneration of osteoporotic bone - Wei Hu; Tianyi Fei; Zhichao Liu; Yude Ding; Mengfei Yu; Fan Yang; Feiya Zhao (Journal of Zhejiang University-SCIENCE B, 2025)

Study on the Effects of Biochar on Water and Salt Transport Characteristics and Leaching Losses of Saline-Alkali Soil Under Muddy Water Conditions - Yalin Gao; Liangjun Fei; Aixia Wang; Youliang Peng; Qianwen Fan; Fangyuan Shen; Wenbin Liu; Zhen Xu; Yingjie Zhou (Journal of Soil Science and Plant Nutrition, 2025)

Enhancing production of nicotinamide mononucleotide by metabolic engineering and flow cytometry screening of Escherichia coli - Lu Yang; Yanwei Wei; Suzhen Yang; Fei Liu; Yan Li; Junqing Wang; Han Fan (Biotechnology Letters, 2025)

Research on Environmental Response Characteristic of Super-Long Inclined Shaft Tunnel and CO Diffusion and Ventilation Optimization of Blasting Procedures - Kong-fei Yu; Huai-bing Wang; Hong-yan Wang; Chen-qi Fan; Bu-rui Liu; Xuan-ke Ren (Applied Geophysics, 2025)

Anti-epidemic pharmaceuticals predominantly contributed to PPCPs flux in the Yangtze River during 2020 - Qinya Fan; Ye Hu; Shier Huang; Yan Guo; Jiaxun Guo; Fei Liu; Weixiao Qi; Huijuan Liu; Jiuhui Qu (Water Research, 2025)

Streptococcus suis employs the Ihk/Irr-PepO axis to subvert macrophage actin polymerization: A novel anti-phagocytic strategy enhancing bacterial virulence - Kaiyue Yang; Qiancheng Wang; Mingxing Liu; Dong Wei; Jinsheng Tang; Hong Zhou; Huixing Lin; Zhe Ma; Fei Pan; Hongjie Fan (Veterinary Microbiology, 2025)

High-performance dynamic radiative regulation via controllable macroscopic materials modulation - Ya Huang; Xueke Wu; Siming Zhao; Baoshun Wang; Zhuojing Zhao; Di Gao; Run Li; Yunrui Li; Fei Wang; Fan Lan; Yanlong Zhao; Rufan Zhang (Science Bulletin, 2025)

Microplastics: an overlooked particle organic carbon in river systems - Xuke Liu; Weijian Zhou; Peng Cheng; Fei Zhang; Liangcheng Tan; Yunchong Fu; Yukun Fan; Jianghu Lan; Huachun Gu; Wen Liu; Ting Wang (Science Bulletin, 2025)

Outdoor thermal comfort and multidimensional health effects of older adults in a subtropical city during autumn: roles of spatial type, activity, and urban–rural setting - Yuanjing Wu; Xinhui Fei; Songjun He; Wei Zhou; Shaozhen Fan; Yuping Tang; Qunyue Liu; Siren Lan (Energy and Buildings, 2025)

Separation of humic substances and inorganic salts from biogas slurry by a novel SiO2 interlayer-based loose nanofiltration membrane - Siwei Liang; Heng Lv; Hong Cai; Fan Ni; Yihao Hua; Fei Shen; Jing Yang; Jinsong He (Desalination, 2025)

All-climate carbonate electrolyte with 2-sulfobenzoic anhydride additive leads the way to high-performance commercial pouch sodium-ion batteries - Zujia Lu; Shufeng Li; Zetao Huang; Kaiyuan Wang; Weizhen Fan; Jingwei Zhao; Fei Wang; Zhuo Zeng (Chemical Engineering Journal, 2025)

Enhanced spatiotemporal prediction of rainfall erosivity through flood season data integration - Fei Qi; Yunpeng Wang; Luyue Xu; Xia Liu; Chunqiang Zhang; Zhaofei Fan; Jiayu Guo; Xing Yang (CATENA, 2025)

Recipient Periodic Fasting Promotes Osteogenesis of Implanted Mesenchymal Stromal Cell Aggregates and Safeguards Diabetic Mandibular Bone Regeneration - Zi-Qi Zhang; Yuan Yuan; Xiao-Hui Zhang; Jia-Ning Liu; Yuan Cao; Lu Liu; Lu-Fan Yang; Yi-Han Xiao; Shan-Shan Huang; Bing-Dong Sui; Jian-Fei Liang; Ji Chen; et al. (Stem Cell Reviews and Reports, 2025)

Fluorescent Nanosensor from Amphiphilic Block Copolymers Functionalized with 1,8-Naphthalimide for Acidic Environments - Fan Kong; Fei Fang (Journal of Fluorescence, 2025)

Unmasking per- and polyfluoroalkyl substances (PFAS) in facemasks: Occurrence and leaching implications - Xinyue Wang; Xuemei Liu; Xingyao Huang; Fan Chen; Yue Zhi; Qian Wang; Dongbei Yue; Xunchang Fei; Xiaoming Wang (Journal of Hazardous Materials, 2025)

New insights into the interaction between nanocolloid of graphene oxide and dissolved organic matter: Spectroscopic methods and density functional theory calculations - Ang Liu; Tuantuan Fan; Weibo Zhang; Xihuan Wang; Zhong Jin; Zeya Zhang; Peng Xia; Fei Guo; Chenglian Feng; Yingchen Bai (Journal of Hazardous Materials, 2025)

A marine fungus Alternaria alternata FB1 degrades polypropylene - Zhenjie Su; Fan Fei; Rui Liu; Chaomin Sun (Journal of Hazardous Materials, 2025)

Does green innovation play a crucial role for environment sustainability? Evidence from ASEAN countries - Fan Fei; Ha Van Trung; Patita Paban Mohanty (Journal of Environmental Management, 2025)

The ternary synergy of Fe, N and P enhances the membrane capacitive deionization performance of porous biochar - Houqi Zhou; Ting Xu; Chi Fei; Yilong Fan; Keying Tang; Chunyu Chen; Dianchun Ju; Han Ma; Zuoqiao Zhu; Rui Mao (Journal of Environmental Chemical Engineering, 2025)

Life Cycle Assessment of semi dry desulfurization ash resource utilization treatment: Calcium acetate production VS brick utilization - Hongzhi Ma; Hao Li; Fan Fei; Wei Su; Hao Wang; Ying Wang (Journal of Environmental Chemical Engineering, 2025)

Flavoromics analysis and sensory evaluation of wines produced from nine red grape cultivars in Manas region, Xinjiang, China: Implications for terroir adaptation - Ning Shi; Yi-Fan Zhao; Hao-Cheng Lu; Meng-Bo Tian; Ming-Yu Li; Jia-Yi Deng; Jia-Yan Wei; Ai-Sai Chen; Chi-Fang Cheng; Shu-De Li; Fei He; Keji Yu; et al. (Food Chemistry, 2025)

Ultrasound-assisted esterification of enzymatic starch for fabrication of OSA starch/chitosan complex granule: A stabilizer for Pickering emulsion - Junwei Fan; Wenkai Lyu; Jing Li; Fei Hu (Food Hydrocolloids, 2025)

Machine learning and causal inference for disentangling air pollution reduction during the Asian Games in megacity Hangzhou - Fan Zhang; Renchang Yan; Xianman Ye; Luolan Fei; Yaofu Zhu; Xiyao Chen; Shupeng Zhu; Bing Qi; Da Xu; Weijun Li (Environmental Pollution, 2025)

Multi-scale analysis of the influence of red-bed lithological interface on tunnel deformation and instability - Jing-Kai Qu; Yi-Guo Xue; Fan-Meng Kong; Cui-Ying Zhou; Zhen Liu; Zuo-Peng Wang; Jin-Rui Duan; Yan Ai; Zi-Ming Qu; Jian-Ning Wang; Bo Wang; Chao Lu; et al. (Engineering Geology, 2025)

The tissue-specific ferroptosis in zebrafish (Danio rerio) exposed to dibutyl phthalate at environmental-relevant concentrations - Tingting Hou; Fei Wang; Lei Wang; Huiqiang Zhang; Xiaoteng Fan (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Hierarchically engineered Janus fiber-hydrogel architecture: An ultrathin biomimetic skin for multiple-response sensing - Xingmei Wang; Yibo Sun; Fan Liu; Rongda Zhang; Tianyu Wang; Fei Jia; Guanghui Gao (Chemical Engineering Journal, 2025)

Synergistic role of Cu0 and acidic sites in Cu/Al2O3 catalysts for enhanced furfural hydrogenation to furfuryl alcohol - Shanguang Xu; Xin Han; Fan Zhang; Zhengyang Sun; Ruiying Chai; Fei Xu; Shanguo Du; Xiuling Jiao; Dairong Chen; Jie Zhang (Chemical Engineering Journal, 2025)

Superoxide radical induced layered reconstruction strategy for efficient direct regeneration of spent cathode materials - Yi Fan; Yongyou Su; Changyi Fan; Xingyi Peng; Zitong Fei; Qi Meng; Peng Dong; Yingjie Zhang (Chemical Engineering Journal, 2025)

Facile Synthesis of Support-Free Copper-Based Catalyst for PH3 Catalytic Oxidation in Micro-Oxygen - Yuan Li; Jun Fan; Bingyao Huang; Hongyan Li; Jie Zhao; Kai Li; Fei Wang (Water, Air, & Soil Pollution, 2025)

New species of green lacewings indicate the diversity of Mesypochrysa (Insecta, Neuroptera, Chrysopidae) from the Middle Jurassic of China - Yong-Fei Wang; Chao-Fan Shi; Dong Ren; Qiang Yang (The Science of Nature, 2025)

Optimized water-nitrogen management enhances soil nitrogen cycling and microbial functions to enhance wheat yield - Fangyuan Shen; Liangjun Fei; Youliang Peng; Runqiao Zheng; Qian Wang; Qianwen Fan; Yalin Gao (Plant and Soil, 2025)

Synthesis and biological evaluation of triazole alcohols containing an indole-3-methyl(phenyl)amino side chain against fluconazole-resistant Candida albicans - Zefei Fan; Lijiao Yang; Jidong Wang; Yafei Hou; Fei Zou; Tianyu Zhang; Yongyan Fu; Yue Zhang; Ruirui Wang; Shichong Yu; Guanghui Ni (Medicinal Chemistry Research, 2025)

Short- and Medium-Term Predictions of Spatiotemporal Distribution of Marine Fishing Efforts Using Deep Learning - Shenglong Yang; Wei Wang; Tianfei Cheng; Shengmao Zhang; Yang Dai; Fei Wang; Heng Zhang; Yongchuang Shi; Weifeng Zhou; Wei Fan (Fishes, 2025)
High-resolution spatiotemporal prediction information on fishing vessel activities is essential for formulating and effectively implementing fisheries policies that ensure the sustainability of marine resources and fishing practices. This study focused on the tuna longline fishery in the Western and Central Pacific Ocean (130° E–150° W, 20° S–20° N) and constructed a CLA U-Net deep learning model to predict fishing effort (FE) distribution based on 2017–2023 FE records and environmental variables. Two modeling schemes were designed: Scheme 1 incorporated both historical FE and environmental data, while Scheme 2 used only environmental variables. The model predicts not only the binary outcome (presence or absence of fishing effort) but also the magnitude of FE. Results show that in short-term predictions, Scheme 1 achieved F1 scores of 0.654 at the 0.5°-1-day scale and 0.763 at the 1°-1-day scale, indicating substantial improvement from including historical FE data. In medium-term predictions, Scheme 1 and Scheme 2 reached maximum F1 scores of 0.77 and 0.72, respectively, at the optimal spatiotemporal scale of 1°-30 days. The analysis also quantified the relative importance of environmental variables, with sea surface temperature (SST) and chlorophyll-a (Chl-a) identified as the most influential. These findings provide methodological insights for spatiotemporal prediction of fishing effort and support the refinement of fisheries management and sustainability strategies.

Mapping for Larimichthys crocea Aquaculture Information with Multi-Source Remote Sensing Data Based on Segment Anything Model - Xirui Xu; Ke Nie; Sanling Yuan; Wei Fan; Yanan Lu; Fei Wang (Fishes, 2025)
Monitoring Larimichthys crocea aquaculture in a low-cost, efficient and flexible manner with remote sensing data is crucial for the optimal management and the sustainable development of aquaculture industry and aquaculture industry intelligent fisheries. An innovative automated framework, based on the Segment Anything Model (SAM) and multi-source high-resolution remote sensing image data, is proposed for high-precision aquaculture facility extraction and overcomes the problems of low efficiency and limited accuracy in traditional manual inspection methods. The research method includes systematic optimization of SAM segmentation parameters for different data sources and strict evaluation of model performance at multiple spatial resolutions. Additionally, the impact of different spectral band combinations on the segmentation effect is systematically analyzed. Experimental results demonstrate a significant correlation between resolution and accuracy, with UAV-derived imagery achieving exceptional segmentation accuracy (97.71%), followed by Jilin-1 (91.64%) and Sentinel-2 (72.93%) data. Notably, the NIR-Blue-Red band combination exhibited superior performance in delineating aquaculture infrastructure, suggesting its optimal utility for such applications. A robust and scalable solution for automatically extracting facilities is established, which offers significant insights for extending SAM’s capabilities to broader remote sensing applications within marine resource assessment domains.

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

Synergy reduction of contaminants discharge and GHGs emission of liquor wastewater treatment plants: Benefits assessment and reconstruction strategies - Yujin Gan; Chenyu Wang; Keke Zhao; Xiao Guan; Chen Li; Zhenbei Wang; Yatao Liu; Fan Li; Fei Qi; Amir Ikhlaq; Oksana Ismailova; Zuhra Kadirova (Journal of Water Process Engineering, 2025)

Urban-industrial synergies in Sustainability: Evaluating the Co-processing of MSWI fly ash in industrial kilns from environmental and economic perspectives - Run Shi; Fan Fei; Xuguang Wang; Dawei Liu; Shuang Wu; Junwei Bai; Yan Zhang; Wei Su; Rongrong Lei; Hao Wang; Hongzhi Ma (Journal of Cleaner Production, 2025)

Regional pollution source apportionment and emission thresholds determination in Zunyi's major watersheds: Implications for environmental management - Keke Zhao; Yujin Gan; Chen Li; Xiao Guan; Zhenbei Wang; Fan Li; Yatao Liu; Fei Qi; Xingcheng Zhu (Environmental Pollution, 2025)

Two-stage dynamic shear response of square RC columns under lateral impact: Mechanisms, inertial force analysis, and punching shear resistance model - Fei-Fan Feng; Lin Chen; Dai-Jiang Zhou; Tao Liu; Dao-Gang Ou; Yong Lu (Engineering Structures, 2025)

Piezo/photo-catalytic nano-actuators modulating mechanical force for mechanosensitive anti-tumor immunotherapy - Cong Cong; Xuejiao J. Gao; Fei Ye; Xuwu Zhang; Yuchu He; Zhenhe Ma; Wenkang Tu; Weili Xue; Kelong Fan; Dawei Gao (Chemical Engineering Journal, 2025)

Glucose membrane-assist pyrolysis engineered ultrafine FeP/CoP3-doped hollow carbon nanospheres: Enhanced bifunctional oxygen catalysts for rechargeable zinc-air batteries - Fan Li; Jilan Long; Li Kang; Fei Zhao; Simeng Ding (Chemical Engineering Journal, 2025)

Applicability of temperature-phased anaerobic digestion in enhancing methanation of high-solid sludge: Process performance, microbial community analysis and energy balance assessment - Li-Jie Wu; Fei Ye; Fan Yang; Yong-Kang Lyu (Bioresource Technology, 2025)

Endothelial Cell Integrin α6 Regulates Vascular Remodeling Through the PI3K/Akt-eNOS-VEGFA Axis After Stroke - Bing-Qiao Wang; Yang-Ying Duan; Mao Chen; Yu-Fan Ma; Ru Chen; Cheng Huang; Fei Gao; Rui Xu; Chun-Mei Duan (Neuroscience Bulletin, 2025)

Construction of multifunctionalized (oxo)indoles via O-Selective interception of the zwitterionic intermediate with N=O - Bao-fan Wang; Ziming Qiu; Fei Lian; Mengke Zhang; Tai-chen Liu; Zheng-hui Kang; Jiu-ling Li (Molecular Diversity, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Prenatal exposure to PM2.5 constituents and newborn leukocyte telomere length in a prospective study: Windows of susceptibility and modification by maternal folic acid supplementation - Gaojie Fan; Qing Liu; Qing Fang; Fei Luo; Xiaofeng Huang; Heng Li; Wenwen Guo; Binghai Liu; Lianyan Yan; Liqin Hu; Chao Xiong; Zhongqiang Cao; et al. (Journal of Hazardous Materials, 2025)

Microbial mechanical insights into the cadmium accumulation of rice (Oryza sativa L.) grains in Cd-contaminated seleniferous paddy soils: A data-driven observational research - Haonan Zhang; Chendao Ruan; Lijiang Chen; Xiaojun Fan; Fei Jia; Jianhao Tong; Chun Zhang; Jiyan Shi (Journal of Hazardous Materials, 2025)

New data-driven off-site-supervision mode for flue gas emissions: Data mining of 713 municipal solid-waste incineration factories in China - Fan Fei; Xinyi Zhang; Qi Cheng; Zongguo Wen; Hongzhi Ma; Jiayue Zhang (Journal of Environmental Management, 2025)

Lavender-like NiV-LDH@P,Se-doped VNi-MOF heterostructure as high-performance electrode material for supercapacitor - Yanqiu Xie; Xin Gao; Haoze Wang; Carlos Garcia Nuñez; Fan Jiang; Qian Li; He Bai; Fei Yao; Hongyan Yue (Chemical Engineering Journal, 2025)

Injectable near-infrared photothermal responsive bone cement with mechanical adaptability and dynamic microenvironment regulation function for diabetic fracture healing - Fei Xue; Zhuo Liang; Jingdi Zhang; Mengnan Wen; Zhiwen Zhang; Qingqing Pan; Zhenlin Fan; Lei Wang; Xiansong Wang; Wenjie Ren (Chemical Engineering Journal, 2025)

Layered hydroxide-supported nano zero-valent iron via nanoarchitectonic design: Enhanced stability and degradation of fluorescent whitening agents - Fei Li; Chen Wang; Pingning Jin; Yaqi Lin; Yan Zheng; Jing Fan (Chemical Engineering Journal, 2025)

Correction to: Exosomal miR-17-92 Cluster from BMSCs Alleviates Apoptosis and Inflammation in Spinal Cord Injury - Wei Wang; Fei Yao; Haiyuan Xing; Fan Yang; Li Yan (Biochemical Genetics, 2025)

Exosomal miR-17-92 Cluster from BMSCs Alleviates Apoptosis and Inflammation in Spinal Cord Injury - Wei Wang; Fei Yao; Haiyuan Xing; Fan Yang; Li Yan (Biochemical Genetics, 2025)

Efficient mining of natural products from Mangrove streptomyces using NP-PRESS - Lin Yu; Junxiao Wang; Kai Jin; Fan Xu; Yi Huang; Ran Zhang; Yihan Wu; Fei Xu (Archives of Microbiology, 2025)

Air classification efficiency evaluation of landfilled municipal solid waste using experiments and a probabilistic method - Lin Feng Yu; Yu Qi Jin; Miao Xin Yuan; Fei Zhang; Jie Hu; Ji Wu Lan; Yu Fan Wei; Yun Min Chen; Han Ke (Waste Management, 2025)

Germline-specific deletion of testis-highly expressed Lrwd1 reveals nonessential roles in male fertility - Chunhai Luo; Dalin Liu; Ziqi Yu; Zhiwei Fan; Haoran Xu; Shumin Zhou; Xuanjing Zhu; Hanchao Liu; Lifu Shao; Yunhao Wu; Zhean Li; Fei Sun; et al. (Theriogenology, 2025)

Genome-wide identification reveals a bZIP transcription factor modulating chlorophyll catabolism during leaf yellowing in harvested Chinese flowering cabbage - Ze-xiang Zeng; Yuan Rong; Zhong-qi Fan; Xin-guo Su; Lin Chen; Yan-chao Han; Hang-jun Chen; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen (Postharvest Biology and Technology, 2025)

Identification, screening and transepithelial transport of ACE inhibitory peptides derived from gastrointestinal digested edible bird's nest - Wanghui Li; Feifei Xu; Fei Liu; Qunyan Fan; Baozhong Guo; Xuncai Liu; Maoshen Chen; Fang Zhong (Food Bioscience, 2025)

Modulation of microbial communities and flavor metabolism in rice-flavor baijiu fermentation by Huazhou Exocarpium Citri Rubrum - Puxi Fan; Yongtao Fei; Minhua Liang; Zhichao Zhang; Gongliang Liu; Weidong Bai; Wenhong Zhao; Mengmeng Zhang (Food Bioscience, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

GGT-targeting polysarcosine-decorated CaCO3 nanoplatform for ICD-enhanced breast cancer immunotherapy - Xikuang Yao; Fei Xiong; Haobo Chen; Xudong Cao; Qinyi Chen; Jiayu He; Liyuan Zhang; Weina Zhang; Wenpei Fan; Xin Li; Wei Huang (Chemical Engineering Journal, 2025)

Emerging tumor hypoxia-relieving nanotherapeutics for boosting photodynamic therapy - Fujun Yang; Fei Chen; Shumeng Li; Shuang Wang; Lin Peng; Shishan Deng; Fan Zhang; Udo Jeschke; Yuequan Wang; Cong Luo (Chemical Engineering Journal, 2025)

Study on the high-efficiency CO2 mineralization reaction mechanism of thermally modified materials from neutralized gypsum residue driven by sulfur vacancies in an aqueous environment - Yuwen Deng; Sisi Chen; Huidong Tang; Fei Wang; Yixing Ma; Lei Shi; Fan Du; Xin Sun; Kai Li; Ping Ning (Chemical Engineering Journal, 2025)

Reversing net loss but aggravating fragmentation of habitat in the global Asian elephant range in the mid-2010s - Xin Zhang; Ahimsa Campos-Arceiz; Fei Chen; Wenping Yin; Fei Xie; Jiejing Zhang; Hui Fan (Biological Conservation, 2025)

Comparative analysis of ancient aurorae records near the Maunder Minimum - Si Chen; Yong Wei; Hong Yuan; Xin’an Yue; Fei He; Limei Yan; Kai Fan; Yuqi Wang (Science China Earth Sciences, 2025)

Improving the accuracy of zenith tropospheric delay in TUW-VMF3 and GFZ-VMF3 using feedforward neural networks - Jian Li; Fei Yang; Lei Fan; Debao Yuan; Guifei Jing; Zhuangzhuang Wang; Jia Xie; Yanru Yang (GPS Solutions, 2025)

In situ monitoring of HCO3−, CO32− and NO3− dynamics during microalgae culture by UV resonance raman spectroscopy - Fei Zhang; Xun Wang; Yu Zhang; Zhen Zhu; Yiming Jiang; Guoqing Jia; Xupeng Cao; Fengtao Fan; Can Li (Algal Research, 2025)

Meta‐Omics Analysis Reveals Global Distribution of Toxic Pseudo‐nitzschia and Enhanced Neurotoxin Production Under Climate Warming - Dong Xu; Zhuonan Wang; Georgina L. Brennan; Yuqiu Wei; Guanchao Zheng; Qingshan Luan; Xintong Huang; Yanmin Sun; Jia Yang; Xiaowen Zhang; Ke Sun; Xiao Fan; et al. (Global Change Biology, 2025)
The harmful diatom Pseudo‐nitzschia produces the neurotoxin domoic acid (DA), threatening human health and seafood safety in a changing climate. However, global patterns of Pseudo‐nitzschia abundance and the responses of DA production to underlying environmental drivers remain poorly understood, hindering accurate projections of their responses to environmental change. Using global meta‐omics data from Tara Oceans, alongside field survey data from the Chinese coasts and the Southern Ocean, we present the first evidence that four of the most toxic species— Pseudo‐nitzschia multiseries , Pseudo‐nitzschia multistriata , Pseudo‐nitzschia delicatissima , and Pseudo‐nitzschia pungens —are prevalent not only in coastal ecosystems but also in open ocean environments, spanning from pole to pole. We identify rising temperatures are recognized as a key driver of Pseudo‐nitzschia 's spatial distribution, DA production, and biosynthetic metabolism. Global models suggest that by 2100, under the SSP2‐4.5 climate scenario, the abundance of P. multiseries will increase by approximately 75.4%, while toxin production will be even more significantly enhanced, rising by up to 200.4%. This study significantly expands the known global distribution of these neurotoxin‐producing diatoms and predicts their increasing prevalence and toxicity under future global changes.

Brain structural reorganization mediates the relationship between hearing loss and cognitive impairment - Yao Wang; Jianfen Luo; Wenqing Li; Yu Han; Wen Ma; Siqi Liu; Lei Xu; Zhaomin Fan; Yu Ai; Meixia Su; Fuxin Ren; Fuyan Li; et al. (Brain Imaging and Behavior, 2025)

Identifying and prioritizing organic toxicants in treated flowback and produced water from shale gas exploitation sites using an integrative effect-directed analysis and nontarget screening method - Liwei He; Fei Cheng; Fan Wu; Keshuo Zhang; Ling Zhang; Yingqi Du; Zhimin Zhou; Huizhen Li; Jiangmeng Kuang; Xiangying Zeng; Zhiqiang Yu; Jing You (Water Research, 2025)

Multi-stage dolomitization controlled by sedimentary facies and basement faults: Insights from the Middle Permian Maokou Formation of the Eastern Sichuan Basin, SW China - Rong Yang; Xiyan Yang; Yang Li; Cunhui Fan; Yue Li; Zisang Huang; Fei Huo; Xingzhi Wang; Xiangyu Fan (Marine and Petroleum Geology, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

Nanospecific effect rather than dissolved Cu2+ dominates the impact of CuO nanoparticles on soil microbiota - Yiguang Qian; Weixin Jiang; Ruhan Li; Fan Liu; Siyue Li; Fei Wang (Journal of Hazardous Materials, 2025)

Mariculture increases microbially-driven carbon metabolism and sequestration in coastal ecosystems - Huanping Liu; Yijun Fan; Erxin Su; Shengwei Liu; Yuzhen Ming; Zhenyu Huang; Huang Yu; Fei Liu; Cheng Wang; Xiaoli Yu; Mingyang Niu; Kun Wu; et al. (Journal of Environmental Management, 2025)

Using Lycopodium spores as an eco-friendly carrier for pendimethalin delivery to enhance the herbicidal activity and reduce its adverse effects - Teng-Fei Fan; Ya-Qiang Wang; Xi-Le Deng (Journal of Environmental Chemical Engineering, 2025)

Surfactant-modulated synthesis of BiOBr-C (C-Br channel) flower-like microspheres for efficient removal of different contaminants from water: Pathway, DFT calculation and degradation mechanism study - He Kang; Yiming Sun; Xiang Fei; Yongli Yin; Weidong Wu; Ting Fan; Yaqing Zhang; Xing Fan; Haifeng Zhou; Peng Liang (Journal of Environmental Chemical Engineering, 2025)

Novel RM based S-scheme heterojunction Bi2WO6/Fe2O3 as an effective activator for peroxydisulfate in the degradation of tetracycline hydrochloride under visible light: Preparation, application, and degradation mechanism - Wen Wang; Guangtao Wei; Zuodan Fan; Linye Zhang; Junchi Gu; Fei Gao (Journal of Environmental Chemical Engineering, 2025)

Study on novel alkali-activated cementitious grout for scour control of offshore foundation - Fei Sha; Yulong Dong; Shijiu Gu; Xiaochen Fan; Wenwen Xiao (Geomechanics for Energy and the Environment, 2025)

Exposure to green space and leukocyte mitochondrial DNA copy number in children and adolescents - Gaojie Fan; Xiaoning Lei; Qing Liu; Qing Fang; Fei Luo; Xiaofeng Huang; Heng Li; Wenwen Guo; Binghai Liu; Lianyan Yan; Liqin Hu; Jing Wei; et al. (Environmental Research, 2025)

Conservation effectiveness of Chinese protected areas on the completeness of medium- and large-bodied mammal community - Lu Zhang; Li Yang; Xinyu Huang; Sheng Li; Wei Wang; Chi Ma; Hanlan Fei; Pengfei Fan (Biological Conservation, 2025)

Characteristics of Energy Evolution and Strength Degradation of JINPING Marble in Multi-stage Compression Tests with Sustained Loading - Chen Fan; Xia-Ting Feng; Jun Zhao; Cheng-Xiang Yang; Meng-Fei Jiang (Rock Mechanics and Rock Engineering, 2025)

Defect-engineered indium–organic framework displays the higher CO2 adsorption and more excellent catalytic performance on the cycloaddition of CO2 with epoxides under mild conditions - Meiyu Ren; Bo Zhao; Chong Li; Yang Fei; Xiaotong Wang; Liming Fan; Tuoping Hu; Xiutang Zhang (Molecular Diversity, 2025)

Identification of Multi-functional Therapeutic Peptides Based on Prototypical Supervised Contrastive Learning - Sitong Niu; Henghui Fan; Fei Wang; Xiaomei Yang; Junfeng Xia (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Record High Temperatures in the Ocean in 2024 - Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Huai-Min Zhang; Andrea Storto; Karina Von Schuckmann; Yuying Pan; Yujing Zhu; Michael E. Mann; Jiang Zhu; Fan Wang; et al. (Advances in Atmospheric Sciences, 2025)
Heating in the ocean has continued in 2024 in response to increased greenhouse gas concentrations in the atmosphere, despite the transition from an El Niño to neutral conditions. In 2024, both global sea surface temperature (SST) and upper 2000 m ocean heat content (OHC) reached unprecedented highs in the historical record. The 0–2000 m OHC in 2024 exceeded that of 2023 by 16 ± 8 ZJ (1 Zetta Joules = 10 21 Joules, with a 95% confidence interval) (IAP/CAS data), which is confirmed by two other data products: 18 ± 7 ZJ (CIGAR-RT reanalysis data) and 40 ± 31 ZJ (Copernicus Marine data, updated to November 2024). The Indian Ocean, tropical Atlantic, Mediterranean Sea, North Atlantic, North Pacific, and Southern Ocean also experienced record-high OHC values in 2024. The global SST continued its record-high values from 2023 into the first half of 2024, and declined slightly in the second half of 2024, resulting in an annual mean of 0.61°C ± 0.02°C (IAP/CAS data) above the 1981–2010 baseline, slightly higher than the 2023 annual-mean value (by 0.07°C ± 0.02°C for IAP/CAS, 0.05°C ± 0.02°C for NOAA/NCEI, and 0.06°C ± 0.11°C for Copernicus Marine). The record-high values of 2024 SST and OHC continue to indicate unabated trends of global heating.

National Inventory of Plastic Mulch Residues in Chinese Croplands From 1993 to 2050 - Jizhao Dai; Can Hu; Markus Flury; Yao Huang; Matthias C. Rillig; Dechang Ji; Jianwei Peng; Jiangchi Fei; Qing Huang; Youcai Xiong; Ning Yang; Davey L. Jones; et al. (Global Change Biology, 2025)
Agricultural plastic mulch films are a major source of plastic pollution of croplands. In China, which uses about 68% of the plastic mulch film produced globally (ca. 1.4 million tonnes y −1 ), soils have been heavily contaminated with mulch fragments. Here, we collected a national dataset of macroplastic residues (> 5 mm) in soil, including 3145 sampling sites, and provincial plastic film usage from 1992 to 2019 in China, and we established a linear model between the residue amount and historical cumulative usage within each province. Using the model, we quantified the amount of macroplastic residues in Chinese croplands on a national scale during the past 30 years and predict plastic pollution until 2050. Our results reveal the total national amount of plastic mulch residue in 2020 to be 2.07 million tonnes with a 95% CI of [1.67, 2.58]. This accumulated amount of plastic in Chinese soils roughly equals the annual amount of plastic films used globally (2.08 million tonnes in 2018) and is about 8% of national historically used plastic mulch film (27.3 million tonnes) remaining in soil as legacy plastic. Plastic concentrations in Chinese croplands in 2020 range from 7.7 kg ha −1 in Anhui to 399 kg ha −1 in Xinjiang, with an average value of 119 kg ha −1 (equivalent to 0.03 g kg −1 soil). We predict that the total amount and average concentration of plastic residues in Chinese croplands will reach 6.24 million tonnes and 357 kg ha −1 (equivalent to 0.1 g kg −1 soil) in 2050 under current plastic usage. There is an urgent need for regulatory actions to control plastic pollution in Chinese agriculture.

Self-assembled nanoparticle vaccine based on the grass carp ferritin remarkably enhance the protective immune responses against GCRV type II infection - Fei-Fan Xu; Zhu-Yang Deng; Jing-Kai Li; Le-Yang Chen; Yong-Qi Liu; Hai-Feng Jiang; Bin Zhu (Aquaculture, 2025)

Proteome profiling of the lung tissues of the mice co-infected with H9N2 influenza A virus and Pseudomonas aeruginosa - Sun Ying-Li; Fan Hua; Li Wen-qian; Li Dan; Bai Ke-fei; Dong Lu-jiao; Zhang Hui-ning; Li Jian-liang; Xie Zhi-jing (Veterinary Microbiology, 2025)

Influence of drainage system on the stability of underground CAES gas storage under different lateral pressure coefficients - Aohui Zhou; Peng Li; Liyang Fan; Zhuowei Yi; Xibo Tang; Wenbin Fei (Tunnelling and Underground Space Technology, 2025)

Experimental study on smoke movement characteristics and temperature distribution in high geothermal tunnel fire during construction with shaft structures - Chuangang Fan; Maozhen Liu; Xiaoxian Fei; Jiayi Ha; Linbo Du; Ao Jiao; Yuhao Li (Tunnelling and Underground Space Technology, 2025)

Chemical activation of willow with co-presence of FeCl3 tailors pore structure of activated carbon for enhanced adsorption of phenol and tetracycline - Wenjian Liu; Mengjiao Fan; Kai Sun; Xiao Cheng; Fei Wu; Shu Zhang; Xun Hu (Science of The Total Environment, 2025)

Sustainable water desalination with anti-wetting Janus membranes under simulated industrial low-grade fluctuated heat conditions in DCMD - Muhammad Mujahid; Muhammad Ali Hasnain; Ghafoor Ahmad; Chao Wang; Fan Xiao; Zhe Wu; Long-Fei Ren; Jiahui Shao (Process Safety and Environmental Protection, 2025)

Effects of germination on the digestibility of instant soybean powders based on an in vitro digestion model of the aged static gastrointestinal tract - Xinrui Wang; Bei Fan; Yang Li; Yangyang Xiong; Chengxin Fei; Litao Tong; Yatao Huang; Fengzhong Wang (Food Chemistry, 2025)

Impact of microwave treatment on polyphenols in safflower seeds and oil - Zhi Qin; Xu Fang; Jia-Lin Fei; Wei Fan; Zi-Meng Chen; Wen-Jie Liao; Ling-Biao Gu; Hua-Min Liu; Zhao Qin; Xin-Liang Zhu; Xue-De Wang (Food Chemistry, 2025)

Mechanistic insights into the influence of dissolved organic matter in stormwater runoff on the TOrCs degradation by PB-Fe@CN: Reaction kinetics and degradation pathways - Yatao Liu; Dongyao Yue; Jiamin Chen; Yang Yang; Ronghua Xu; Zhenbei Wang; Chen Li; Fan Li; Fei Qi; Ewa Maria Siedlecka; Jolanta Kumirska; Amir Ikhlaq; et al. (Chemical Engineering Journal, 2025)

Acid etching V2O5 nanowires cathode for high-performance zinc-ion full batteries - Huan-zhang Wen; Aiqun Kong; Yun-fei Shen; Yun-qi Fan; Jian-jie Liu; Long Chen (Chemical Engineering Journal, 2025)

Short-term thermal perception and evaluation model under temperature step changes of building transition spaces - Jiajing Wang; Yan Wang; Qiwei Dong; Wanxiang Yao; Lixin Sun; Hongbin Zhao; Fan Fei (Building and Environment, 2025)

Urban heat health risk inequality and its drivers based on local climate zones: A case study of Qingdao, China - Fei Guo; Guining Fan; Jun Zhao; Hongchi Zhang; Jing Dong; Hui Ma; Na Li (Building and Environment, 2025)

Prediction of Pharmacoresistance in Drug-Naïve Temporal Lobe Epilepsy Using Ictal EEGs Based on Convolutional Neural Network - Yiwei Gong; Zheng Zhang; Yuanzhi Yang; Shuo Zhang; Ruifeng Zheng; Xin Li; Xiaoyun Qiu; Yang Zheng; Shuang Wang; Wenyu Liu; Fan Fei; Heming Cheng; et al. (Neuroscience Bulletin, 2025)

Effects of the interspecific competition between Eichhornia crassipes and Alternanthera philoxeroides and the additional impact of their biological control agents: relevance for aquatic weed management - Zhenhuan He; Xiaoliang Zhang; Shufeng Fan; Rui Chen; Jieyu Sun; Fei Ma; Peidong Zhao; Jinfu Liu; Haiyan Zhang; Chunhua Liu (Hydrobiologia, 2025)

The role of symbiotic nitrogen-fixing bacteria, Rhizobium and Sinorhizobium, as “bridges” in the rhizosphere of legumes after fomesafen application - Wei Chen; Yuntao Li; Gaoling Shi; Guangping Fan; Fei Tong; Lizhu Liu; Jiangye Li; Yan Gao (Applied Soil Ecology, 2025)

Correction to: Influence of Synoptic Pattern on the Spatiotemporal Features and Diurnal Variation of Extremely Persistent Heavy Rainfall over the Sichuan Basin, China - Fan Xia; Xiaogang Huang; Jianfang Fei; Ju Wang; Xiaoping Cheng; Chi Zhang (Advances in Atmospheric Sciences, 2025)

Effects of Fermented Soybean Meal Replacing Fishmeal and Adding Lentinus edodes Fermentation Supplementation on Japanese Eel (Anguilla japonica) Cultivated in Pond Cage - Jie Yu; Fei Xiao; Qian Xiao; Dongming Chen; Guoyong Zhou; Huanbin Jiang; Xiaoya Fan; Herong Shi; Huihong Zhao (Fishes, 2025)
Replacing fishmeal (FM) with plant-based protein sources remains a significant challenge, particularly for carnivorous fish. This study investigates the effect of dietary Lentinus edodes fermentation (LEF) supplementation on Japanese eel (Anguilla japonica) fed with fermented soybean meal (FSM) as a partial FM replacement. The positive control consisted of 64% FM (Con), and the negative control (FSM group) included 52% FM plus 12% FSM. Two experimental diets were formulated by adding 2% LEF (LEF2 group) and 3% LEF (LEF3 group) to the negative control diet. The experimental diet was administered to Japanese eels weighing 62.50 ± 2.14 g for 12 weeks. The experimental fish were randomly assigned to four groups, with three replicates of 100 fish per group. The results indicated that growth performance and feed efficiency were significantly reduced in the FSM group, but were significantly improved by LEF supplementation (p 0.05), but significantly increased muscle amino acid content and levels of certain fatty acids (linoleic acid, γ-linolenic acid, eicosatrienoic acid, DHA) (p

PIM1 enhances insulin secretion and inhibits ferroptosis of high glucose-induced pancreatic β-cells through strengthening PINK1/Parkin-mediated mitophagy via inactivating JNK/p38 signaling pathway - Bingjie Fan; Lili Yin; A.’ni Wang; Fei Li; Shuguang Han (Tissue and Cell, 2025)

Thioketal-photocage: a universal modification strategy for constructing new photochemical tools for real-time imaging in living cells - Ding-Heng Zhou; Shan-Yong Chen; Yan-Zhao Liu; Hong Zhang; Jun-Mei Li; Qian Zhou; Fei-Fan Xiang; Xiao-Qi Yu; Kun Li (Science Bulletin, 2025)

Is multi-source solid waste co-disposal practices in waste-to-energy plants sustainable? A comparative life cycle assessment - Jiayue Zhang; Fan Fei; Zixuan Jiang; Kosajan Vorada; Zheng Hao Leong; Zongguo Wen; Hongbo Zhang; Shufei Han (Resources, Conservation and Recycling, 2025)

Mineralogy, geochemistry, and S isotope investigation of seafloor massive sulfides from the Yunzang hydrothermal field, South Atlantic Ridge - Wen-Sheng Li; Pei Ni; Xue-Fa Shi; Bing Li; Shao-Wen Liu; Stefano Albanese; Fei-Peng Fan; Guan-Hua Wang; An-Qi Hong (Journal of Geochemical Exploration, 2025)

Catalytic oxidation of ultralow concentration methane using solid wastes or natural ores as catalysts - Haiming Wang; Yuchen Fan; Fei Xie; Yilin Liu; Wenjie Zhang; Xu Zhou; Qigang Deng; Changfu You (Journal of Environmental Chemical Engineering, 2025)

Enhanced impact of western North Pacific tropical cyclones on El Niño intensity in the past 40 years - Xingfang Huang; Fei Huang; Hengxin Qu; Tingting Fan; Shibin Xu (Atmospheric Research, 2025)

Publisher Correction: Flow Velocity Modulates Growth, Oxidative Stress, and Transcriptomic Responses in Spotted Sea Bass (Lateolabrax maculatus) - Shuo Li; Yuyan Liu; Qian Wang; Zhiwen Zhu; Weijing Li; Chen Li; Fan Fei; Baoliang Liu; Changwei Shao (Marine Biotechnology, 2025)

Flow Velocity Modulates Growth, Oxidative Stress, and Transcriptomic Responses in Spotted Sea Bass (Lateolabrax maculatus) - Shuo Li; Yuyan Liu; Qian Wang; Zhiwen Zhu; Weijing Li; Chen Li; Fan Fei; Baoliang Liu; Changwei Shao (Marine Biotechnology, 2025)

The clinical characteristics of Streptococcus equi ssp. zooepidemicus causing acute death in pigs and its prevention with chimeric monoclonal antibodies - Chen Yuan; Yuchang Wang; Xiaowen Zhang; Xingyu Tian; Ying Liang; Fei Pan; Haoshuai Song; Linya Xia; Zhihui Wu; Wenqing Wang; Xiaowen Zhang; Yurui Xie; et al. (Veterinary Microbiology, 2025)

NDO-enhanced adaptive fixed-time prescribed performance sliding mode tracking control for coaxial cross-domain flying buoys under unknown ocean disturbances - Mingqing Lu; Menglei Tu; Fei Liao; Shichong Wu; Beibei Xing; Zhaolin Fan; Yumin Su; Wenhua Wu (Ocean Engineering, 2025)

Complete genome sequence of the marine mangrove fungus Sarcopodium sp.QM3–1 confirmed its high potential for antimicrobial activity - Wenzhou Zhang; Minghuang Ling; Kai Zhang; Ruzhen Liu; Xiaomei Huang; Gaili Fan; Hans-Peter Grossart; Fei Peng; Zhuhua Luo (Marine Genomics, 2025)

Effects of different drying methods on the structure, bioaccessibility, and bioavailability of selenium-enriched peptides from soybean sprouts - Yangyang Xiong; Bei Fan; Lin Li; Yanfang Liu; Xinrui Wang; Chengxin Fei; Litao Tong; Fengzhong Wang; Yatao Huang (Food Chemistry, 2025)

Mitigating LPS-induced stress in Chinese mitten crab (Eriocheir sinensis) with P4’ peptide-bearing Bacillus subtilis - Chao-Fan He; Ye Yang; Yong Liu; Xiang Liu; Xiang-Fei Li; Guang-Zhen Jiang; Wen-Bin Liu (Fish & Shellfish Immunology, 2025)

Can lignin nanosphere be used as a recycled sacrificed template for constructing high performance loose nanofiltration membranes? - Jinsong He; Wenjie Liu; Fan Ni; Dong Tian; Yongjia Lei; Jianmei Zou; Yanzong Zhang; Fei Shen; Xiaochan An (Desalination, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Corrosion behavior of WC-NiMoCrFeCo coating in seawater environment: Positive corrosion inhibition of a novel dynamic reaction product - Yu-Hang Zhang; Yao-Ning Sun; Xiu-Juan Fan; Bo-Kai Liao; Chun-Ming Deng; Shuang-Jian Li; Chao Wang; Yi-Fei Xv; Kang Li; Yi-Zhe Lv (Chemical Engineering Journal, 2025)

A photoswitchable phase-reversible gel engine for systemic redox homeostasis remodeling and on-demand chemodynamic immunotherapy with sustainable immunostimulation - Minghao Sun; Weiwei Liu; Yuanyuan Ma; Pengfei Ni; Wenjing Yao; Yingjie Xu; Rui Bao; Jue Wang; Fei Xiong; Xihe Kuang; Teng Zhang; Xiaochen Zhang; et al. (Chemical Engineering Journal, 2025)

Measurement and spectral analysis of medical shock wave parameters based on flexible PVDF sensors - Liansheng Xu; Fei Shen; Fan Fan; Qiong Wu; Li Wang; Fengji Li; Yubo Fan; Haijun Niu (Physical and Engineering Sciences in Medicine, 2025)

A New Pattern of Species Diversification Revealed by Populus on the Qinghai-Tibet Plateau - Jia-Xuan Mi; Fei-Fei Tian; Jin-Liang Huang; Yu-Jie Shi; Jing Li; Fan-Yu Meng; Fang He; Yu Zhong; Han-Bo Yang; Fan Zhang; Liang-Hua Chen; Xue-Qin Wan (Evolutionary Biology, 2025)

2D Laplace-Fourier domain acoustic wave equation modeling with an optimal finite-difference method - Jing-Yu Wang; Na Fan; Xue-Fei Chen; Shou-Rui Zhong; Bo-Yu Li; Dan Li; Gang Zhao (Applied Geophysics, 2025)

Influence of Synoptic Pattern on the Spatiotemporal Features and Diurnal Variation of Extremely Persistent Heavy Rainfall over the Sichuan Basin, China - Fan Xia; Xiaogang Huang; Jianfang Fei; Ju Wang; Xiaoping Cheng; Chi Zhang (Advances in Atmospheric Sciences, 2025)

Toward an integrated pantropical ocean observing system - Gregory R. Foltz; Yassir A. Eddebbar; Janet Sprintall; Antonietta Capotondi; Sophie Cravatte; Peter Brandt; Adrienne J. Sutton; Tamaryn Morris; Juliet Hermes; Clive R. McMahon; Michael J. McPhaden; Lev B. Looney; et al. (Frontiers in Marine Science, 2025)
Global climate is regulated by the ocean, which stores, releases, and transports large amounts of mass, heat, carbon, and oxygen. Understanding, monitoring, and predicting the exchanges of these quantities across the ocean’s surface, their interactions with the atmosphere, and their horizontal and vertical pathways through the global oceans, are key for advancing fundamental knowledge and improving forecasts and longer-term projections of climate, weather, and ocean ecosystems. The existing global observing system provides immense value for science and society in this regard by supplying the data essential for these advancements. The tropical ocean observing system in particular has been developed over decades, motivated in large part by the far-reaching and complex global impacts of tropical climate variability and change. However, changes in observing needs and priorities, new challenges associated with climate change, and advances in observing technologies demand periodic evaluations to ensure that stakeholders’ needs are met. Previous reviews and assessments of the tropical observing system have focused separately on individual basins and their associated observing needs. Here we provide a broader perspective covering the tropical observing system as a whole. Common gaps, needs, and recommendations are identified, and interbasin differences driven by socioeconomic disparities are discussed, building on the concept of an integrated pantropical observing system. Finally, recommendations for improved observations of tropical basin interactions, through oceanic and atmospheric pathways, are presented, emphasizing the benefits that can be achieved through closer interbasin coordination and international partnerships.

Provenance of fine-grained Quaternary sediments in the Tengger Sandy Desert recorded by Sr-Nd isotopes and its linkage with Quaternary aeolian silts on the Chinese Loess Plateau - Yuxin Fan; Minmin Gao; Fei Wang; Qingsong Cai; Guangliang Yang; Chunlei Zong; Ke Bi; Xueyu Yan; Qiang Shu; Bowen Kong (Quaternary Science Reviews, 2025)

Structural parameters analysis and optimization design study of double-pier linkage-type anticollision device - Yichang Cai; Bohan Ma; Fei Wang; Yuanji Fan; Huijuan Chang; Haiqi Zhang; Yonggang Wang; Yuxuan Zheng (Ocean Engineering, 2025)

Corrigendum to “Long-term warming and acidification interaction drives plastic acclimation in the diatom Pseudo-nitzschia multiseries” [Mar. Environ. Res. 204 (2025) 106901] - Yanmin Sun; Fan Yang; Ran Duan; Dong Xu; Yanan Zhang; Chengwei Liang; Zhuonan Wang; Xintong Huang; Bingkun Wang; Yapeng Wang; Haoming Sun; Naihao Ye; et al. (Marine Environmental Research, 2025)

Long-term warming and acidification interaction drives plastic acclimation in the diatom Pseudo-nitzschia multiseries - Yanmin Sun; Fan Yang; Ran Duan; Dong Xu; Yanan Zhang; Chengwei Liang; Zhuonan Wang; Xintong Huang; Bingkun Wang; Yapeng Wang; Haoming Sun; Naihao Ye; et al. (Marine Environmental Research, 2025)

Meso-mechanical mechanism of ordered mica alignment on the progressive failure process of granite under different lateral stress directions - Chen Fan; Xia-Ting Feng; Jun Zhao; Cheng-Xiang Yang; Meng-Fei Jiang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Selecting of lactic acid bacteria from traditionally fermented food and their application in functional raspberry fermented beverage - Yongtao Fei; Yihe Huang; Puxi Fan; Jianjun Shen; Weidong Bai; Gongliang Liu (Food Bioscience, 2025)

Wheat tends to accumulate higher levels of cadmium in the grains than rice under a wide range of soil pH and Cd concentrations: A field study on rice-wheat rotation farmland - Yuntao Li; Guangping Fan; Yan Gao; Wei Chen; Gaoling Shi; Fei Tong; Lizhu Liu; Dongmei Zhou (Environmental Pollution, 2025)

Interfacial shear behavior between prefabricated Strain-Hardening Ultra-High-Performance Concrete (SH-UHPC) and cast-in-place concrete - Ke-Fan Weng; Ji-Xiang Zhu; Bo-Tao Huang; Jian-Guo Dai; Jian-Fei Chen (Engineering Structures, 2025)

Corrigendum to “Platelet-rich plasma/chitosan/chondroitin sulfate immunomodulatory hydrogel co-networks for diabetic wound repair: Functions and molecular mechanisms” [Chem. Eng. J. 491 (2024) 152138] - Zi-Lin Wang; Lin-Yue Li; Hong-Jie Liu; Ya-Ling Fan; Yu-Xue Shen; Fei Song; Li-Li Zhu (Chemical Engineering Journal, 2025)

Genomic analysis of modern maize inbred lines reveals diversity and selective breeding effects - Kaijian Fan; Mohsin Ali; Kunhui He; Yingwei Feng; Tingxi Yu; Hao Zhang; Tai An; Weiwei Zeng; Junjie Fu; Ying Zhou; Yanfang Heng; Fei Gu; et al. (Science China Life Sciences, 2025)

Time-Dependent Asymmetric Instability in a Deep TBM Tunnel Due to the Combination of Mesoscopic Rock Heterogeneity and Triaxial Stress - Chen Fan; Xia-Ting Feng; Jun Zhao; Cheng-Xiang Yang; Meng-Fei Jiang (Rock Mechanics and Rock Engineering, 2025)

Draft Genome of Naganishia uzbekistanensis from a Clinical Pulmonary Infection - Rong-Chen Dai; Xin-Fei Chen; Xin Fan; Li Gu; Li Zhang; Dan Guo; Ying-Chun Xu; Meng Xiao (Mycopathologia, 2025)

Vocal differences in note, sequence and great call sequence among three closely related Nomascus gibbon species - Pu Han; Hai-gang Ma; Zi-di Wang; Peng-lai Fan; Peng-fei Fan (International Journal of Primatology, 2025)
The vocal structure of gibbons has long been believed to be under strong genetic control and consistent with phylogeny. Gibbon vocalizations show hierarchical structures and song coordination behaviors, which may have different functions and convey distinct information compared to basic notes. However, previous studies have not compared vocalizations at multiple levels across species. We compared the vocal structures of three Nomascus species in the wild in South China, namely the western black gibbon ( Nomascus concolor ), Cao vit gibbon ( N. nasutus ), and Hainan gibbon ( N. hainanus ) at the levels of note (six features of four types of notes), male sequence (eight features), and song coordination (four features of the overlap pattern between male and female songs). We selected 15 recordings for each species: N. concolor (six groups, 2006 to 2021), N. nasutus (seven groups, 2008 to 2021), and N. hainanus (six groups, 2020 to 2021). We used permuted random forest analysis to test for species differences in vocal structure and the contribution of acoustic features to species differences at each level. We used acoustic features to construct a hierarchical clustering tree, and compared it with phylogenetic relationships. We found significant differences at all levels except the boom note. Acoustic similarity did not match genetic similarity in boom and pre-modulated notes, suggesting that genetic differences are not the only factor leading to species differences in vocal structures. We also found different contributions of acoustic features to differentiation in vocal structure at different levels. Our study suggests that we need to compare gibbon vocalizations at different levels to understand their differentiation and evolution.

Exogenous trehalose alleviates the inhibitory effects of salt and drought stresses in okra plants - Fei Wang; Zihang Jiang; Haiyang Wang; Fan Liang; Yusheng Wang; Jinrui Zhang; Zeliang Liu; Lei Luo; Xinhong Chen; Feibing Wang (Horticulture, Environment, and Biotechnology, 2025)

Impact of flow velocity on growth performance, muscle texture, and nutritional composition in seabass (Lateolabrax maculatus) - Fan Fei; Yingying Fang; Zhiwen Zhu; Xinyu Liu; Ao Li; Jiawen Zhang; Xiaoqiang Gao; Wenyang Li; Hongjun Yang; Wensheng Li; Chuanxin Zhang; Baoliang Liu (Aquaculture International, 2025)

Evaluation on the antibacterial activity of glycyrrhizin against Pseudomonas plecoglossicida in ayu fish (Plecoglossus altivelis) - Fan Tao; Jia-Feng Cao; Yan-Jun Liu; Ru-Yi Chen; Jin-Jin Shi; Chang-Yun Li; Jian-Fei Lu; Guan-Jun Yang; Jiong Chen (Aquaculture, 2025)

Removal and ecological impact of sulfamethoxazole and N-acetyl sulfamethoxazole in mesocosmic wetlands dominated by submerged plants: Plant tolerance, microbial response, and nitrogen transformation - Xiaoying Mu; Congli Chen; Qinya Fan; Weihang Zhang; Fei Liu; Jiaxun Guo; Weixiao Qi; Huijuan Liu (Science of The Total Environment, 2025)

Immobilization and coordination chemistry of Friedel’s salt (Ca/Al-LDHs) on heavy metals removal - Chengcheng Fan; Baomin Wang; Hu Feng; Hongyu Zhou; Yihan Zhang; Weigao Ding; Fei Liu (Process Safety and Environmental Protection, 2025)

On the generation of light hydrocarbons from the closed pores of Jurassic strata, Sichuan Basin - Fei Liu; Yuanjia Han; Hanyong Bao; Ming Fan; Zhiguo Shu; Tian Dong; Zhiliang He (Marine and Petroleum Geology, 2025)

Stratified charge assisted jet ignition mode (SCAJI) for low-speed two-stroke Otto cycle ammonia marine engine - Zhuohang Li; Yezeng Fan; Jinze Li; Kaijian Wu; Zhenyingnan Zhang; Fei Ren; Zhan Gao; Ang Li; Lei Zhu; Zhen Huang (Fuel, 2025)

Exposure to multiple metals and leukocyte telomere length in children and adolescents: The mediating effect of thyroid hormones - Qing Liu; Gaojie Fan; Jianing Bi; Qing Fang; Fei Luo; Xiaofeng Huang; Heng Li; Binghai Liu; Lianyan Yan; Wenwen Guo; Liqin Hu; Surong Mei; et al. (Environmental Research, 2025)

Low-resource dynamic loading identification of nonlinear system using pretraining - Rui Zhu; Weixuan Yuan; Qingguo Fei; Qiang Chen; Gang Fan; Stefano Marchesiello; Dario Anastasio (Engineering Structures, 2025)

Crack opening calculation in phase-field modeling of fluid-filled fracture: A robust and efficient strain-based method - Fan Fei; Jinhyun Choo (Computers and Geotechnics, 2025)

Controllable development of a novel MXene-based reactive electrochemical ceramic membrane for efficient treatment of reverse osmosis concentrate - Chen Li; Xiaomeng Shang; Zhenbei Wang; Yatao Liu; Fan Li; Zonglin Jiang; Ruijun Ren; Fei Qi; Amir Ikhlaq; Oksana Ismailova; Zukhra Kadirova (Chemical Engineering Journal, 2025)

A droplet memristor with ionic liquid-electrolyte meniscus - Wei Liu; Jianyu Shang; Fei Zheng; Qinyang Fan; Xiaoxuan Yuan; Yunfei Chen; Jingjie Sha (Chemical Engineering Journal, 2025)

A novel dual-emission fluorescence sensor with different responsive modes for non-invasive and simultaneous quantitative detection of carbaryl and imidacloprid - Yi-Fan Xia; Hou-Qun Yuan; Zhi-Qiang Cai; Le Fang; Zhen-Chong Dou; Qian-Wen Yang; Yi-Xuan Hu; Ran Wang; Yu-Fei Zhong; Guang-Ming Bao (Chemical Engineering Journal, 2025)

Fluorine bismaleimide resin with outstanding piezoelectric characteristics for Structure-Function integrated composites - Bilin Zhang; Fei Liu; Shuting Chen; Liangkang Huang; Yuanyuan Zhong; Wei Fan; Jianwei Li (Chemical Engineering Journal, 2025)

Cross-sectional and Longitudinal Associations Between Metal Mixtures and Serum C3, C4: Result from the Manganese‑exposed Workers Healthy Cohort - Sencai Lin; Junxiu He; Yinghua Zhou; Yu Bao; Xiuming Feng; Hong Cheng; Haiqing Cai; Sihan Hu; Lin Wang; Yuan Zheng; Mengdi Zhang; Qinghua Fan; et al. (Biological Trace Element Research, 2025)

Surface-Enhanced Raman Scattering (SERS)-based biosensors for advanced extracellular vesicle detection: A review - Rui Fan; Siting Chen; Fei Lan; Wenbin Li; Yitong Zhu; Lifeng Zhang; Ye Zhang; Ling Li (Analytica Chimica Acta, 2025)

SOTHE: SOlar-terrestrial habitability explorer - Jiajia Liu; Bingkun Yu; Fuchuan Pang; Siteng Fan; Lixiang Gu; Lingping He; Yajuan Lei; Bo Li; Rui Li; Yiren Li; Dongdong Liu; Kai Liu; et al. (Advances in Space Research, 2025)

Analysis of correlation between daily rhythm of digestion and metabolism of grouper (Epinephelus lanceolatus♂ × Epinephelus fuscoguttatus♀) and water quality parameters in recycling aquaculture system - Wenyang Li; Hongxu Li; Fan Fei; Xiaoqiang Gao; Shuquan Cao; Wensheng Li; Bo Jin; Baoliang Liu (Aquaculture International, 2025)

Differences in glycogen and lipid accumulation and mobilization during ovarian maturation in female Litopenaeus vannamei - Yanan Yin; Haitao Fan; Xin Zhang; Zhangyi Zheng; Jiajie Xu; Tinghong Ming; Fei Kong; Lefei Jiao (Aquaculture International, 2025)

Effects of Different Light Spectra on Oxidative Stress and Nutritional Quality of the Fish Plectropomus leopardus - Wensheng Li; Zheng Zhang; Baoliang Liu; Yingying Fang; Shuquan Cao; Wenyang Li; Yan Sun; Chengbin He; Chuanxin Zhang; Fan Fei (Fishes, 2024)
This study investigated the impacts of light spectra on oxidative stress and nutrient quality of the fish Plectropomus leopardus in indoor recirculating aquaculture systems. The fish (100 g ± 0.45 g [wet weight]) were cultures in five different light spectra (full-spectrum (400–800 nm), blue (450 nm), green (530 nm), red (630 nm), and dark) for 60 days. After experimentation, blood and muscle tissue were collected and analyzed for biochemical variables and nutritional quality. We demonstrated that the total cholesterol, triglycerides activities of P. leopardus in the dark groups were substantially elevated, relative to other groups (p

Effect of Photoperiod on Nutritional Quality of Muscle and Lipid Metabolism of Litopenaeus vannamei - Yingying Fang; Fan Fei; Fulu Guo; Chengliang Zhu; Xiaoqiang Gao; Wenyang Li; Hongjun Yang; Yan Sun; Chuanxin Zhang; Baoliang Liu (Fishes, 2024)
Photoperiod serves as a significant environmental signal for organisms and plays a critical role in regulating their metabolic processes. This research aimed to investigate the lipid metabolism and nutritional quality of adults Litopenaeus vannamei (wet weight: 11.27 ± 0.73 g, body length: 12.45 ± 0.42 cm) under five photoperiods (0L:24D, 8L:16D, 12L:12D, 16L:8D, and 24L:0D) for 40 days in recirculating water systems (RASs). The 24L:0D group increased lipid metabolism, as indicated by increased lipid metabolism enzyme levels and related gene expression linked to lipogenesis. Additionally, shrimp in the 24L:0D exhibited the highest value of crude fat. The 0L:24D showed a significantly reduced content of crude fat compared with the 8L:16D and 12L:12D. In 24L:0D, the content of total essential amino acids (TEAAs), total hydrolyzed essential amino acids (THEAAs), and total non-essential amino acids (TNEAAs) increased significantly. Similarly, the content of polyunsaturated fatty acids (PUFAs) in 24L:0D was also higher than in other groups. Conversely, 0L:24D resulted in lower metabolic activity and a reduction in PUFA content. In conclusion, prolonging light could benefit shrimp cultivation. This study thoroughly examined the effects of varying photoperiods on muscle quality and lipid metabolism in L. vannamei, providing essential insights for the improvement of indoor aquaculture environments. Provision of light for 24 h improves production but has some adverse effects on animal welfare, so a 16 h light cycle is recommended.

Effects of spectral on growth, physiology, and growth axis gene expression in Plectropomus leopardus - Fan Fei; Shuquan Cao; Wensheng Li; Zhiwen Zhu; Wenyang Li; Xiaoqiang Gao; Xianhong Zhang; Yan Sun; Chuanxin Zhang; Baoliang Liu (Aquaculture, 2024)

Establishment and validation of a real-time fluorescent PCR freeze-dried type assay for 11 sheep and goats pathogens - Liting Ke; Guangzheng Hou; Pengcheng Cao; Yanlei Ding; Changxu Zhao; Fei Wang; Yingqiu Liu; Yunpeng Fan; Qiqi Liu (The Veterinary Journal, 2024)

Sediment grain size regulates the biogeochemical processes of nitrate in the riparian zone by influencing nutrient concentrations and microbial abundance - Fei Ye; Lei Duan; Zhoufeng Wang; Yike Wang; Xiaomei Kou; Fan Wan; Yi Wang (Science of The Total Environment, 2024)

Forms of rare earth loss and the function mechanism of acetic acid in the aluminum removal process of rare earth leaching liquor - Chen Xin; Chen Jin-fa; Xiao Xin-lei; Fan Lin; Xiao Yan-fei; Huang Li (Minerals Engineering, 2024)

Hidden pathogen risk in mature compost: Low optimal growth temperature confers pathogen survival and activity during manure composting - Nenglong Peng; Junmao Zhang; Ruiwen Hu; Songfeng Liu; Fei Liu; Yijun Fan; Huijing Yang; Jing Huang; Jijuan Ding; Ruihan Chen; Li Li; Zhili He; et al. (Journal of Hazardous Materials, 2024)

Efficient biodegradation of poly(butylene adipate-co-terephthalate) in mild temperature by cutinases derived from a marine fungus - Fan Fei; Zhenjie Su; Rui Liu; Rongrong Gao; Chaomin Sun (Journal of Hazardous Materials, 2024)

Distribution of oil mist particles and air quality improvement in the working area of the cutting workshop - Yuming Zhang; Yang Yang; Qingfeng Cao; Yi Wang; Jia-Ning Fan; Hu Chen; Xin Wang; Fei Wang; Yu Zhou; Mengfan Quan (Journal of Hazardous Materials, 2024)

High stability and reactivity of porous calcium tartrate supported nano zero-valent iron in aerobic environment and alkaline wastewater - Fei Li; Xia Zhang; Feng Liang; Chen Wang; Pingning Jin; Jing Fan (Journal of Environmental Chemical Engineering, 2024)

Onboard amino acid salt-based CO2 integrated absorption and mineralization: Kinetics, mechanism, economics and life cycle - Xiaojia Tang; Mingpeng Fan; Yue Tian; Chaoyu Zhu; Xinyu Shi; Fei Gao; Yangyuan Ji; Yufei Wang; Yimin Zhu (Journal of Environmental Chemical Engineering, 2024)

Reworking of a Caledonian (Early Paleozoic) granodiorite porphyry in a collisional zone in South China and its contribution for tungsten mineralization - Wen-Jing Mao; Yi-Qu Xiong; Yong-Jun Shao; Matthew J. Brzozowski; Qiang He; Hong-Fei Di; Zhi-Wei Fan; Yu-Jie Mao; Wen-Jie Fang (Journal of Asian Earth Sciences, 2024)

Geochemical behavior of riverine magnesium isotopes in the Yarlung Tsangpo River Basin, southern Tibetan Plateau - Ya-Ni Yan; Jun-Wen Zhang; Jie Wu; Bai-Ling Fan; Dong Zhang; Long-Fei Gou; Qing-You Liu; Zhi-Qi Zhao (Global and Planetary Change, 2024)

Investigating how oxygen levels and particle size impact the thermodynamics of low temperature coal oxidation: A case study using weakly caking coal - Li-Feng Ren; Fan Tao; Teng-Fei Weng; Qing-Wei Li; Xin Yu; Xiao-Wei Zhai; Teng Ma (Fuel, 2024)

Lignanamides: A comprehensive review of chemical constituents, biological activities, extraction methods and synthetic pathway - Jing Sun; Li-Tao Tong; Peng-Fei Tu; Lin-Lin Chen; Xin Xu; Ya Song; Xin-Xin Yang; Zi-Bin Guo; Xiang Zou; Chen-Xin Sun; Yan Mi; Bei Fan; et al. (Food Chemistry, 2024)

Activating copper by creating low-coordinated copper sites for antibiotic detoxification through Electrocatalytic hydrodechlorination reaction - Xiangyi Tang; Fei Shen; Wei Fan; Jianhui Liu; Lingpiao Chen; Yinan Liu; Liang Ao; Xiaoshu Lv; Wenyang Fu; Yan Zou; Ling Chen; Yan Jiang; et al. (Chemical Engineering Journal, 2024)

Efficient removal of radioactive Th(IV) and U(VI) from rare earth leaching solution using HDES - Lei-Tao Sha; Qiang Wu; Yi-Fan Zhang; Wei-Jia Wang; Fei Wu; Qing-Gang Huang; Ze-Yi Yan (Chemical Engineering Journal, 2024)

Intense intrusion of low-oxygen waters into mid-Cambrian surface ocean carbonate factories - Yang-fan Li; Fei Li; Gregory E. Webb; Jitao Chen (Chemical Geology, 2024)

Statins may Decrease Aneurysm wall Enhancement of Unruptured Fusiform Intracranial Aneurysms: A high-resolution 3T MRI Study - Jiaxiang Xia; Fei Peng; Xuge Chen; Fan Yang; Xin Feng; Hao Niu; Boya Xu; Xinmin Liu; Jiahuan Guo; Yao Zhong; Binbin Sui; Yi Ju; et al. (Translational Stroke Research, 2024)

Nanoparticle attachment promotes nugget effect of Au-rich metallic melts in hydrothermal ore deposits - Gao-Hua Fan; Jian-Wei Li; Ya-Fei Wu; Si-Yu Hu; Xiao-Dong Deng; Hao-Yang Zhou; Zhan-Ke Li; Yan Liu (Contributions to Mineralogy and Petrology, 2024)

From thermal demand characterization to accurate evaluation: Exploring seasonal differences in outdoor thermal comfort of the elderly in China's communities - Yan Wang; Liyuan Yin; Qiwei Dong; Fan Fei; Wanxiang Yao; Jiang Sun; Zhongtian Jiang (Urban Climate, 2024)

Bioaccessibility and bioavailability assessment of cadmium in rice: In vitro simulators with/without gut microbiota and validation through in vivo mouse and human data - Fei-Fei Xu; Ying-Si Chen; Xiu-Qin Lin; Ai-Hua Zhong; Min Zhao; Yue-Qi Li; Zi-Yin Li; Yue-Fei Lai; Jia Song; Jia-Liang Pan; Zhan-Fan Cai; Xu-Xia Liang; et al. (Science of The Total Environment, 2024)

Curcumin is an efficacious therapeutic agent against Chilodonella uncinata via interaction with tubulin alpha chain as protein target - Wenjia Han; Kechen Yang; Xiaoping Tan; Longkun Gao; Shenye Qu; Gengrong Zhang; Wenqi Fan; Mingzhu Liu; Erlong Wang; Pengfei Li; Fei Ling; Gaoxue Wang; et al. (Fish & Shellfish Immunology, 2024)

A novelty strategy for AMD prevention by biogas slurry: Acetate acid inhibition effect on chalcopyrite biooxidation and leachate - Xin Li; Shi-jie Yuan; Fei-fan Ren; Bin Dong; Zu-xin Xu (Environmental Research, 2024)

Enterobacter sp. HIT-SHJ4 isolated from wetland with carbon, nitrogen and sulfur co-metabolism and its implication for bioremediation - Kaili Fan; Fei Wang; Xijun Xu; Jia Shi; Wei Wang; Defeng Xing; Nanqi Ren; Duu-Jong Lee; Chuan Chen (Environmental Research, 2024)

Mechanistic insights into the roles of copper in enhanced peroxymonosulfate activation for tetracycline degradation by copper ferrite composite catalyst - Jinsong He; Licui Feng; Taoran Shi; Fan Ni; Li Zhao; Yongjia Lei; Yan Liu; Dexin Fang; Zongsu Wei; Fei Shen (Chemical Engineering Journal, 2024)

Link Brain-Wide Projectome to Neuronal Dynamics in the Mouse Brain - Xiang Li; Yun Du; Jiang-Feng Huang; Wen-Wei Li; Wei Song; Ruo-Nan Fan; Hua Zhou; Tao Jiang; Chang-Geng Lu; Zhuang Guan; Xiao-Fei Wang; Hui Gong; et al. (Neuroscience Bulletin, 2024)
Knowledge about the neuronal dynamics and the projectome are both essential for understanding how the neuronal network functions in concert. However, it remains challenging to obtain the neural activity and the brain-wide projectome for the same neurons, especially for neurons in subcortical brain regions. Here, by combining in vivo microscopy and high-definition fluorescence micro-optical sectioning tomography, we have developed strategies for mapping the brain-wide projectome of functionally relevant neurons in the somatosensory cortex, the dorsal hippocampus, and the substantia nigra pars compacta. More importantly, we also developed a strategy to achieve acquiring the neural dynamic and brain-wide projectome of the molecularly defined neuronal subtype. The strategies developed in this study solved the essential problem of linking brain-wide projectome to neuronal dynamics for neurons in subcortical structures and provided valuable approaches for understanding how the brain is functionally organized via intricate connectivity patterns.

Bisifusarium delphinoides: a causal agent of stalk rot in Pennisetum × sinese Roxb - Ke Yue; Linxia Fan; Fengcheng Zhang; Fei Wang; Wei Guo (Australasian Plant Pathology, 2024)

The HSP70 and IL ‐1β of Nile tilapia as molecular adjuvants can enhance the immune protection of DNA vaccine against Streptococcus agalactiae infection - Fei‐Fan Xu; Zhu‐Yang Deng; Jun‐Jie Sheng; Bin Zhu (Journal of Fish Diseases, 2024)
Globally, streptococcal disease caused by Streptococcus agalactiae is known for its high mortality rate, which severely limits the development of the tilapia breeding industry. As a third‐generation vaccine, DNA vaccines have shown great application prospects in the prevention and control of aquatic diseases, but their low immunogenicity limits their development. The combination of DNA vaccines and molecular adjuvants proved to be an effective method for inducing protective immunity. This study constructed recombinant plasmids encoding tilapia HSP70 and IL‐1β genes (pcHSP70 and pcIL‐1β) to verify their effectiveness as molecular adjuvants for S. agalactiae DNA vaccine (pcSIP) in the immunized tilapia model. The results revealed that serum‐specific IgM production, enzyme activities, and immune‐related gene expression in tilapia immunized with pcSIP plus pcHSP70 or pcIL‐1β were significantly higher than those in tilapia immunized with pcSIP alone. It is worth noting that combination with molecular adjuvants improved the immune protection of DNA vaccines, with a relative percentage survival (RPS) of 51.72% (pcSIP plus pcHSP70) and 44.83% (pcSIP plus pcIL‐1β), respectively, compared with that of pcSIP alone (24.14%). Thus, our study indicated that HSP70 and IL‐1β in tilapia are promising molecular adjuvants of the DNA vaccine in controlling S. agalactiae infection.

The Environmental Niche of the Light Purse Seine Fleet in the Northwest Pacific Ocean Based on Automatic Identification System Data - Shenglong Yang; Lijun Wan; Linlin Yu; Jiashu Shi; Weifeng Zhou; Shengmao Zhang; Fei Wang; Zuli Wu; Yang Dai; Keji Jiang; Wei Fan (Journal of Marine Science and Engineering, 2024)
Ecosystem-based fisheries management requires high-precision fisheries information to provide relevant data for natural resource management, assessment, and marine spatial planning. This study utilizes Automatic Identification System (AIS) data from light purse seine vessels from the Chinese mainland that were collected from May to November between 2020 and 2022, along with the corresponding environmental data. By applying boosted regression trees (BRTs) and generalized additive models (GAMs), this study establishes nonlinear relationships between fishing intensity and predictor variables and explores the ecological and environmental drivers behind the spatial distribution of light purse seine vessels from the Chinese mainland in the Northwest Pacific. This research identifies the key influencing factors and reveals significant seasonal preferences for different marine environments in various months, with chlorophyll-a being the primary influencing factor. The predicted fishing effort closely resembles observed data, providing valuable information to support fisheries resource management and planning.

A novel approach for quantifying the influence intensity of urban water and greenery resources on microclimate for efficient utilization - Fan Fei; Yuling Xiao; Luyao Wang; Yan Wang; Hiroatsu Fukuda; Wanxiang Yao; Haiming Yu; Qiwei Dong (Sustainable Cities and Society, 2024)

System simulation and multi-objective optimization methodology for sustainable municipal solid waste classification management: A case study in China - Jiayue Zhang; Zongguo Wen; Yupeng Hu; Fan Fei; Yihan Wang; Yiling Xie (Sustainable Production and Consumption, 2024)

Oil in food waste to methane by anaerobic digestion: Co-effects of mixing intensity and long chain fatty acid loading - Li-Jie Wu; Zi-Wen Hao; Fei Ye; Fan Yang; Yong-Kang Lyu (Process Safety and Environmental Protection, 2024)

Removal of sulfadiazine from water by a three-dimensional electrochemical system coupled with persulfate: Enhancement effect of ball-milled CuO-Fe3O4@biochar - Taiqing Wei; Jingwen Li; Chao Fei; Zhiping Fan; Bo Wang (Process Safety and Environmental Protection, 2024)

Global path planning for Unmanned Surface Vehicles in complex maritime environments considering environmental interference - Dongdong Mu; Tanghui Li; Xinjie Han; Yunsheng Fan; Fei Wang (Ocean Engineering, 2024)

Plasma-induced surface interactions of Pd/SrTiO3 catalyst for improved performance of photocatalytic degradation of toluene - Dongliang Gao; Bingwei Wang; Jingyue Bi; Fan Xue; Mifen Cui; Zhaoyang Fei; Lei Li; Xu Qiao (Journal of Environmental Chemical Engineering, 2024)

Recent progress in strategies to enhance the photocatalytic oxidation performance of cyclohexane - Haohao Huo; Bingrong Guo; Guoxin Ma; Yuan Xiang; Huidong Lv; Siwei Li; Zhe Liu; Fei Huang; Yao Xu; Fan Zhang (Journal of Environmental Chemical Engineering, 2024)

Simultaneous extraction of five heavy metal ions from root vegetables via dual-frequency ultrasound-assisted enzymatic digestion - Min Yuan; Xinyan Huan; Xiaojun Yang; Menghan Fan; Jiaqi Yin; YingQing Ma; Bo Deng; Hui Cao; Yiyi Han; Fei Xu (Food Chemistry, 2024)

DPA-Zn enables targeting and bypassing endosomal trapping delivery of a genome-editing system into cancer cells via phosphatidylserine-mediated endocytic pathway - Qi Shao; Cai-Liang Shen; Wei You; Xuan Nie; Wei-Qiang Huang; Fan Gao; Xiao-Hong Zhou; Hai-Li Wang; Long-Hai Wang; Guang Chen; Chang-Hui Wang; Chun-Yan Hong; et al. (Chemical Engineering Journal, 2024)

A One-Nano MOF-Two-Functions Strategy Toward Self-healing, Anti-inflammatory, and Antibacterial Hydrogels for Infected Wound Repair - Ya-Ling Fan; Hong-Jie Liu; Zi-Li Wang; Zi-Lin Wang; Li-Li Zhu; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2024)

Outstanding comprehensive energy storage performances in multiscale synergistic regulation-engineered (Bi0.5Na0.5)TiO3-based multilayer ceramics - Hang Xie; Zhenhao Fan; Linjing Liu; Shuai Yang; Qiangwei Kou; Rui Lv; Jian Dai; Hongliang Du; Yunfei Chang; Fei Li (Chemical Engineering Journal, 2024)

Explainable machine learning-driven predictive performance and process parameter optimization for caproic acid production - Hongzhi Ma; Yichan Liu; Jihua Zhao; Fan Fei; Ming Gao; Qunhui Wang (Bioresource Technology, 2024)

Gas isotope geochemistry of Tangquan hot spring system in Nanjing (China) - Yifan Bao; Zhonghe Pang; Yiman Li; Jiao Tian; Ji Luo; Yifan Fan; Fengtian Yang; Tingqing Qian; Fei Chen; Caixia Sun; Zongying Zhou (Applied Geochemistry, 2024)

Magnetic conjugated microporous polymer for rapid extraction and sensitive analysis of environmental endocrine disruptors in environmental waters and dairy products - Hai-Long Jiang; Fu-Shuai Kang; Ye-Fei Fan; Xia Wang; Yun-Liang Lin; Lu Liu; Wei Liu; Yan-Fang Zhao; Ru-Song Zhao (Analytica Chimica Acta, 2024)

Nervonic acid and its sphingolipids: Biological functions and potential food applications - Nghi Van Phung; Fei Rong; Wan Yue Xia; Yong Fan; Xian Yu Li; Shi An Wang; Fu Li Li (Critical Reviews in Food Science and Nutrition, 2024)

Dysregulated Purinergic Signalling in Fragile X Syndrome Cortical Astrocytes - Kathryn E. Reynolds; Matthew Napier; Fan Fei; Kirk Green; Angela L. Scott (NeuroMolecular Medicine, 2024)

The vertical partitioning between denitrification and dissimilatory nitrate reduction to ammonium of coastal mangrove sediment microbiomes - Yijun Fan; Zhengyuan Zhou; Fei Liu; Lu Qian; Xiaoli Yu; Fangjuan Huang; Ruiwen Hu; Hualong Su; Hang Gu; Qingyun Yan; Zhili He; Cheng Wang (Water Research, 2024)

Remotely sensed estimates of long-term biochemical oxygen demand over Hong Kong marine waters using machine learning enhanced by imbalanced label optimisation - Yadong Zhou; Boayin He; Xiaoyu Cao; Yu Xiao; Qi Feng; Fan Yang; Fei Xiao; Xueer Geng; Yun Du (Science of The Total Environment, 2024)

Association of exposure to multiple metals with hemoglobin levels in Chinese children and adolescents - Fei Luo; Jianing Bi; Qing Liu; Gaojie Fan; Qing Fang; Xiya Qin; Xukuan Zhang; Xiaofeng Huang; Heng Li; Wenwen Guo; Binghai Liu; Lianyan Yan; et al. (Science of The Total Environment, 2024)

The chelation mechanism of neonicotinoid insecticides influencing cadmium transport and accumulation in rice at different growth stage - Qiongfang Ouyang; Na Liu; Zhaoxia Fan; Feng Li; Fei Ge (Science of The Total Environment, 2024)

Mid-infrared superconducting nanowire single photon detector enhanced by overcoupled metasurfaces - Yue Dai; Fengjie Zhu; Kebin Fan; Qi Chen; Labao Zhang; Fei Zhou; Yue Fei; Hang Yuan; Hongkai Shi; Hao Wang; Xiaoqing Jia; Qingyuan Zhao; et al. (Science Bulletin, 2024)

Molecular phylogeny of Hesperiidae (Lepidoptera) with an emphasis on Asian and African genera - Zhenfu Huang; Hideyuki Chiba; Yanqing Hu; Xiaohua Deng; Wen Fei; Szabolcs Sáfián; Liwei Wu; Min Wang; Xiaoling Fan (Molecular Phylogenetics and Evolution, 2024)

Synergistic degradation of 2,4-dichlorophenoxyacetic acid in water by interfacial pre-reduction enhanced peroxymonosulfate activation derived from novel zero-valent iron/biochar - Yatao Liu; Tianyi Wang; Qiaofeng Hong; Chen Li; Zhenbei Wang; Fan Li; Mingyuan Li; Mengfei He; Fei Qi; Ewa Maria Siedlecka; Jolanta Kumirska (Journal of Hazardous Materials, 2024)

Self-assembled Chitosan/Polyvinyl alcohol hydrogel film incorporated with TiO2 with excellent stability, mechanical and antibacterial properties for the preservation of chilled pork - Debao Wang; Juan Chen; Xiangyuan Wen; Simin Fan; Chaoqiao Zhu; Xin Li; Fei Fang; Wei Yang; Wenchun Fan; Dequan Zhang; Chengli Hou (Food Packaging and Shelf Life, 2024)

New approach for raw biogas: Production of single cell protein by sulfide-tolerant methane-oxidizing bacteria consortia - Hai-Ming Huang; Zhi-Xin Xue; Yu-Feng Jiang; Rui Li; Rong-Bo Guo; Xiao-Lei Fan; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Electrochemically-induced metal–oxygen bond Cu(II)- SO5− on novel CuBi2O4 anode for efficient peroxymonosulfate activation - Yatao Liu; Yongzhen Li; Chen Li; Asuna; Zhenbei Wang; Fan Li; Fei Qi; Ronghua Xu; Ewa Maria Siedlecka; Jolanta Kumirska (Chemical Engineering Journal, 2024)

The response of Martian photoelectron boundary to the 2018 global dust storm - Yuqi Wang; Jun Cui; Yong Wei; Zhaopeng Wu; Kai Fan; Zhaojin Rong; Fei He; Yutian Cao; Jiawei Gao (Science China Earth Sciences, 2024)

Synthesis, structure-activity relationship and evaluation of antifungal activity of tryptanthrin derivatives against drug-resistant Candida albicans - Yandan Wu; Luyi Jiang; Ruina Liu; Lijiao Yang; Fei Zou; Tianyu Zhang; Zefei Fan; Tianbao Zhang; Huan Yang; Shuyun Yin; Ruirui Wang; Ganpeng Li; et al. (Medicinal Chemistry Research, 2024)

Autonomous Underwater Vehicle Path Planning Based on Improved Salp Swarm Algorithm - Xuan Guo; Dongming Zhao; Tingting Fan; Fei Long; Caihua Fang; Yang Long (Journal of Marine Science and Engineering, 2024)
Aiming at the problem of path planning for autonomous underwater vehicle (AUV) to cope with the influence of obstacles and eddies in complex marine environments, a path planning method based on an improved salp swarm algorithm (ISSA) is proposed. Firstly, the motion model of the AUV and eddy current model are constructed, including the relationship between position, velocity, attitude, and control inputs. Secondly, the improved SSA is proposed, which introduces the Levy flight strategy to enhance the algorithm’s optimization seeking ability and adds a nonlinear convergence factor to enhance the convergence ability of the algorithm. The stability and robustness of the improved algorithm are verified by test functions. Finally, the ISSA is applied to AUV path planning, which optimizes the AUV travel distance, improves the search efficiency and accuracy, and avoids the local optimum of the algorithm. The ISSA enhances the adaptive ability and robustness of the algorithm by introducing a dynamic adjustment strategy and feedback mechanism. Experimental verification is carried out using a simulated marine environment. The results show that the ISSA is better than the traditional algorithm in terms of path length as well as algorithm stability, and can effectively improve the navigation performance of AUV.

Genetic and Pathogenic Characterization of an Iridovirus from the Cultured Largemouth Bass Micropterus salmoides - Yi-Fan Zhang; Ying Li; Peng-Tian Li; Jing Jiang; Wei-Hang Zeng; Kun Ye; Yi-Lei Wang; Peng-Fei Zou (Fishes, 2024)
The largemouth bass is a freshwater aquacultured fish species of great economic importance in China. With the rapid development of aquaculture industry and the increase in the aquaculture density of the fish, various infectious pathogens, including parasites, bacteria, and viruses, have been widely spread, which have caused huge losses to the aquaculture industry. Among them, largemouth bass iridovirus (LMBV) is one of the most harmful pathogens. In the present study, a virus strain named LMBV-GDSD was isolated from cultured largemouth bass and was successfully proliferated in FHM and EPC cells, with numerous viral particles observed in the infected cells under transmission electron microscopy analysis. The annotated complete genome of LMBV-GDSD was 99,285 bp and contained 102 ORFs. Based on genomic sequence alignment and phylogenetic analysis, the identified LMBV-GDSD belonged to the genus Ranavirus of Iridoviridae and was pathogenic to largemouth bass under regression infection experiments. In addition, the infection of LMBV-GDSD in largemouth bass could significantly up-regulate the expression of antiviral immune-related genes such as IRF3, IRF7, and Mx. It is thus providing valuable genetic data for a deeper understanding of the pathogenic mechanism of iridovirus in largemouth bass.

Temperature dependence of the rain-gas and snow-gas partition coefficients for nearly a thousand chemicals - Pu-Fei Yang; Wan-Li Ma; Hang Xiao; Kaj M. Hansen; Liang Wang; Jing-Jing Sun; Li-Yan Liu; Zi-Feng Zhang; Hong-Liang Jia; Yi-Fan Li (Chemosphere, 2024)

In situ real-time pathway to study the polyethylene long-term degradation process by a marine fungus through confocal Raman quantitative imaging - Wanying He; Rui Liu; Fan Fei; Shichuan Xi; Zengfeng Du; Zhendong Luan; Chaomin Sun; Xin Zhang (Science of The Total Environment, 2024)

Ball-milled biochar-modified zero-valent aluminum activates peroxodisulfate for phenol degradation: Enhancement of catalysis by membrane-breaking effect - Yang Meng; Chao Fei; Jingwen Li; Zhiping Fan; Bo Wang (Science of The Total Environment, 2024)

Fungicide resistance in Colletotrichum fructicola and Colletotrichum siamense causing peach anthracnose in China - Mohammad Mazharul Karim; Hafiz Muhammad Usman; Qin Tan; Jia-Jie Hu; Fei Fan; Rafakat Hussain; Chao-Xi Luo (Pesticide Biochemistry and Physiology, 2024)

The seasonal evolution of the Yellow Sea Cold Water Mass Circulation: Roles of fronts, thermoclines, and tidal rectification - Yibo Hu; Fei Yu; Guangcheng Si; Fan Sun; Xingchuan Liu; Xinyuan Diao; Zifei Chen; Feng Nan; Qiang Ren (Ocean Modelling, 2024)

Confirmation of Skywalker Hoolock Gibbon (Hoolock tianxing) in Myanmar Extends Known Geographic Range of an Endangered Primate - Pyae Phyo Aung; Ngwe Lwin; Tin Htun Aung; Thura Soe Min Htike; Carolyn Thompson; Christian Roos; Sa Myo Zaw; L. Zawng Lum; Win Naing Oo; Zung Sau; Samuel T. Turvey; Wai Zinn Thein; et al. (International Journal of Primatology, 2024)
Characterizing genetically distinct populations of primates is important for protecting biodiversity and effectively allocating conservation resources. Skywalker gibbons ( Hoolock tianxing ) were first described in 2017, with the only confirmed population consisting of 150 individuals in Mt. Gaoligong, Yunnan Province, China. Based on river geography, the distribution of the skywalker gibbon has been hypothesized to extend into Myanmar between the N’Mai Kha and Ayeyarwaddy Rivers to the west, and the Salween River (named the Thanlwin River in Myanmar and Nujiang River in China) to the east. We conducted acoustic point-count sampling surveys, collected noninvasive samples for molecular mitochondrial cytochrome b gene identification, and took photographs for morphological identification at six sites in Kachin State and three sites in Shan State to determine the presence of skywalker gibbons in predicted suitable forest areas in Myanmar. We also conducted 50 semistructured interviews with members of communities surrounding gibbon range forests to understand potential threats. In Kachin State, we audio-recorded 23 gibbon groups with group densities ranging between 0.57 and 3.6 group/km 2 . In Shan State, we audio-recorded 21 gibbon groups with group densities ranging between 0.134 and 1.0 group/km 2 . Based on genetic data obtained from skin and saliva samples, the gibbons were identified as skywalker gibbons (99.54–100% identity). Although these findings increase the species’ known population size and confirmed distribution, skywalker gibbons in Myanmar are threatened by local habitat loss, degradation, and fragmentation. Most of the skywalker gibbon population in Myanmar exists outside protected areas. Therefore, the IUCN Red List status of the skywalker gibbon should remain as Endangered.

Analysis of global vegetation resilience under different future climate scenarios - Zheng Chen; Peiyi Fan; Xintong Hou; Fei Ji; Li Li; Zhonghua Qian; Guolin Feng; Guiquan Sun (Climate Dynamics, 2024)

Self-assembly of cascade nanoenzyme glucose oxidase encapsulated in copper benzenedicarboxylate for wearable sweat-glucose colorimetric sensors with smartphone readout - Binghua Fan; Yongjun Wu; Hongchao Guo; Fei Yu; Li-e Liu; Songcheng Yu; Jia Wang; Yilin Wang (Analytica Chimica Acta, 2024)

Optimization and scale-up of the spray drying process for Euglena gracilis - Kaikai Zhang; Minxi Wan; Wenmin Bai; Zhengxu Bao; Xingbo Duan; Weiliang Wang; Fei Fan; Yuanguang Li (Algal Research, 2024)

Mechanisms of cuproptosis and its relevance to distinct diseases - Qiao-mei Lou; Fei-fan Lai; Jing-wei Li; Kun-jun Mao; Hai-tong Wan; Yu He (Apoptosis, 2024)

Projecting Wintertime Newly Formed Arctic Sea Ice through Weighting CMIP6 Model Performance and Independence - Jiazhen Zhao; Shengping He; Ke Fan; Huijun Wang; Fei Li (Advances in Atmospheric Sciences, 2024)
Precipitous Arctic sea-ice decline and the corresponding increase in Arctic open-water areas in summer months give more space for sea-ice growth in the subsequent cold seasons. Compared to the decline of the entire Arctic multiyear sea ice, changes in newly formed sea ice indicate more thermodynamic and dynamic information on Arctic atmosphere–ocean–ice interaction and northern mid–high latitude atmospheric teleconnections. Here, we use a large multimodel ensemble from phase 6 of the Coupled Model Intercomparison Project (CMIP6) to investigate future changes in wintertime newly formed Arctic sea ice. The commonly used model-democracy approach that gives equal weight to each model essentially assumes that all models are independent and equally plausible, which contradicts with the fact that there are large interdependencies in the ensemble and discrepancies in models’ performances in reproducing observations. Therefore, instead of using the arithmetic mean of well-performing models or all available models for projections like in previous studies, we employ a newly developed model weighting scheme that weights all models in the ensemble with consideration of their performance and independence to provide more reliable projections. Model democracy leads to evident bias and large intermodel spread in CMIP6 projections of newly formed Arctic sea ice. However, we show that both the bias and the intermodel spread can be effectively reduced by the weighting scheme. Projections from the weighted models indicate that wintertime newly formed Arctic sea ice is likely to increase dramatically until the middle of this century regardless of the emissions scenario. Thereafter, it may decrease (or remain stable) if the Arctic warming crosses a threshold (or is extensively constrained).

Stereoscopic urban morphology metrics enhance the nonlinear scale heterogeneity modeling of UHI with explainable AI - Yanting Shen; Weikang Kong; Fan Fei; Xilong Chen; Yiwen Xu; Chenyu Huang; Jiawei Yao (Urban Climate, 2024)

Viral communities locked in high elevation permafrost up to 100 m in depth on the Tibetan Plateau - Qian Wen; Xiufeng Yin; Abulimiti Moming; Guangyue Liu; Boyong Jiang; Jun Wang; Zhaojun Fan; Wasim Sajjad; Yingying Ge; Shichang Kang; Shu Shen; Fei Deng (Science of The Total Environment, 2024)

Revisiting the quantification of power plant CO2 emissions in the United States and China from satellite: A comparative study using three top-down approaches - Cheng He; Xiao Lu; Yuzhong Zhang; Zhu Liu; Fei Jiang; Youwen Sun; Meng Gao; Yiming Liu; Haipeng Lin; Jiani Yang; Xiaojuan Lin; Yurun Wang; et al. (Remote Sensing of Environment, 2024)

Hierarchical Nash equilibrium seeking for optimal fault-tolerant formation control of networked MSVs in aggregative games - Yi-Fan Li; Ming-Feng Ge; Qian Chen; Teng-Fei Ding; Zhi-Wei Liu (Ocean Engineering, 2024)

A new species of Populus and the extensive hybrid speciation arising from it on the Qinghai-Tibet Plateau - Yu-Jie Shi; Jia-Xuan Mi; Jin-Liang Huang; Fei-Fei Tian; Fang He; Yu Zhong; Han-Bo Yang; Fang Wang; Yu Xiao; Lin-Kai Yang; Fan Zhang; Liang-Hua Chen; et al. (Molecular Phylogenetics and Evolution, 2024)

Theoretical investigation on hydrogen storage into N-ethylcarbazole catalyzed by electron-rich Ni4/TiO2-Al2O3 - Wenwu Zhou; Xiaodi Zhu; Jie Kang; Fei Fan; Houxiang Sun; Zhiping Chen; Fengfei He (Fuel, 2024)

Mass transfer and kinetic measurement and modeling for CO2 absorption into aqueous EAE and water-lean EAE/NMP solvents - Fei Liu; Shenghui Liu; Ning Li; Wenyue Tang; Shien Sun; Haidong Fan; Zhifu Qi (Chemical Engineering Journal, 2024)

A flexible sanded cotton fabric coated with Au@polypyrrole for seawater desalination - Zenghui Sun; Fei Huang; Yongshuang Cai; Wanying Liang; Siyu Fan; Chao Tu; Yufeng Liu; Chao Yan (Chemical Engineering Journal, 2024)

Platelet-Rich Plasma/Chitosan/Chondroitin sulfate immunomodulatory hydrogel Co-Networks for diabetic wound Repair: Functions and molecular mechanisms - Zi-Lin Wang; Lin-Yue Li; Hong-Jie Liu; Ya-Ling Fan; Yu-Xue Shen; Fei Song; Li-Li Zhu (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Intermediate Principal Stress Effects on the 3D Cracking Behavior of Flawed Rocks Under True Triaxial Compression - Yuan Sun; Fan Fei; Louis Ngai Yuen Wong; Jinhyun Choo (Rock Mechanics and Rock Engineering, 2024)
Crack initiation, growth, and coalescence in flawed rocks have been extensively studied for 2D (planar, penetrating) flaws under uniaxial/biaxial compression. However, little is known as to the mechanisms and processes of cracking from 3D flaws under true triaxial compression, where the intermediate principal stress ( $$σ _2$$ σ 2 ) is distinguished from the major and minor principal stresses. In this work, we systematically investigate the effects of $$σ _2$$ σ 2 on the 3D cracking behavior of rock specimens with preexisting flaws, through the use of mechanistic simulations of mixed-mode fracture in rocks. We explore how two characteristics of $$σ _2$$ σ 2 , namely, (i) its orientation with respect to the flaw and (ii) its magnitude, affect two aspects of the cracking behavior, namely, (i) the cracking pattern and (ii) the peak stress. Results show that the orientation of $$σ _2$$ σ 2 exerts more control over the cracking pattern than the flaw inclination angle. The peak stress becomes highest when $$σ _1$$ σ 1 is parallel to the flaw, whereas it becomes lowest when $$σ _2$$ σ 2 is parallel to the flaw. Also, the effects of $$σ _2$$ σ 2 magnitude are more significant when $$σ _2$$ σ 2 becomes more oblique to the flaw plane. On the basis of our observations, we propose mechanisms underlying the cracking behavior of 3D flawed rocks under true triaxial compression. Highlights The effects of the intermediate principal stress ( $$σ _2$$ σ 2 ) on the 3D cracking behavior of flawed rocks under true triaxial compression are systematically investigated. The orientation of $$σ _2$$ σ 2 exerts more control over the cracking pattern than the flaw inclination angle. The effects of $$σ _2$$ σ 2 magnitude become more significant when $$σ _2$$ σ 2 are more oblique to the flaw plane. Mechanisms underlying the cracking behavior of 3D flawed rocks under true triaxial compression are proposed based on the observations made.

Unveiling toxicity profile for food risk components: A manually curated toxicological databank of food-relevant chemicals - Xing-Xing Shi; Fan Wang; Zhi-Zheng Wang; Guang-Yi Huang; Min Li; Jesus Simal-Gandara; Ge-Fei Hao; Guang-Fu Yang (Critical Reviews in Food Science and Nutrition, 2024)

Transcriptomic mechanism revealed IbGST4 and IbGST2 genes response to low-temperature stress in sweet potatoes - Wei-Sheng Zhao; Long-Fei Yan; Kang-Di Hu; Zhi-Lin Zhou; Si-Qi Wang; Le-Ying Yan; Fan Hu; Hua Zhang; Gai-Fang Yao (Postharvest Biology and Technology, 2024)

Evolutionary genomics of climatic adaptation and resilience to climate change in alfalfa - Fan Zhang; Ruicai Long; Zhiyao Ma; Hua Xiao; Xiaodong Xu; Zhongjie Liu; Chunxue Wei; Yiwen Wang; Yanling Peng; Xuanwen Yang; Xiaoya Shi; Shuo Cao; et al. (Molecular Plant, 2024)

Multistage dolomitization influenced by the Emeishan large igneous province: Petrographical and geochemical evidence - Yang Li; Xiyan Yang; Xinzhi Wang; Cunhui Fan; Xiangyu Fan; Yu Zhang; Rong Yang; Yue Li; Zisang Huang; Fei Huo (Marine and Petroleum Geology, 2024)

Navigating the complexity of pharmaceutical wastewater treatment by “effective strategy, emerging technology, and sustainable solution” - Yujie Li; Chen Li; Zhenbei Wang; Yatao Liu; Yunhan Jia; Fan Li; Ruijun Ren; Amir Ikhlaq; Jolanta Kumirska; Ewa Maria Siedlecka; Oksana Ismailova; Fei Qi (Journal of Water Process Engineering, 2024)

Ammonia stripping by in situ biogas self-circulation to upgrade continuous thermophilic and mesophilic digestion of hydrothermal high-solid sludge - Li-Jie Wu; Xiao-Xiao Li; Fei Ye; Yu-Xiang Liu; Fan Yang; Quan Zhou; Yong-Kang Lyu (Bioresource Technology, 2024)

In the songs of Hainan gibbons: Automated individual dynamic monitoring from acoustic recordings - Zi-di Wang; Hai-gang Ma; Xu-kai Zhong; Chang-yue Zhu; Yu-xin Wang; Ji-chao Wang; Peng-fei Fan (Biological Conservation, 2024)

Optimized air-ground data fusion method for mine slope modeling - Dan Liu; Man Huang; Zhigang Tao; Chenjie Hong; Yuewei Wu; En Fan; Fei Yang (Journal of Mountain Science, 2024)

Spatially confined CuFe2O4 nanosphere in N/O-codoped porous carbon mimetics for triple-mode sensing of antibiotics and visual detection of neurotransmitters in biofluids - Ying Lin; Wan-Wan Shao; Dan Wu; Tong Zhang; Dan-Ni Fei; Ya-Nan Kong; Yi-Fan Gao; Shu-Chang Zhao; Rui-Lin Liu (Analytica Chimica Acta, 2024)

New Record Ocean Temperatures and Related Climate Indicators in 2023 - Lijing Cheng; John Abraham; Kevin E. Trenberth; Tim Boyer; Michael E. Mann; Jiang Zhu; Fan Wang; Fujiang Yu; Ricardo Locarnini; John Fasullo; Fei Zheng; Yuanlong Li; et al. (Advances in Atmospheric Sciences, 2024)
The global physical and biogeochemical environment has been substantially altered in response to increased atmospheric greenhouse gases from human activities. In 2023, the sea surface temperature (SST) and upper 2000 m ocean heat content (OHC) reached record highs. The 0–2000 m OHC in 2023 exceeded that of 2022 by 15 ± 10 ZJ (1 Zetta Joules = 10 21 Joules) (updated IAP/CAS data); 9 ± 5 ZJ (NCEI/NOAA data). The Tropical Atlantic Ocean, the Mediterranean Sea, and southern oceans recorded their highest OHC observed since the 1950s. Associated with the onset of a strong El Niño, the global SST reached its record high in 2023 with an annual mean of ∼0.23°C higher than 2022 and an astounding > 0.3°C above 2022 values for the second half of 2023. The density stratification and spatial temperature inhomogeneity indexes reached their highest values in 2023.

Diagnosis, isolation and description of a novel amnoonvirus recovered from diseased fancy guppies, Poecilia reticulata - Esteban Soto; Benjamin R. LaFrentz; Susan Yun; Dorothea Megarani; Eileen Henderson; Chutchai Piewbang; Amber E. Johnston; Somporn Techangamsuwan; Terry Fei Fan Ng; Janet Warg; Win Surachetpong; Kuttichantran Subramaniam (Journal of Fish Diseases, 2024)
The guppy, Poecilia reticulata , is one of the most common cultured ornamental fish species, and a popular pet fish highly desired by hobbyists worldwide due to its availability of many brilliantly coloured fish of many varieties. The susceptibility of guppies to diseases presents a remarkable concern for both breeders and hobbyists. In this study, we report the emergence of disease in fancy guppies caused by a previously uncharacterized virus in the USA. This virus was isolated from moribund guppies in two separate outbreaks in California and Alabama, from December 2021 to June 2023. The infected guppies presented with acute morbidity and mortality shortly after shipping, displaying nonspecific clinical signs and gross changes including lethargy, anorexia, swimming at the water surface, gill pallor, mild to moderate coelomic distension and occasional skin lesions including protruding scales, skin ulcers and hyperaemia. Histological changes in affected fish were mild and nonspecific; however, liver and testes from moribund fish were positive for Tilapia lake virus (TiLV), the single described member in the family Amnoonviridae , using immunohistochemistry and in situ hybridization, although the latter was weak. A virus was successfully recovered following tissue inoculation on epithelioma papulosum cyprini and snakehead fish cell lines. Whole genome sequencing and phylogenetic analyses revealed nucleotide and amino acid homologies from 78.3%–91.2%, and 78.2%–97.7%, respectively, when comparing the guppy virus genomes to TiLV isolates. Based on the criteria outlined herein, we propose the classification of this new virus, fancy tailed guppy virus (FTGV), as a member of the family Amnoonviridae , with the name Tilapinevirus poikilos (from the Greek ‘poikilos’, meaning of many colours; various sorts, akin to ‘poecilia’).

Exploring Seasonal Variations in Fish Communities: A Study of the Yellow River Estuary and Its Adjacent Waters Using eDNA and Trawl Surveys - Xiaoyang Wang; Fan Li; Fei Shao; Hongjun Song; Na Song; Xiaomin Zhang; Linlin Zhao (Fishes, 2024)
The Yellow River Estuary and its adjacent waters serve as crucial spawning, foraging, and nursery areas for marine organisms, possessing abundant biological resources. Monitoring fish communities provides a baseline for implementing the sustainable utilization of marine resources. In this study, data were collected from 15 spring surface and bottom sites and 17 summer surface sites using eDNA and trawl surveys. The results showed that 37, 40, and 35 fish species were detected using eDNA in the spring (surface and bottom) and summer (surface), respectively, with 38 fish species caught during summer trawling. The dominant species mainly belonged to Engraulidae of Clupeiformes in the spring and Gobiidae of Perciformes in the summer, characterized by smaller-sized, short-lived, and pelagic fish species. The summer surface communities exhibited higher diversity than the spring surface and bottom communities. NMDS analysis revealed a degree of seasonal differences in fish communities and that there may be a lack of vertical stratification in the spring communities. The pH and DO were identified as the key environmental factors affecting the fish community. Additionally, the combination of eDNA and trawl surveys was regarded as a superior survey method. Our study provides valuable information for understanding seasonal fish communities in the Yellow River Estuary and its adjacent waters, contributing to fishery resource management and conservation in the region.

CDK5-mediated rearrangement of vimentin during Duck Tembusu virus infection inhibits viral replication - Guangbin Bao; Shinuo Fan; Chunyan Hu; Chen Li; Fei Ma; Guijun Wang; Hongjie Fan; Qing Wang (Veterinary Microbiology, 2024)

Three-dimensional multi-channel structure NiCo alloy used for boosting efficient overall water splitting - Fan Yang; Zelin Li; Fei Zhu; Xiaolong Chen; Songwei Ge; Fei Yin; Fairy Fan Yang; Rui Yang; Yanjing Liu; Lili Gao; Qiang Wang; Rui Feng; et al. (Fuel, 2024)

MR-TADF emitter as a dual-functional solid additive to extend exciton lifetime and optimize morphology for organic solar cells with ∼19% efficiency - Rulin Hao; Hao Xia; Xumeng Wang; Han Wei; Jingwei Huang; Fei Wang; Yujia Zhang; Hua Tan; Mengbing Zhu; Xin Song; Qunping Fan; Weiguo Zhu (Chemical Engineering Journal, 2024)

Lowing surface steric hindrance of strongly-confined perovskite quantum dots enables efficient pure-red light-emitting diodes - Shixu Yang; Jing Li; Junfeng Wang; Lin Zhang; Linhan Fan; Xiong Chen; Fei Huang; Jianjun Tian (Chemical Engineering Journal, 2024)

Low-frequency Stimulation at the Subiculum Prevents Extensive Secondary Epileptogenesis in Temporal Lobe Epilepsy - Yujia Shen; Yiwei Gong; Xiaoli Da; Shajing Gao; Shuo Zhang; Minjuan Sun; Yuanzhi Yang; Xiaoyun Qiu; Menghan Li; Yang Zheng; Fan Fei; Yi Wang; et al. (Neuroscience Bulletin, 2024)

Effects of CO$$_2$$ vegetation forcing on precipitation and heat extremes in China - Zheng Chen; Xintong Hou; Peiyi Fan; Fei Ji; Li Li; Guiquan Sun; Guolin Feng; Zhonghua Qian (Climate Dynamics, 2024)

Development of a probabilistic agricultural drought forecasting (PADF) framework under climate change - Yizhuo Wen; Yifan Fei; Yurui Fan; Aili Yang; Bingqing Wang; PangPang Gao; Daniel Scott (Agricultural and Forest Meteorology, 2024)

Assessment of the Carbon Footprint of Large Yellow Croaker Farming on the Aquaculture Vessel in Deep Sea in China - Fei Fan; Jianli Zheng; Huang Liu; Mingchao Cui (Journal of Marine Science and Engineering, 2024)
The present study conducted a Life Cycle Assessment (LCA) to evaluate the carbon emissions associated with large yellow croaker farming on Aquaculture Vessel “Conson No. 1”. The functional unit considered was 1 kg of fresh large yellow croakers delivered to a wholesaler. The life cycle of large yellow croaker farming on the aquaculture vessel was divided into five processes: feed production (FP), ship construction (SC), fingerling breeding (FB), adult fish farming (AF), and fish distribution (FD). Results showed that the carbon footprint (CF, kgCO2e/kg LW) for the complete life cycle amounted to 6.2170 kgCO2e/kg LW, while the CF per unit economic value of “Conson No. 1” large yellow croaker was estimated at 31 gCO2e/CNY. Among all processes, AF and FP had the highest CF contribution rates at 69.30% and 24.86%, respectively. Notably, energy consumption by aquaculture equipment on board emerged as the primary contributor across all sources of CF comparative analysis demonstrated that the CF of marine fish farming on the aquaculture vessel was lower than that of closed aquaculture systems’ average level and it was a viable option for implementing low-carbon aquaculture in the deep sea. In order to reduce energy consumption and promote a low-carbon economy in aquaculture vessels, several suggestions were proposed, including adjusting energy structure, enhancing energy efficiency, improving feed ratio, and optimizing feeding methods.

Large-scale quantum emulating simulations of biomolecules: A pilot exploration of parallel quantum computing - Honghui Shang; Fei Wang; Yi Fan; Huan Ma; Qi Liu; Chu Guo; Pengyu Zhou; Qi Chen; Qian Xiao; Tianyu Zheng; Bin Li; Fen Zuo; et al. (Science Bulletin, 2024)

Review of wave attenuation by artificial oyster reefs based on experimental analysis - Wei Xu; Aifeng Tao; Risheng Wang; Shufang Qin; Jun Fan; Jinyang Xing; Fei Wang; Gang Wang; Jinhai Zheng (Ocean Engineering, 2024)

Methane sulfonic acid-assisted synthesis of g-C3N4/Ni2P/Ni foam: Efficient, stable and recyclable for photocatalytic nitrogen fixation under visible light - Xianqiang Gao; Bowen Zhang; Lulu Cao; Fei Liu; Hai Fan; Chuanjun Wang; Jing Xu (Journal of Environmental Chemical Engineering, 2024)

The initial magma–fluid evolution of the Laochang porphyry molybdenum deposit in Lancang, Yunnan, SW China: Insights from the in-situ analysis of mica and titanite - Ying-Ying Zhang; Tai-Yi Luo; Yun-Fei Fan; Han-Sheng Long; Yong Yang; Jin-Biao Yang; Fu-Qing Meng (Journal of Asian Earth Sciences, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Bisphenol F exposure induces depression-like changes: Roles of the kynurenine metabolic pathway along the “liver-brain” axis - Zheng Yu; Yuxin Lin; Linlin Wu; Luyao Wang; Yichun Fan; Liuting Xu; Linwei Zhang; Weilan Wu; Jingxian Tao; Fei Huan; Wenwei Liu; Jun Wang; et al. (Environmental Pollution, 2024)

An upcycling bioprocess for sustainable aviation fuel production from food waste-derived greenhouse gases: Life cycle assessment and techno-economic analysis - Chenyue Zhang; Rongzhan Fu; Lixia Kang; Yingqun Ma; Daidi Fan; Qiang Fei (Chemical Engineering Journal, 2024)

Performance boosting by induction heating for hydrolysis of carbonyl sulfide using magnetic ordered mesoporous alumina as catalyst - Chao Huang; Yunchuan Hong; Binchen Wu; Hongchao Yu; Xiangqian Du; Min Pan; Weiyi Fan; Fei Gao; Feng Wu; Yixin Zhong; Lin Li; Guoshu Deng; et al. (Chemical Engineering Journal, 2024)

Recrystallization strategy of ZnBTC nanowires and derivates for supercapacitor application - Fei-Bao Zhang; Zu-Shun Fan; Brian Yuliarto; Sameh M. Osman; Minjun Kim; Yusuke Yamauchi (Chemical Engineering Journal, 2024)

Generation of dichloroacetonitrile with the co-presence of g-C3N4 and chloride in peroxymonosulfate/Vis system: Impacts and mechanism - Zhiwei Zhao; Yu Li; Fei Wang; Zhitao Xu; Sai Zhang; Li Li; Junyu Fan; Jie Liu (Chemical Engineering Journal, 2024)

ASAPA: a bioinformatic pipeline based on Iso-Seq that identifies the links among alternative splicing, alternative transcription initiation and alternative polyadenylation - Fei Wang; Zhongxin Jin; Shengnan Wang; Longcheng Yang; Zongbao Fan; Yuxin Yao (Functional & Integrative Genomics, 2024)

Occurrence, Species, and Health Effects of Groundwater Arsenic in Typical Rural Areas Along the Northern Foot of the Qinling Mountains, China - Qianqian Du; Jianhua Wu; Fei Xu; Yongqiang Yang; Fan Li (Exposure and Health, 2024)

Will the Globe Encounter the Warmest Winter after the Hottest Summer in 2023? - Fei Zheng; Shuai Hu; Jiehua Ma; Lin Wang; Kexin Li; Bo Wu; Qing Bao; Jingbei Peng; Chaofan Li; Haifeng Zong; Yao Yao; Baoqiang Tian; et al. (Advances in Atmospheric Sciences, 2024)

Dissolved organic matter promoted hydroxyl radical formation and phenanthrene attenuation during oxygenation of iron-pillared montmorillonites - Mengjing Guo; Longliang Wang; Haiyan Du; Fei Liu; Keli Yang; Yaoling Zhang; Shisuo Fan; Xin Liu; Huacheng Xu (Chemosphere, 2024)

The effect of astaxanthin on the alkalinity stress resistance of Exopalaemon carinicauda - Wenyang Li; Jiajia Wang; Jitao Li; Ping Liu; Fan Fei; Baoliang Liu; Jian Li (Science of The Total Environment, 2024)

Towards the co-benefits of carbon capture, utilization and sequestration: A life cycle assessment study for steel slag disposal - Zijie Li; Yi Xing; Mengying Ma; Wei Su; Yongkang Cui; Jinglei Tian; Fan Fei (Journal of Cleaner Production, 2024)

New multi-source waste co-incineration and clustering park operating model for small- and medium-sized city: A case study in China - Fan Fei; Zongguo Wen; Jiayue Zhang; Yi Xing; Hongbo Zhang; You Li (Journal of Environmental Management, 2024)

Superpixelwise likelihood ratio test statistic for PolSAR data and its application to built-up area extraction - Fan Zhang; Xuejiao Sun; Fei Ma; Qiang Yin (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Corrigendum to “Transformation of lakebed into a major soluble-salt-bearing dust source for Asia since the mid-pleistocene” [Global and Planetary Change 230 (2023) 1–14 /104282] - Xiaoyun Sun; Fei Wang; Yuxin Fan; Zaijun Li; Xin Liu; Jie Zhao; Baofeng Li; Dunsheng Xia (Global and Planetary Change, 2024)

Stochastic response of nonlinear oscillators under non-homogeneous Poisson white noise excitations - Fei-Fan Meng; Qingxuan Shi; Siu-Siu Guo (Engineering Structures, 2024)

Deciphering Soil Fertility of Tobacco Planting Fields with Back Propagation Artificial Neural Networks in Southwest China - Fei Wang; Zhiyong Fan; Yan Kuai; Nan Sun; Xiaomei Cheng; Jiuquan Zhang; Dexun Wang; Jiaen Su; Minggang Xu (Journal of Soil Science and Plant Nutrition, 2024)

A novel heterotrophic cultivation process of Euglena gracilis based on NaCl stress significantly increases the paramylon production - Kaikai Zhang; Minxi Wan; Wenmin Bai; Zhengxu Bao; Xingbo Duan; Weiliang Wang; Fei Fan; Yuanguang Li (Algal Research, 2024)

Insights into the interaction between stocking density and feeding rate in fish Megalobrama ambylcephala based on growth performance, innate immunity, antioxidant activity, and the GH-IGF1 axis - Zi-Shang Liu; Ling Zhang; Wei-Liang Chen; Chao-Fan He; Xiang-Yu Qian; Wen-Bin Liu; Xiang-Fei Li (Aquaculture, 2024)

Toxicity and chemical characterization of shale gas wastewater discharged to the receiving water: Evidence from toxicity identification evaluation - Zhimin Zhou; Fan Wu; Yujun Tong; Shaoqiong Zhang; Liang Li; Fei Cheng; Biao Zhang; Xiangying Zeng; Zhiqiang Yu; Jing You (Science of The Total Environment, 2024)

Whether biorefinery is a promising way to support waste source separation? From the life cycle perspective - Hongzhi Ma; Yulian Wei; Fan Fei; Ming Gao; Qunhui Wang (Science of The Total Environment, 2024)

Spatio-temporal variability of fishing habitat suitability to tuna purse seine fleet in the Western and Central Pacific Ocean - Shenglong Yang; Lijun Wang; Yingjie Fei; Shengmao Zhang; Linlin Yu; Heng Zhang; Fei Wang; Yumei Wu; Zuli Wu; Wei Wang; Jiayu Shi; Keji Jiang; et al. (Regional Studies in Marine Science, 2024)

A modified Green-Ampt infiltration model for muddy water - Shouxuan Kang; Liangjun Fei; Yun Zhong; Penghui Zhao; Zhen Yang; Qianwen Fan (Journal of Hydrology, 2024)

Antibiotic resistance genes and heavy metals in landfill: A review - Yan-Jiao Li; Ying Yuan; Wen-Bing Tan; Bei-Dou Xi; Hui Wang; Kun-Long Hui; Jia-Bao Chen; Yi-Fan Zhang; Lian-Feng Wang; Ren-Fei Li (Journal of Hazardous Materials, 2024)

Molecular characterization and functional study of a galectin-9 from a teleost fish, Boleophthalmus pectinirostris - Yong-Fei Zhu; Yi-Fan Hu; Chang-Hong Li; Li Nie; Jiong Chen (Fish & Shellfish Immunology, 2024)

Vertically aligned graphene-MXene nanosheets based electrodes for high electrochemical performance asymmetric supercapacitor - Yanfei Yu; Haopeng Zhang; Yanqiu Xie; Fan Jiang; Xin Gao; He Bai; Fei Yao; Hongyan Yue (Chemical Engineering Journal, 2024)

Biogas upgrading by biotrickling filter: Effects of temperature and packing materials - Jie-Hua Huang; Xiao-Lei Fan; Rui Li; Meng-Ting Sun; Hua Zou; Yi-Feng Zhang; Rong-Bo Guo; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Structural engineering of rare earth metal-organic frameworks derivatives with high anisotropy for high-efficiency electromagnetic wave absorption - Lutong Li; Jiurong Liu; Fei Pan; Jing Qiao; Xue Zhang; Jingpeng Lin; Wei Liu; Qilei Wu; Shifei Tao; Fan Wu; Zhihui Zeng (Chemical Engineering Journal, 2024)

Artificial neural networks prediction and optimization based on four light regions for light utilization from Synechocystis sp. PCC 6803 - Tao Yu; Fei Fan; Lei Huang; Weiliang Wang; Minxi Wan; Yuanguang Li (Bioresource Technology, 2024)

Correction to: a novel method for optimizing regional-scale management zones based on a sustainable environmental index - Yue Li; Davide Cammarano; Fei Yuan; Raj Khosla; Dipankar Mandal; Mingsheng Fan; Syed Tahir Ata-UI-Karim; Xiaojun Liu; Yongchao Tian; Yan Zhu; Weixing Cao; Qiang Cao (Precision Agriculture, 2024)

A novel method for optimizing regional-scale management zones based on a sustainable environmental index - Yue Li; Davide Cammarano; Fei Yuan; Raj Khosla; Dipankar Mandal; Mingsheng Fan; Syed Tahir Ata-UI-Karim; Xiaojun Liu; Yongchao Tian; Yan Zhu; Weixing Cao; Qiang Cao (Precision Agriculture, 2024)

Promoting rice growth can effectively reduce NH3 volatilization in paddy soil under rice-based cropping system - Wei Zhou; Yu Fan; Yanqiu Chen; Zhitao Hu; Tao Wang; Yong Chen; Fei Deng; Xiaolong Lei; Youfeng Tao; Wanjun Ren (Nutrient Cycling in Agroecosystems, 2024)

Measurement and Analysis of Impulse Source Produced by Ballistic Shock Wave Therapy Device in Different Medium Using PVDF Sensor - Fan Fan; Liansheng Xu; Qiong Wu; Fei Shen; Li Wang; Fengji Li; Yubo Fan; Haijun Niu (Journal of Medical and Biological Engineering, 2024)

Rheumatoid arthritis is a protective factor against Alzheimer’s disease: a bidirectional two-sample Mendelian randomization study - Guo-Shuai Li; Yong-Ze Yang; Guo-Rong Ma; Peng-Fei Li; Qing-Hao Cheng; An-Ren Zhang; Zhuang-Zhuang Zhang; Fu-Kang Zhang; Xin Yang; Hua Fan; Hong-Zhang Guo (Inflammopharmacology, 2024)

Interactive effects of dietary leucine and isoleucine affect amino acid profile and metabolism through AKT/TOR signaling pathways in blunt snout bream (Megalobrama amblycephala) - Mang-mang Wang; Yang-yang Huang; Wen-bin Liu; Kang Xiao; Xi Wang; Hui-xing Guo; Yi-lin Zhang; Jing-Wei Fan; Xiang-fei Li; Guang-zhen Jiang (Fish Physiology and Biochemistry, 2024)

Dual-emissive Eu(III)-functionalized metal-organic frameworks for visual, rapid, and intelligent sensing of albendazole and albendazole sulfoxide in animal-origin food - Hou-Qun Yuan; Yi-Fan Xia; Yu-Fei Zhong; Wei Li; Hongda Zhu; Ran Wang; Peiyao Chen; Zhiming Gao; Xiangwei Zhu; Yan-Xia Li; Guang-Ming Bao (Analytica Chimica Acta, 2024)

Effects of shelter on the welfare of juvenile Amphioctopus fangsiao: Survival, growth, behavior and physiology - Yuanhai Hu; Jian Zheng; Fei Han; Luyan Fan; Youqing Liu; Yaosen Qian; Qingqi Zhang; Xiaodong Zheng (Aquaculture, 2024)

A level IV fugacity-based multimedia model based on steady-state particle/gas partitioning theory and its application to study the spatio-temporal trends of PBDEs in atmosphere of northeast China - Meng Qin; Wan-Li Ma; Pu-Fei Yang; Wen-Long Li; Lei Wang; Li-Li Shi; Li Li; Yi-Fan Li (Science of The Total Environment, 2024)

Evaluating nutrient limitation in co-culture of Chlorella pyrenoidosa and Rhodobacter sphaeroides - Xiao-Fei Shen; Ya-Ping Xu; Yi-Fan Jiang; Lin-Jun Gao; Xiao-Qin Tong; Jing Gong; Yan-Fang Yang; Raymond Jianxiong Zeng (Science of The Total Environment, 2024)

Investigating key factors influencing consumer plastic bag use reduction in Nanjing, China: A comprehensive SEM-ANN analysis - Yue Zhou; Weijun Gao; Takaaki Kato; Wanxiang Yao; Chunyan Shi; Jinming Wang; Fan Fei (Process Safety and Environmental Protection, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

Mechanism insight into highly efficient stabilization of Cd contaminated soils by steam flash heating - Xiaolu Fan; Xue Wu; Xueyan Li; Tianyun Wu; Bo Jiang; Jing Xiong; Fei Li; Shupeng Li; Lei Zheng; Xinzi Wang; Linying Yao; Fang Zhang; et al. (Journal of Cleaner Production, 2024)

Determination of operational parameters for the first stage of continuous temperature-phased anaerobic digestion of oily food waste: Influent concentration, hydraulic retention time, pH control and temperature - Li-Jie Wu; Xiao-Xiao Li; Fei Ye; Fan Yang; Yong-Kang Lyu (Journal of Cleaner Production, 2024)

Role of crustal radiogenic heating in ultra-high temperature metamorphism of the Greater Himalayan Crystalline complex: Phase equilibrium and numerical modelling - Yin-Long Fan; Li-Fei Zhang; Yang Wang; Zhong-Hai Li (Gondwana Research, 2024)

Preparation and characterization of lotus root starch based bioactive edible film containing quercetin-encapsulated nanoparticle and its effect on grape preservation - Ya-Fan Zeng; Ying-Ying Chen; Yuan-Yuan Deng; Chao Zheng; Cheng-Zhi Hong; Qiang-Ming Li; Xue-Fei Yang; Li-Hua Pan; Jian-Ping Luo; Xue-Ying Li; Xue-Qiang Zha (Carbohydrate Polymers, 2024)

Spatiotemporal patterns and quantitative analysis of influencing factors of PM2.5 and O3 pollution in the North China Plain - Mingliang Ma; Mengnan Liu; Xueyan Song; Mengjiao Liu; Wenping Fan; Yuqiang Wang; Huaqiao Xing; Fei Meng; Yongqiang Lv (Atmospheric Pollution Research, 2024)

Vector-mediated viral exchange between crops and weedy plants - Xiao-bin Shi; Zhuo Zhang; Fan Li; Evan L. Preisser; Li-ping Huang; De-yong Zhang; Zhan-hong Zhang; Song-bai Zhang; Xu-guo Zhou; An-sheng Zhang; Hui Liu; Yuan-hua Wu; et al. (Journal of Pest Science, 2024)

Emergency treatment effect evaluation of rear-slope cutting and front-slope pressing on a hydrodynamic pressure landslide: a case study of the Shuping landslide in the Three Gorges Reservoir Area - Zhihong Fan; Shimei Wang; Li Wang; Fei Guo; Fangyun Nan; Yuxuan Hu (Bulletin of Engineering Geology and the Environment, 2024)

Fluid mud induced by periodic tidal advection and fine-grained sediment settling in the Yangtze estuary - Hao Wu; Jieping Tang; Weihua Li; Fei Xing; Haifei Yang; Fan Zhang; Ya Ping Wang (Frontiers in Marine Science, 2023)
This study presents in-situ observations of fluid mud in the Yangtze Estuary via a bottom tripod. Six occurrences of periodic fluid muds (F1-F6) were observed at high slack water, with suspended sediment concentration (SSC) exceeding 10 kg/m 3 . The thickness of the fluid mud varied across the six occurrences, reaching a maximum of 0.32m. Notably, temperature and salinity anomalies were observed within the fluid mud. The formation of fluid mud was found to be influenced by turbulence, with turbulence kinetic energy (TKE) below 5×10 -4 m 2 /s 2 favoring settling as the primary cause of formation. The critical shear stress ( τ cw ) for fluid mud formation was estimated to be approximately 0.09 Pa. The formation of fluid muds during early tidal cycles was attributed to liquefaction and bed erosion resulting from strong waves. However, in most cases, the wave energy was insufficient for erosion, suggesting that advection played a role in sediment supply during the subsequent tide cycles. The increased cross-channel current velocity during flood facilitated the lateral transport of a significant amount of eroded sediment from shallow water into the channel. Due to its short duration, the fluid mud layer was entrained by the current before consolidation. Enhanced turbulence led to the breakdown of fluid mud at the early ebb. The critical τ cw for fluid mud breakdown depended on the density and duration of the fluid mud, with a maximum value of up to 0.70 Pa. The absence of the fluid mud layer during low slack water and neap tide was associated with a reduction in advection and tidal pumping, disrupting the original sediment balance between supply and demand. These data provide valuable insights into the formation and breakdown of fluid mud, contributing to estuarine hydrodynamic modeling studies and enhancing the understanding of estuary dynamics.

Strontium alleviated the growth inhibition and toxicity caused by cadmium in rice seedlings - Jun Liu; Xinting Fan; Yuanyuan Jiang; Juan Ni; Aili Mo; Meihan Cai; Tong Li; Yaqi Wang; Peishuang He; Shiyu Hu; Tangjian Peng; Cuiying Peng; et al. (Science of The Total Environment, 2023)

Green transformation strategy of pallet logistics in China based on the life cycle analysis - Tingting Zhang; Zongguo Wen; Fan Fei; Vorada Kosajan; Yiqi Tan; Mao Xu; Paul Ekins (Science of The Total Environment, 2023)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

Diverse indole-diterpenoids with protein tyrosine phosphatase 1B inhibitory activities from the marine coral-derived fungus Aspergillus sp. ZF-104 - Fei Zhang; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Qing-Yun Ma; Lu-Ting Dai; Li-Man Zhou; Hao-Fu Dai; Fan-Dong Kong; Du-Qiang Luo; You-Xing Zhao (Phytochemistry, 2023)

Unraveling the driving factors of the plastic waste trade network formation and dynamics - Fei Liu; Chenlu Fan; Jinhui Li; Quanyin Tan (Journal of Environmental Management, 2023)

JAZ1 gene regulates starch biosynthesis and changes physicochemical properties in wheat grains - Sha-Sha Yuan; Peng Fan; Dan-Dan Zhang; Hai-Tao Liu; Peng-Fei Wang; Tian-Cai Guo; Ge-Zi Li; Yong-Hua Wang; Guo-Zhang Kang (Food Bioscience, 2023)

Effects of Water and Nitrogen Coupling on Apple Yield, Soil Water and Nitrogen Distribution, and Enzyme Activity Under Surge-Root Irrigation in Loess Plateau, China - Youliang Peng; Liangjun Fei; Kun Hao; Feilong Jie; Fangyuan Shen; Lihua Liu; Qianwen Fan (Journal of Soil Science and Plant Nutrition, 2023)

Mulching and Planting Density on Photosynthesis, Lodging Resistance, and Yield of Maize - Li Zhao; Guangming Xie; Mingyuan Fan; Sumera Anwar; Qi Zhang; Jingying Lu; Liguang Zhang; Fei Gao; Chuangyun Wang (International Journal of Plant Production, 2023)

Construction and application of highly efficient waste cooking oil degrading bacteria consortium in oily wastewater - Zhuo-qun Zhao; Jian Yang; Heng-yuan Chen; Wen-fan Wang; Xiao-jian Lian; Xiao-jie Xie; Min Wang; Ke-fei Yu; Hua-bao Zheng (Environmental Science and Pollution Research, 2023)

Efficient removal of Cd(II) and Pb(II) from aqueous solution using biochars derived from food waste - Shuai Tian; Xueliu Gong; Qiuyu Yu; Fei Yao; Wenjian Li; Zilin Guo; Xin Zhang; Yuan Yuan; Yuqing Fan; Rongjun Bian; Yan Wang; Xuhui Zhang; et al. (Environmental Science and Pollution Research, 2023)

A Deep Learning-Based Lightweight Model for the Detection of Marine Fishes - Fei Wu; Yitao Zhang; Lang Wang; Qiu Hu; Shengli Fan; Weiming Cai (Journal of Marine Science and Engineering, 2023)
The species and population size of marine fish are important for maintaining the ecological environment and reflecting climate change. Traditional fish detection methods mainly rely on manual or traditional computer vision, which has disadvantages such as complex design, low detection accuracy, and poor generalization. The widespread use of ocean observation systems has accumulated a large number of images and videos, which makes the application of deep learning on marine fish detection possible. In this paper, a real-time high-precision fish detection algorithm based on YOLOv5s is constructed. Considering the enhancement of the channel representation and spatial interaction ability of the model, the attention mechanism and gated convolution are introduced, respectively, and GhostNet is introduced to lighten the model. Through a series of model comparisons, two improved models, S-Head-Ghost-Fish9 and S-SE-HorBlock-Head-Ghost-Fish9, are finally obtained. Compared with the original model, in terms of model size, the former reduces by 19% and the latter increases by 9.5%; in terms of computation, the former reduces by 15.7% and the latter reduces by 3.1%; in terms of detection speed, both take about 17 ms to detect a single image, and both can meet the real-time detection requirements; in terms of detection accuracy, the former improves by 3% and the latter by 3.6%. Compared with the latest detection algorithms of YOLOv6 and YOLOv8, the detection accuracy is slightly lower than 1%, but the model size and computation amount are only 1/3 to 1/2 of them. The improved models can help assess the population size and growth of the fish, which is of great significance in maintaining the stability of the fish population.

CatBoost algorithm for estimating maize above-ground biomass using unmanned aerial vehicle-based multi-source sensor data and SPAD values - Weiguang Zhai; Changchun Li; Shuaipeng Fei; Yanghua Liu; Fan Ding; Qian Cheng; Zhen Chen (Computers and Electronics in Agriculture, 2023)

Coupling coordination between the ecological environment and urbanization in the middle reaches of the Yangtze River urban agglomeration - Xinmin Zhang; Houbao Fan; Fei Liu; Tiangui Lv; Lu Sun; Zhaoling Li; Wenlong Shang; Guoliang Xu (Urban Climate, 2023)

Cadmium affects the growth, antioxidant capacity, chlorophyll content, and homeostasis of essential elements in soybean plants - Jun Liu; Juan Ni; Aili Mo; Xinting Fan; Yuanyuan Jiang; Hongyan Xie; Jingsong Hu; Yunhua Zhu; Cuiying Peng; Fei Yang (South African Journal of Botany, 2023)

Physiological and transcriptomic analyses reveal that phytohormone pathways and glutathione metabolism are involved in the arsenite toxicity response in tomatoes - Yingzhi Wang; Menglu Xing; Xinru Gao; Min Wu; Fei Liu; Liangliang Sun; Ping Zhang; Ming Duan; Weixin Fan; Jin Xu (Science of The Total Environment, 2023)

Field test on the mechanism of composite bucket foundation penetrating sandy silt overlying clay - Xun Zhu; Zheng Chen; Yun-Fei Guan; Pengpeng Ni; Kai-Fang Fan; Yuan-Xu Jing; Chun-Jie Yang (Ocean Engineering, 2023)

Rice bran is a key structure affecting high nutrition and low toxicity of indica hybrid rice (Oryza sativa L.) - Yu Fan; Yujie Yuan; Zhiyou Gong; Yajun Wang; Xiufeng Mei; Fengjun Yan; Tao Wang; Fei Deng; Yong Chen; Xiaolong Lei; Jianfeng Hu; Youfeng Tao; et al. (Journal of Cereal Science, 2023)

Transformation of lakebed into a major soluble-salt-bearing dust source for Asia since the mid-pleistocene - Xiaoyun Sun; Fei Wang; Yuxin Fan; Zaijun Li; Xin Liu; Jie Zhao; Baofeng Li; Dunsheng Xia (Global and Planetary Change, 2023)

Integrative risk assessment method via combining geostatistical analysis, random forest, and receptor models for potentially toxic elements in selenium-rich soil - Hao Wu; Nan Cheng; Ping Chen; Fei Zhou; Yao Fan; Mingxing Qi; Jingyi Shi; Zhimin Zhang; Rui Ren; Cheng Wang; Dongli Liang (Environmental Pollution, 2023)

Evolution law and mechanism of time-delayed spalling in a deep TBM tunnel: A case study - Chen Fan; Xia-Ting Feng; Lianjie Fu; Jun Zhao; Chengxiang Yang; Zhibin Yao; Jun Wang; Fei Wei (Engineering Geology, 2023)

Influence of greenery configuration on summer thermal environment of outdoor recreational space in elderly care centers - Fan Fei; Yan Wang; Luyao Wang; Hiroatsu Fukuda; Wanxiang Yao (Building and Environment, 2023)

Evaluating Suitability of Fishing Areas for Squid-Jigging Vessels in the Northwest Pacific Ocean Derived from AIS Data - Yingjie Fei; Shenglong Yang; Mengya Huang; Xiaomei Wu; Zhenzhen Yang; Jiangyue Zhao; Fenghua Tang; Wei Fan; Sanling Yuan (Fishes, 2023)
Understanding the spatial distribution of fishing activity and suitable fishing areas is important for improving sustainable fisheries management and protecting vulnerable fish stocks. To identify climate-related habitat changes and variations in the distribution of fishing activity for squid-jigging vessels in the Northwest Pacific Ocean, two types (weighted arithmetic mean method, weighted-AMM; weighted geometric mean method, weighted-GMM) of habitat suitability index (HSI) models were developed in this study with marine environmental data at different depths. The boosted regression tree (BRT) model was adopted to access the monthly important environmental variables and the relative influence of the corresponding variables. The results showed that the weighted-AMM has better prediction performance than the weighted-GMM. The suitable fishing areas showed significant seasonal changes in both spatial location and coverage area. The hotspot map showed that the suitable fishing area for squid-jigging vessels was located in the scope of 42∘ N∼44∘ N, 155∘ E∼170∘ E throughout the year during 2012∼2019, which suggests that high squid-jigging fishing pressure should be given more attention in fishery management. The HSI model also had good prediction performance for the fishery data of Chinese companies, except for June and July. Additionally, fishing efforts could be used as alternative data for fishery research. The study has also suggested that fishery data are restricted by spatial and temporal distribution and fishing experience, which probably biases the results of the research.

Short-term effect of meteorological factors and extreme weather events on daily outpatient visits for dry eye disease between 2013 and 2020: a time-series study in Urumqi, China - Si-Yu Gui; Fei Wang; Jian-Chao Qiao; Xin-Chen Wang; Zhi-Hao Huang; Fan Yang; Cheng-Yang Hu; Fang-Biao Tao; Li-Ming Tao; Dong-Wei Liu; Xiang-Long Yi; Zheng-Xuan Jiang (Environmental Science and Pollution Research, 2023)

Investigation of composite bucket foundation bearing characteristics in various soil properties - Kai-Fang Fan; Yun-Fei Guan; Xun Zhu; Wen-Xuan Li; Yi Tang; Yuan-Yi Chen (Marine Georesources & Geotechnology, 2023)

Co-evolution of orbital-to-millennial East Asian monsoon and westerlies variability over the past 150 ka - Xingxing Liu; Jie Wu; Jef Vandenberghe; Hong Chang; Zhengguo Shi; Fei Guo; Yougui Song; Peng Cheng; Shugang Kang; Jianghu Lan; Yidan Ding; Huimin Fan; et al. (Quaternary Science Reviews, 2023)

Two episodes of Mesozoic granitic magmatism in East Qinling, central China: Constraints from geochemistry and isotope geochronology of the Huangbeiling pluton - Zesheng Qian; Fan Yang; Weidong Ren; M. Santosh; Jinhao Liu; Huan Li; Fei Xue (Lithos, 2023)

Longan pulp polysaccharides regulate gut microbiota and metabolites to protect intestinal epithelial barrier - Yajuan Bai; Yue Zhou; Xiang Li; Ruifen Zhang; Fei Huang; Bei Fan; Litao Tong; Fengzhong Wang; Mingwei Zhang (Food Chemistry, 2023)

Sediment exchange between southern yellow sea and Yangtze river Estuary in response to storm events - Yao Xu; Fei Xing; Jun Cheng; Fan Zhang; Hailun He; Jicai Zhang; Jianjun Jia; Ya Ping Wang (Estuarine, Coastal and Shelf Science, 2023)

Realization of highly deformable freestanding borophene hybrid film for flexible energy storage device - Jiali Yu; Zhimin Fan; Fei Yu; Hang Zhao; Pingping Yao; Shengnan Chen; Haiyan Yang; Caizhen Zhu; Jian Xu (Chemical Engineering Journal, 2023)

Coupling architectural and electronic engineering over cobalt molybdenum intermetallic compound for boosting hydrogen generation from ammonia borane - Jiahuan He; Panpan Zhou; Xuezhang Xiao; Fei Chu; Liuzhang Ouyang; Baozhong Liu; Ruhong Li; Ziwei Huang; Leijie Hu; Sicheng Yuan; Tao Zhou; Xiulin Fan; et al. (Chemical Engineering Journal, 2023)

Nonlinear seismic response analysis of layered seabed considering seawater-seabed coupling effects - Hong-Fei Fan; Yan-Zhen Wang; Guo-Xing Chen; Wei-Yun Chen; Kai Zhao; Sheng-Dong Zhu (Frontiers in Marine Science, 2023)
Earthquake in the sea area is an important factor affecting the safety of marine engineering construction, seabed site seismic response analysis is an important preliminary work for marine engineering construction. Based on a fluid-solid weak coupling model which could simulate seawater-seabed interaction, four typical borehole sections along the proposed tunnel at Qiongzhou strait are selected to establish layered seabed models for studying the seabed site seismic responses affected by the seawater, seabed soft sediments and bedrock earthquake motion under bidirectional seismic excitation, in which the dynamic nonlinearity of the seabed soft soil is simulated by a generalized non-Masing constitutive model (DCZ model). The result shows: the suppression effect of seawater on seabed seismic motion exists only in the shallow range of seabed (< 50 m), and the suppression effect on the vertical seismic response is higher than that along the horizontal direction; the suppression effect of seawater on the seabed surface seismic motion and the frequency response phenomenon of “high frequency suppression, low frequency amplification” of seabed seismic response is positively correlated with seawater depth; The mean lines of the horizontal and vertical spectrum β obtained by numerical calculation are higher than the design spectrum in the land code within several period ranges, and the possibility of adverse effects induced by seawater and seabed soft sedimentation on the seismic resistance of marine engineering should be considered.

Tigliane-and daphnane-type diterpenoids from the buds of Daphne genkwa with their cytotoxic activities - Ying Chen; Cai-Lin Zhao; Wei Dong; Fei-Fan Song; Li-Na Guo; Hong-Lian Zhang; Lv Zhen; Li Li; Jin Ye; Bo Song (Natural Product Research, 2023)

Effects of size and surface charge on the sedimentation of nanoplastics in freshwater - Honglu Zhu; Xiaolei Fan; Hua Zou; Rong-Bo Guo; Shan-Fei Fu (Chemosphere, 2023)

Analytical solutions of flow velocity profile based on the morphological response of flexible vegetation - Wei-Jie Wang; Yan-Fang Zhao; Shi Ren; Xiao-Bo Liu; Fei Dong; Jin-Jin Li; Jing-Jing Fan; Wen-Qiang Wu (Journal of Hydrology, 2023)

Mechanism-based understanding of the potential cellular targets of triclosan in zebrafish larvae - Fan Wang; Fei Liu (Environmental Toxicology and Pharmacology, 2023)

A novel porous asymmetric cation exchange membrane with thin selective layer for efficient electrodialysis desalination - Huiqin Fan; Yong Xu; Fei Zhao; Qing-Bai Chen; Di Wang; Jianyou Wang (Chemical Engineering Journal, 2023)

Hierarchical-structure and high-modulus aramid nanofiber membrane protective layer achieving high-performance lithium metal anode - Fan Wu; Zhichao He; Li Liu; Shengjie Guan; Fei Wang; Yudong Huang (Chemical Engineering Journal, 2023)

An innovative and efficient hydrogen peroxide-citric acid pretreatment of bamboo residues to enhance enzymatic hydrolysis and ethanol production - Fanyang Meng; Jing Fan; Fei Cui; Haiyan Yang; Zhengjun Shi; Dawei Wang; Jing Yang (Bioresource Technology, 2023)

A nosocomial Pseudomonas aeruginosa ST3495 isolated from a wild Burmese python (Python bivittatus) with suppurative pneumonia and bacteremia in Hainan, China - Roushan Li; Bo Ling; Jifeng Zeng; Xin Wang; Nuo Yang; Lixia Fan; Guiying Guo; Xuesong Li; Fei Yan; Jiping Zheng (Brazilian Journal of Microbiology, 2023)

Analysis of the effect of triclosan on gonadal differentiation of zebrafish based on metabolome - Fan Wang; Haifang Liu; Fei Liu (Chemosphere, 2023)

Toxicity identification evaluation for hydraulic fracturing flowback and produced water during shale gas exploitation in China: Evidence from tissue residues and gene expression - Fan Wu; Zhimin Zhou; Shaoqiong Zhang; Fei Cheng; Yujun Tong; Liang Li; Biao Zhang; Xiangying Zeng; Huizhen Li; Dali Wang; Zhiqiang Yu; Jing You (Water Research, 2023)

Moringa oleifera Lam. leaves as new raw food material: A review of its nutritional composition, functional properties, and comprehensive application - Min Yang; Liang Tao; Xin-Rui Kang; Zi-Lin Wang; Ling-Yan Su; Ling-Fei Li; Fan Gu; Cun-Chao Zhao; Jun Sheng; Yang Tian (Trends in Food Science & Technology, 2023)

The combined toxic effects of polystyrene microplastics and different forms of arsenic on the zebrafish embryos (Danio rerio) - Zheng Zhang; Xuewei Li; Jia Li; Yupeng Pan; Zile Zhuang; Xiaofeng Zhang; Canbin Chen; Yinglin Liu; Liwen Zhang; Yuxuan Luo; Fei Liu; Haoliang Fan; et al. (Science of The Total Environment, 2023)

Enhancement of waste activated sludge hydrolysis and decomposition by combined free nitrous acid and sodium citrate pretreatment - Wu-yang Zhou; Qian Fang; Wen-xue Ding; Zi-long Xiao; Fan Luo; Peng-fei Ren; Guang-hua Wang (Journal of Water Process Engineering, 2023)

Effectively removing gaseous polycyclic aromatic hydrocarbons (PAHs) by willow catkins: Do you still dislike the catkins floating? - Peng-Tuan Hu; Dong-Hai Liu; Zhi-Guo Cao; Hong Wei; Fu-Jie Zhu; Wan-Li Ma; Zi-Feng Zhang; Li-Yan Liu; Jing-Lan Feng; Yong-Feng Li; Yu-Fei Li; Yi-Fan Li (Journal of Hazardous Materials, 2023)

A new method for evaluating the synergistic effect of urban water body and vegetation in the summer outdoor thermal environment - Fan Fei; Luyao Wang; Yan Wang; Wanxiang Yao; Hiroatsu Fukuda; Yuling Xiao; Lei Tian; Tongtong Ji (Journal of Cleaner Production, 2023)

Mechanisms of urban blue-green infrastructure on winter microclimate using artificial neural network - Fan Fei; Yan Wang; Luyao Wang; Hiroatsu Fukuda; Wanxiang Yao; Yue Zhou; Xiaohan Dong (Energy and Buildings, 2023)

Chemical constituents from the pericarps of Zanthoxylum bungeanum Maxim. and their chemotaxonomic significance - Bang-Yin Tan; Cai-Feng Ding; Rui-Rong Guo; Jing-Zhi Zhao; Di-Wei Ma; Kun Fan; Lan-Chun Zhang; Rong-Ping Zhang; Wei-Yan Hu; Hao-Fei Yu (Biochemical Systematics and Ecology, 2023)

Mendelian randomization analysis reveals causal relationships between gut microbiome and optic neuritis - Kangcheng Liu; Pengfei Wu; Jing Zou; Huimin Fan; Hanying Hu; Yanhua Cheng; Fei He; Jingying Liu; Zhipeng You (Human Genetics, 2023)

Three-Dimensional Ultrasonic Reverse-Time Migration Imaging of Submarine Pipeline Nondestructive Testing in Cylindrical Coordinates - Daicheng Peng; Fei Cheng; Xiaoyu She; Yunpeng Zheng; Yongjie Tang; Zhuo Fan (Journal of Marine Science and Engineering, 2023)
Submarine pipelines are a safe and energy-efficient mode of gas transport. However, due to the complex manufacturing process and harsh operating environment, submarine pipelines are subject to fatigue cracks under long-term cyclic loading. A comprehensive and high-precision characterization strategy for submarine pipelines can effectively prevent potential safety hazards and have significant economic and social repercussions. As a matter of fact, pipeline defects cannot be reliably detected with current traditional 2D methods. On the other hand, in ultrasonic testing, cylindrical geometry increases the complexity of the 3D wave field in the submarine pipeline space and significantly influences the accuracy of the detection results. In this paper, we put forward a novel method for 3D ultrasonic image testing that is suitable for cylindrical coordinates. In order to accurately simulate the ultrasonic signal received from pipelines, we generalize the 3D staggered-grid finite-difference method from Cartesian coordinates to cylindrical ones and simulate the full wave field in the 3D pipeline space. Then, signal processing is performed on the ultrasound simulation records, and 3D reverse-time migration imaging of submarine pipeline defects can be effectively achieved using the reverse-time migration method and cross-correlation imaging conditions. The results obtained from simulations and real field data show that the proposed method provides high-quality 3D imaging of defects in pipelines, taking into account multiple scattering and mode conversion information at the bottom of the defects.

Effect of boiling on texture of scallop adductor muscles and its mechanism based on label-free quantitative proteomic technique - Zi-Xuan Wu; Yan-Hong Bai; Zi-Ye Wang; Ying-Chen Fan; Liang Song; Yu-Xin Liu; De-Yang Li; Peng-Fei Jiang; Da-Yong Zhou (Food Chemistry, 2023)

Study on winter thermal environment characteristics and thermal comfort of university classrooms in cold regions of China - Luyao Wang; Yan Wang; Fan Fei; Wanxiang Yao; Lixin Sun (Energy and Buildings, 2023)

Thermophysical and molecular mechanisms of a novel and cost-efficient Cr-contaminated soil stabilization by steam flash heating - Xiaolu Fan; Tianyun Wu; Xue Wu; Bo Jiang; Jing Xiong; Fei Li; Shupeng Li; Lei Zheng; Yunpeng Liu; Dayi Zhang (Chemical Engineering Journal, 2023)

Anthropogenic Contribution to the Rapid Warming over the Tibetan Plateau - Yu Wang; Pengcheng Yan; Fei Ji; Bicheng Huang; Peiyi Fan; Guolin Feng (Climate Dynamics, 2023)

Evaluation of the treatment effect of rear slope cutting on hydrodynamic pressure landslides: A case study - Li Wang; Jun-jie Huang; Yong Chen; Shi-mei Wang; Zhi-hong Fan; Fei Guo; Xiao-wei Li (Journal of Mountain Science, 2023)

Enhanced degradation of fomesafen by a rhizobial strain Sinorhizobium sp. W16 in symbiotic association with soybean - Wei Chen; Yan Gao; Gaoling Shi; Jiangye Li; Guangping Fan; Chenye Yang; Bo Wang; Fei Tong; Yuntao Li (Applied Soil Ecology, 2023)

Site-directed transformants with E407K substitution in Bcmdl1 possesses different fitness from field anilinopyrimidine resistant isolates with E407K mutation in Botrytis cinerea - Fei Fan; Ming-Yi Wu; Yong-Xu Zhu; Guo-Qing Li; Chao-Xi Luo (Pesticide Biochemistry and Physiology, 2023)

Formation and transport of fluid mud triggered by typhoon events in front of the subaqueous Changjiang Delta - Jieping Tang; Hao Wu; Fei Xing; Fan Zhang; Bixuan Tang; Gaocong Li; Ya Ping Wang (Marine Geology, 2023)

Excess methane production and operation stability for anaerobic digestion of oily food waste controlled by mixing intensity: Focusing on heterogeneity of long chain fatty acids - Li-Jie Wu; Zi-Wen Hao; Xiao-Xiao Li; Fei Ye; Fan Yang; Yong-Kang Lyu (Journal of Environmental Management, 2023)

Plasma-reconstructed LaMnO3 nanonetwork supported palladium catalyst for methane catalytic combustion - Jinlin Jiang; Cuicui Wang; Shuai Zhao; Fan Xue; Lei Li; Mifen Cui; Xu Qiao; Zhaoyang Fei (Journal of Environmental Chemical Engineering, 2023)

Enhanced simultaneous arsenite oxidation and sorption by Mn-modified biochar: Insight into the mechanisms under optimal modification condition - Qin Huang; Fei Tong; Yan Gao; Jinlin Chen; Dongmei Zhou; Zhiqiang Qu; Guangping Fan; Wei Chen; Gaoling Shi (Journal of Environmental Chemical Engineering, 2023)

Elastic full-wave field simulation in 3D tunnel space with the variable staggered-grid finite-difference method in cylindrical coordinates - Yunpeng Zheng; Fei Cheng; Jiangping Liu; Zhuo Fan; Bingkai Han; Jing Wang (Journal of Applied Geophysics, 2023)

Effect of low temperature on the resistance of Listeria monocytogenes and Escherichia coli O157:H7 to acid electrolyzed water - Man Yu; Chunling Jiang; Yuanyuan Meng; Fan Wang; Jiang Qian; Fulin Fei; Zhenjie Yin; Wei Zhao; Yong Zhao; Haiquan Liu (Food Research International, 2023)

Metabolomics profile of plasma in acute diquat-poisoned patients using gas chromatography-mass spectrometry - Xinhua Dai; Maozhu Liu; Shuyun Xu; Han Zhao; Xuezhi Li; Yangjuan Bai; Yuangao Zou; Yunfei An; Fei Fan; Jing Zhang; Bei Cai (Food and Chemical Toxicology, 2023)

Exosomes derived from EphB2-overexpressing bone marrow mesenchymal stem cells regulate immune balance and repair barrier function - Si Chu; Ting Yu; Wenzhu Wang; Hui Wu; Feng Zhu; Chunzhu Wei; Fei Gao; Chang Liu; Heng Fan (Biotechnology Letters, 2023)

Ameliorative effect of calcium poly(aspartic acid) (PASP-Ca) and calcium poly-γ-glutamic acid (γ-PGA-Ca) on soil acidity in different horizons - Fei Kang; Qilin Lv; Jingbiao Fan; Yun Zhang; Yuling Song; Xueqin Ren; Shuwen Hu (Environmental Science and Pollution Research, 2023)

Biosonar activity of the Indo-Pacific humpback dolphin (Sousa chinensis) near the tunnel section of the world’s longest cross-sea bridge—the Hong Kong-Zhuhai-Macao Bridge—is negatively correlated with underwater noise - Xue An; Pengxiang Duan; Weilun Li; Jing Yuan; Yuwei Chen; Fei Fan; Xiaojun Deng; Yousheng Xiao; Xi Chen; Ding Wang; Zhitao Wang; Kexiong Wang (Frontiers in Marine Science, 2023)
Underwater noise pollution from the world’s longest cross-sea bridge—the Hong Kong-Zhuhai-Macao Bridge (HZMB)—which stretches across the Chinese White Dolphin National Nature Reserve (of the People’s Republic of China, PRC) in the Pearl River Estuary may affect the distribution of local humpback dolphins. In this study, static passive acoustic monitoring was applied to monitor biosonar activity of humpback dolphins and underwater noise adjacent to the tunnel section of the HZMB for more than one year. During the monitoring period, dolphin biosonar signals were detected on 88.5% of days. A significant temporal pattern occurred in dolphin biosonar activity and in anthropogenic noise. Biosonar activity was significantly higher at night than during the day, whereas underwater noise occurred more in the day than at night. Significantly more echolocation signals were detected in winter-spring than in summer-autumn, and highest acoustic activity occurred significantly more during high tide than at other tidal periods. In addition, the negative correlation between elevated underwater noise and dolphin sonar activity in winter suggests that dolphins may avoid noisy waters for short periods, perhaps due to auditory stress, but fish prey movement cannot be ruled out. These findings facilitate understanding activity patterns of humpback dolphins in the Pearl River Estuary and may contribute to conservation efforts.

Discovery of novel HPPD inhibitors: Virtual screening, molecular design, structure modification and biological evaluation - Xin-Yu Leng; Shuang Gao; Yi-Fan Ma; Li-Xia Zhao; Meng Wang; Fei Ye; Ying Fu (Pesticide Biochemistry and Physiology, 2023)

Identification, in silico selection, and mechanism study of novel antioxidant peptides derived from the rice bran protein hydrolysates - Li-kun Ren; Jing Fan; Yang Yang; Xiao-fei Liu; Bing Wang; Xin Bian; Dang-feng Wang; Yue Xu; Bao-xiang Liu; Peng-yu Zhu; Na Zhang (Food Chemistry, 2023)

Incorporation of cinnamon essential oil-loaded Pickering emulsion for improving antimicrobial properties and control release of chitosan/gelatin films - Simin Fan; Debao Wang; Xiangyuan Wen; Xin Li; Fei Fang; Aurore Richel; Naiyu Xiao; Marie-Laure Fauconnier; Chengli Hou; Dequan Zhang (Food Hydrocolloids, 2023)

Comparative study of the negative bending behaviour of corrugated web steel–concrete composite beams using NC, ECC and UHPC - Fangwen Wu; Zhou Fan; Lanqing He; Shuo Liu; Jian Zuo; Fei Yang (Engineering Structures, 2023)

Multifunctional 1,3-benzoxazole-merocyanine-based probe for the ratiometric fluorescence detection of pH/HSO3−/viscosity in mitochondria - Wei-Na Wu; Yu-Fei Song; Xiao-Lei Zhao; Yuan Wang; Yun-Chang Fan; Zhi-Hong Xu; Tony D. James (Chemical Engineering Journal, 2023)

Development of near-infrared lysosomal pH-activatable fluorescent probe for real-time visualization of autophagy progression - Bin Feng; Yeshuo Ma; Fan Zheng; Xueyan Huang; Xueping Feng; Kexiang Zhang; Li Liu; Fei Chen; Wenbin Zeng (Chemical Engineering Journal, 2023)

Purification technology of oil mist in industrial buildings: A review - Yang Yang; Hu Chen; Qingfeng Cao; Mengdan Qiao; Yi Wang; Jia-Ning Fan; Chunhui Yang; Bo Pan; Xin Wang; Fei Wang; Wenchao Ju; Yu Zhou (Building and Environment, 2023)

A green extraction strategy for the detection of antioxidants in food simulants and beverages migrated from plastic packaging materials - Wenjuan Zhu; Pingning Jin; Hongrui Yang; Fei Li; Chen Wang; Tiemei Li; Jing Fan (Food Chemistry, 2023)

Essential role of the Cytochrome P450 2 (CYP2) in the mud crab Scylla paramamosain antioxidant defense and immune responses - Chang-Hong Cheng; Shu-Fei Zhang; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Jian-Jun Jiang; Juan Feng; Zhi-Xun Guo (Fish & Shellfish Immunology, 2023)

Different reoxygenation rates induce different metabolic, apoptotic and immune responses in Golden Pompano (Trachinotus blochii) after hypoxic stress - Tian Jiang; Ye Song Liang; Yue Gu; Fu Cheng Yao; Yi Fan Liu; Kai Xi Zhang; Fei Biao Song; Jun Long Sun; Jian Luo (Fish & Shellfish Immunology, 2023)

The priming effects of plant leachates on dissolved organic matter degradation in water depend on leachate type and water stability - Yuan Cui; Jian-Qiao Meng; Yu-Han Chen; Fei-Fan Shao; Xuan-Zheng Chen; Yu Jin; Ming-Xiang Zhang; Guo Yun-Qian; Fang-Li Luo; Fei-Hai Yu (Environmental Research, 2023)

Gut-liver immune and redox response in hybrid fish (Carassius cuvieri ♀ × Carassius auratus red var. ♂) after gut infection with Aeromonas hydrophila - Ning-Xia Xiong; Wei-Sheng Luo; Xu-Ying Kuang; Fei Wang; Zi-Xuan Fang; Jie Ou; Ming-Zhu Huang; Lan-Fen Fan; Sheng-Wei Luo; Shao-Jun Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Weak base-modulated synthesis of bundle-like carbon superstructures from metal-organic framework for high-performance supercapacitors - Zu-Shun Fan; Yusuf Valentino Kaneti; Silvia Chowdhury; Xiohan Wang; Muhammad Rezaul Karim; Ibrahim Abdullah Alnaser; Fei-Bao Zhang (Chemical Engineering Journal, 2023)

Toward the Scientific Interpretation of Geophysical Well Logs: Typical Misunderstandings and Countermeasures - Jin Lai; Guiwen Wang; Qixuan Fan; Fei Zhao; Xin Zhao; Yuhang Li; Yidi Zhao; Xiaojiao Pang (Surveys in Geophysics, 2023)

A novel method for extraction of paramylon from Euglena gracilis for industrial production - Kaikai Zhang; Minxi Wan; Wenmin Bai; Maolei He; Weiliang Wang; Fei Fan; Jiacai Guo; Tao Yu; Yuanguang Li (Algal Research, 2023)

Novel insights into source apportionment of dissolved organic matter in aquifer affected by anthropogenic groundwater recharge: Applicability of end-member mixing analysis based optical indices - Xu Cao; Wei He; Mengqing Fan; Wei He; Yuanyuan Shi; Tongyan An; Xiaorui Chen; Zhanhao Zhang; Fei Liu; Yi Zhao; Pengpeng Zhou; Cuibai Chen; et al. (Science of The Total Environment, 2023)

A 13 million-year record of Li isotope compositions in island carbonates: Constraints on bulk inorganic carbonate as a global seawater Li isotope archive - Guang-Yi Wei; Feifei Zhang; Yi-Sheng Yin; Yi-Bo Lin; Philip A.E. Pogge von Strandmann; Mengchun Cao; Na Li; Guolin Xiong; Xinran Chen; Caiwei Fan; Changgui Xu; Fei Tan; et al. (Geochimica et Cosmochimica Acta, 2023)

Ratiometric fluorescent immunochromatography for simultaneously detection of two nitrofuran metabolites in seafoods - Yuanyuan Cheng; Xiuying Liu; Min Yang; Fei Xia; Ling Fan; Xue Gao; Xiaofei Sun; Lijie Zhu (Food Chemistry, 2023)

Room-temperature synthesis of nitrogen-rich conjugated microporous polymers for solid-phase extraction of trace synthetic musks - Ye-Fei Fan; Hai-Long Jiang; Xiang-Feng Chen; Na Li; Xiao-Li Wang; Jin-Ming Lin; Ru-Song Zhao (Food Chemistry, 2023)

Differences in texture and digestive properties of different parts in boiled abalone muscles - Man-Man Yu; Ying-Chen Fan; De-Yang Li; Yu-Xin Liu; Peng-Fei Jiang; Da-Yong Zhou; Bei-Wei Zhu (Food Chemistry, 2023)

Houttuynia cordata Thunb. crude extract inactivates Cronobacter sakazakii: Antibacterial components, antibacterial mechanism, and application as a natural disinfectant - Yunhe Chang; Shiwen Xia; Peng Fei; Hongxia Feng; Fangyu Fan; Yu Liu; Likang Qin; Lizhi Ma; Qianhua Song; Yonghong Liu (Food Control, 2023)

Overexpressing SIRT6 can Attenuate the Injury of Intracerebral Hemorrhage by Down-Regulating NF-kB - Jing Cheng; Yan-Qin Fan; Wen-Fei Zhang; Guo Zhang; Kuo Zeng; Zhang Ye; Dan Zhao; Li-Quan Wu; Zhi-Biao Chen (NeuroMolecular Medicine, 2023)

Neuroprotective effect of hyperoside in MPP+/MPTP -induced dopaminergic neurodegeneration - Xing-Jie Xu; Tao Pan; Hui-Jie Fan; Xu Wang; Jie-Zhong Yu; Hai-Fei Zhang; Bao-Guo Xiao; Zhen-Yu Li; Bo Zhang; Cun-Gen Ma; Zhi Chai (Metabolic Brain Disease, 2023)

The influence of Pacific-North American teleconnection on the North Pacific SST anomalies in Wintertime under the global warming - Zheng Chen; Bolan Gan; Fei Huang; Jianping Li; Lixin Wu; Lei Fan; Yina Diao (Climate Dynamics, 2023)
The impact of the enhancing Pacific-North American teleconnection (PNA) on the intensity of the first mode of SST anomalies (SSTa) in wintertime North Pacific [known as the Pacific decadal oscillation (PDO)-like SST pattern] under global warming is studied using reanalysis datasets and 12 selected CMIP5 models. The robust observational result of the PNA one month ahead of the PDO shows that the PNA has a great effect on the PDO-like SSTa. The intensities of PNA and PDO are defined with elimination of the ENSO signals to evaluate the direct impact of PNA on the PDO in the North Pacific under global warming. By comparing RCP8.5 and historical scenario of selected multi-models (PNA enhanced models), future projection illustrates that the PDO intensity will intensify 2.2 times its internal variability. Approximately 67% of the increase in PDO variations is contributed by the PNA-induced SSTa in the future warming scenario of multi-models ensemble mean. Models with stronger intensification of PNA variability tends to have larger magnitude of SSTa response in the North Pacific, which has more contributions to the enhancement of PDO intensity change in a warmer climate. This may shed some light on the projection of PDO variability and the relative role of PNA forcing under the global warming.

A novel stepwise dilution strategy to improve astaxanthin production of Haematococcus pluvialis in outdoor horizontal tubular photobioreactors - Zhongnan Fei; Fei Fan; Junjie Liao; Minxi Wan; Wenmin Bai; Weiliang Wang; Maolei He; Yuanguang Li (Algal Research, 2023)

MUSER and IPS telescopes for solar and space weather observations - Yihua Yan; Wei Wang; Linjie Chen; Fei Liu; Jin Fan; Zhijun Chen; Lihong Geng; Chengming Tan; Suli Ma; Sha Li; Cang Su; Jing Du; et al. (Advances in Space Research, 2023)

The impact of environmental regulations on the performance of regional collaborative innovation—in case of China’s 30 provinces - Huinan Huang; Enni Xu; Fei Fan (Environmental Science and Pollution Research, 2023)

Teleost TRAF7, a protein functions in the host antiviral responses via NF-κB and IRF3/7 mediated signaling - Peng Tian Li; Ying Li; Ying Chen; Jia Xi Zhang; Zi Hao Luo; Yi Fan Zhang; Jing Jiang; Yi Lei Wang; Zi Ping Zhang; Yong Hua Jiang; Peng Fei Zou (Frontiers in Marine Science, 2023)
Tumor necrosis factor receptor-associated factors (TRAFs) play vital roles in tumor necrosis factor receptor (TNF-R) and interleukin-1 receptor/Toll-like receptor (IL-1R/TLR) mediated signaling pathway. However, the role that TRAF7 plays in the host immune responses is largely unknown in comparison to the extensive and in-depth research that has been conducted on other members of the TRAF family. Notably, Lc -TRAF7, a cloned TRAF7 ortholog, was discovered in the large yellow croaker ( Larimichthys crocea ) in the current study, which has an open reading frame (ORF) of 1,962 base pairs and encodes a protein of 653 amino acids (aa). Lc -TRAF7 is consisted of a RING finger domain, a coiled-coil domain, and seven WD40 domains, with the genomic organization consisted of 20 exons and 19 introns. According to the expression analysis, Lc-TRAF7 was presented in a wide range of detected organs and tissues of the healthy fish, and was able to significantly induced by stimulations of poly I:C, LPS, PGN, and Pseudomonas plecoglossicida infection. Subcellular distribution analysis revealed that Lc- TRAF7 was a cytoplasmic protein, with the RING finger and coiled-coil domain function importantly in its subcellular localization. Luciferase assays demonstrated that Lc -TRAF7 overexpression significantly induced the activation of NF-κB, IRF3, IRF7, and IFN1 promoters. In addition, the WD40 domains play a pivotal role in the NF-κB promoter activation, whereas the RING finger and coiled-coil domain were essential in the IRF3, IRF7, and IFN1 promoter activation. Notably, Lc -TRAF7 overexpression could suppress SVCV proliferation in EPC cells, and the expression levels of IRF3 , IRF7 , ISG15, ISG56 , RSAD2 , and TNF-α were up-regulated under Lc -TRAF7 overexpression in LYCMS cells. These findings collectively implied that Lc -TRAF7 may function as an important regulator in the host antiviral responses via the NF-κB as well as IRF3/7 involved signaling pathways.

Differences in lipid accumulation and mobilization in the hepatopancreas and ovary of female mud crab (Scylla paramamosain, Estampador, 1949) during ovarian development - Baojia Chen; Jia Zheng; Cuiying Chen; Kun Wu; Fan Lin; Lijun Ning; Hua Rong; Chuan Chen; Fei Xiao; Haotian Zhang; Xiaobo Wen (Aquaculture, 2023)

Environmental impacts of three Asian dust events in the northern China and the northwestern Pacific in spring 2021 - Tianle Zhang; Mei Zheng; Xiaoguang Sun; Huanhuan Chen; Yuntao Wang; Xuehua Fan; Yubing Pan; Jiannong Quan; Junyi Liu; Yinan Wang; Daren Lyu; Shuangling Chen; et al. (Science of The Total Environment, 2023)

High-consistency proton exchange membrane fuel cells enabled by oxygen-electron mixed-pathway electrodes via digitalization design - Zhiming Bao; Biao Xie; Weizhuo Li; Shenghui Zhong; Linhao Fan; Chasen Tongsh; Fei Gao; Qing Du; Mohamed Benbouzid; Kui Jiao (Science Bulletin, 2023)

The F-box protein OsEBF2 confers the resistance to the brown planthopper (Nilparvata lugens Stål) - Feilong Ma; Zixin Li; Sayi Wang; Kejia Li; Fei Tang; Jingxuan Jia; Qiujin Zhao; Peihua Jing; Wenqing Yang; Congmin Hua; Haifu Han; Jiayin Xu; et al. (Plant Science, 2023)

Theoretical investigation on the inert pair effect of Ga on both the Ga-Ni-Mo-S nanocluster and the direct desulfurization of 4,6-dimethyldibenzothiophene - Fei Fan; Zhiping Chen; Anning Zhou; Zhiyuan Yang; Yating Zhang; Xinxin He; Jie Kang; Wenwu Zhou (Fuel, 2023)

Dual-color aggregation-induced emission nanoparticles for simultaneous lateral flow immunoassay of nitrofuran metabolites in aquatic products - Xiuying Liu; Fei Xia; Shaoen Zhang; Yuanyuan Cheng; Ling Fan; Si Kang; Xue Gao; Xiaofei Sun; Jianrong Li; Xuepeng Li; Lijie Zhu (Food Chemistry, 2023)

Soil ammonium (NH4+) toxicity thresholds for restoration grass species - Huixian Yang; Jun Zhou; Jiasai Fei; Kaidong Ci; Demin Li; Jianbo Fan; Chaoyang Wei; Jiani Liang; Ruizhi Xia; Jing Zhou (Environmental Pollution, 2023)

Improved catalytic activity and stability of Cu/ZnO catalyst by boron oxide modification for low-temperature methanol synthesis - Fei Chen; Jiaming Liang; Fan Wang; Xiaoyu Guo; Weizhe Gao; Yasuharu Kugue; Yingluo He; Guohui Yang; Prasert Reubroycharoen; Tharapong Vitidsant; Noritatsu Tsubaki (Chemical Engineering Journal, 2023)

Design and optimization of a novel Y-Fe-GO magnetic adsorbent for simultaneous removal of tetracycline and arsenic and adsorption mechanisms - Jinsong He; Hui Zheng; Fan Ni; Fei Shen; Min Xu; Dong Tian; Jianmei Zou; Yongjia Lei; Yan He; Yan Liu (Chemical Engineering Journal, 2023)

Prediction and optimization of medium-chain carboxylic acids production from food waste using machine learning models - Fei Long; Joshua Fan; Hong Liu (Bioresource Technology, 2023)

The detection of major clades and new species of Mallocybe (Inocybaceae, Agaricales) from China with elongate cheilocystidia - Jian-Hua Hu; Wen-Jie Yu; Lun-Sha Deng; Yu-Guang Fan; Tolgor Bau; Li-Ping Tang; Wen-Fei Lin; Chun-Ying Deng (Mycological Progress, 2023)

Retraction Note: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2023)

Effects of climate and land‐cover change on the conservation status of gibbons - Li Yang; Tao Chen; Kai‐Chong Shi; Lu Zhang; Ngwe Lwin; Peng‐Fei Fan (Conservation Biology, 2023)
Species shift their distribution in response to climate and land‐cover change, which may result in a spatial mismatch between currently protected areas (PAs) and priority conservation areas (PCAs). We examined the effects of climate and land‐cover change on potential range of gibbons and sought to identify PCAs that would conserve them effectively. We collected global gibbon occurrence points and modeled (ecological niche model) their current and potential 2050s ranges under climate‐change and different land‐cover‐change scenarios. We examined change in range and PA coverage between the current and future ranges of each gibbon species. We applied spatial conservation prioritization to identify the top 30% PCAs for each species. We then determined how much of the PCAs are conserved in each country within the global range of gibbons. On average, 31% (SD 22) of each species’ current range was covered in PAs. PA coverage of the current range of 9 species was p = 0.01, SD 0.01), suggesting that gibbons will benefit from effective management of land cover. PA coverage of future range was

The Environmental Niche of the Tuna Purse Seine Fleet in the Western and Central Pacific Ocean Based on Different Fisheries Data - Shenglong Yang; Linlin Yu; Fei Wang; Tianfei Chen; Yingjie Fei; Shengmao Zhang; Wei Fan (Fishes, 2023)
Understanding the spatial pattern of human fishing activity is very important for fisheries resource monitoring and spatial management. The environmental preferences of tropical tuna purse seine fleet in the Western and Central Pacific Ocean (WCPO) were constructed and compared at different spatial scales based on the fishing effort (FE) data from the available automatic identification system (AIS) and commercial fishery data compiled from the Western and Central Pacific Fisheries Commission (WCPFC), using maximum entropy (MaxEnt) methods. The MaxEnt models were fitted with FE and commercial fishery data and remote sensing environmental data. Our results showed that the area under the curve (AUC) value each month based on the commercial fishery data (1°) and FE at 0.25° and 0.5° spatial scales was greater than 0.8. The AUC values each month based on the FE data at a 1° scale ranged from 0.775 to 0.829. The AUC values based on commercial fishing data at the 1° scale were comparable to the model results based on FE data at the 0.5° scale and inferior to the model results based on FE data at the 0.25° scales. Overall, the sea surface temperature (SST), temperature at 100 metres (T100), oxygen concentration at 100 metres (O100) and total primary production (PP) had the greatest influence on the distribution of the purse seine tuna fleet. The oxygen concentration at 200 metres (O200), distance to shore (DSH), dissolved oxygen (Dox), EKE, mixed layer depth (Mld), sea surface salinity (SSS), salinity at 100 metres (S100) and salinity at 200 metres (S200) had moderate influences, and other environmental variables had little influence. The suitable habitat areas varied in response to environmental conditions. The purse seine tuna fleet was mostly present at locations where the SST, T100, O100, O200 and PP were 28–30 °C, 27–29 °C, 150–200 mmol/m3 and 5–10 mg/m−3, respectively. The MaxEnt models enable the integration of AIS data and high-resolution environmental data from satellite remote sensing to describe the spatiotemporal distribution of the tuna purse seine fishery and the influence of environmental variables on the distribution, and can provide forecasts for fishing ground distributions based on future remote sensing environmental data.

Effects of LED spectrum on circadian rhythmic expression of clock genes and Aanat2 in the brain of juvenile European seabass (Dicentrarchus labrax) - He Ma; Songtao Liu; Pingping Wei; Fan Fei; Jilong Ren; Mingyun Dai; Zhen Ma; Ying Liu (Frontiers in Marine Science, 2023)
The circadian rhythm is a physiological phenomenon that occurs in various organisms with a cycle of about 24 hours. Light is one of the important environmental factors affecting biological rhythm. To clarify whether a shift in light spectrum can influence the circadian expression in fish brain, a total of 175 European seabasses [body weight: 32.5 ± 0.71) g; body length: (13.78 ± 0.35) cm] were exposed to white light (WL), red light (RL), yellow light (YL), green light (GL) or blue light (BL). After 50 days of exposure, circadian expressions of four core clock genes ( Clock, Bmal1, Per2, Cry1 ) and Aanat2 gene in brain were examined. The results showed that the temporal expression patterns of positive clock gens ( Clock and Bmal1 ) showed increases during the scotophase and decreases during the photophase, with peaks near the middle of the darkness. Clock gene expression showed a stable circadian rhythm (R 2 = 0.578-0.824, P =0.000- 0.027) in all light groups while Bmal1 showed circadian rhythm in WL, GL and RL, not in BL and YL. Daily expression patterns of the negative clock genes oscillated in the opposite phase from the positive clock genes, showing increasing mRNA levels during the light, decreases during the dark, and peaks near the shift from night to day, except Per2 in RL and Cry1 in BL. Compared with WL, the acrophases of Clock and Bmal1 were delayed under all light treatments (BL: + 3.7h, +6.73h; RL: +2.4h,+1.35h; YL: + 4.94h, 2.00h; GL: +0.05, +0.16h). Cry1 showed advanced acrophase under all light treatments (BL: -10.74 h, GL: -3.81 h, RL: -3.93 h, YL: -7.56 h) but Per2 showed delayed acrophase in all light treatments (GL: +0.86 h, RL: +10.35 h, YL: +9.62 h), except in BL (-0.43 h). The acrophase of Aanat2 was advanced by all monochromatic light, the Aanat2 level was significantly increased in RL compared with other light treatment. Therefore, the results indicate that RL may regulate the expression of Aanat2 gene by affecting the expression of clock gene in fish brain. Spectrum can affect the biological clock system of fish, and unreasonable spectrum may disturb the rhythm of gene expression of biological clock of fish. Under the irradiation of light spectrum, some clock genes still maintain obvious circadian oscillation, while the rhythm of some clock genes is not obvious and may be destroyed. Our findings suggest a primary role of light spectrum information to the fish brain circadian system.

Hypoxia alters glucose and lipid metabolisms in golden pompano (Trachinotus blochii) - Tian Jiang; Jun Long Sun; Yue Gu; Fu Cheng Yao; Ye Song Liang; Yi Fan Liu; Kai Xi Zhang; Fei Biao Song; Li Zhou; Zhong Wei Wang; Jian Fang Gui; Jian Luo (Aquaculture, 2023)

Graphene quantum dots disturbed the energy homeostasis by influencing lipid metabolism of macrophages - Yan Shao; Xiaoyang Wang; Liting Wang; Youying Huang; Quanfang Wei; Wei Sun; Xiaodan Lai; Fan Yang; Fei Li; Yi Huang (Toxicology, 2023)

Random response analysis of nonlinear structures with inerter system - Fei-Fan Meng; Qingxuan Shi (Soil Dynamics and Earthquake Engineering, 2023)

Catalysts for gaseous organic sulfur removal - Yuxuan Xie; Jiacheng Bao; Xin Song; Xin Sun; Ping Ning; Chi Wang; Fei Wang; Yixing Ma; Maohong Fan; Kai Li (Journal of Hazardous Materials, 2023)

Simple and high-precision DFT-QSPR prediction of enthalpy of combustion for sesquiterpenoid high-energy–density fuels - Hang Yang; Zhi-Jiang Yang; Qi-Fan Yang; Xin-Miao Wei; Yu-Quan Yuan; Liang-Liang Wang; Yan-Fei Hu; Jun-Jie Ding (Fuel, 2023)

Heavy metal-mediated adsorption of antibiotic tetracycline and ciprofloxacin on two microplastics: Insights into the role of complexation - Fei Tong; Di Liu; Zhenhua Zhang; Wei Chen; Guangping Fan; Yan Gao; Xueyuan Gu; Cheng Gu (Environmental Research, 2023)

Accumulated temperature and allocation of photo-thermal resources are key meteorological factors affecting rice cadmium content - Wei Zhou; Fengjun Yan; Yu Fan; Chi Zhang; Fan Yang; Qi Liu; Tao Wang; Bo Li; Yong Chen; Fei Deng; Jianfeng Hu; Xiaolong Lei; et al. (European Journal of Agronomy, 2023)

Direct cytosolic delivery of DNA by creating fast closable holes in the cell membrane - Haili Wang; Wei You; Fan Gao; Lei Zhang; Aizong Shen; Fei Wang; Guang Chen; Xuan Nie; Lei Xia; Wei-Qiang Huang; Wen-Jian Zhang; Long-Hai Wang; et al. (Chemical Engineering Journal, 2023)

Porous Cobalt-nickel phosphides prepared from Al-doped NiCo-LDH precursors for supercapacitor and electrocatalysis applications - Ruonan Liu; Lulu Chen; Fei Mo; Haiyan Song; Guang Yang; Chunxia Chen; Xiaoliang Wu; Yichao Huang; Zhuangjun Fan (Chemical Engineering Journal, 2023)

Honokiol inhibits interleukin-induced angiogenesis in the NSCLC microenvironment through the NF-κB signaling pathway - Xudong Cheng; Fei Wang; Yu Qiao; Ting Chen; Ling Fan; Xikun Shen; Dongwei Yu; Yuyu Huang; Minggang Wei (Chemico-Biological Interactions, 2023)

The dominant driving factors of rocky desertification and their variations in typical mountainous karst areas of southwest China in the context of global change - Bing Guo; Fei Yang; Yewen Fan; Wenqian Zang (CATENA, 2023)

Interaction mechanism between nitrogen conversion and the microbial community in the hydrodynamic heterogeneous interaction zone - Lei Duan; Jinghui Fan; Yike Wang; Yakun Wu; Chenchen Xie; Fei Ye; Jiajia Lv; Ming Mao; Yaqiao Sun (Environmental Science and Pollution Research, 2023)

Association between gestational arsenic exposure and intrauterine growth restriction: the role of folate content - Fei-Xiang Xu; Xu Chen; Heng Zhang; Yi-Jun Fan; Ya-Ping Song; Jin-Wei Lv; Ya-Li Xie; Yichao Huang; Dao-Zhen Chen; Hua Wang; De-Xiang Xu (Environmental Science and Pollution Research, 2022)

Identification of nitrogen pollution sources and transport transformation processes in groundwater of different landforms using C, H, N, and O isotope techniques: an example from the lower Weihe River - Lei Duan; Yakun Wu; Jinghui Fan; Fei Ye; Chenchen Xie; Xinyi Fu; Yaqiao Sun (Environmental Science and Pollution Research, 2022)

The effects of human care on the blowhole and gut microbiotas of two cohabiting dolphin species based on a year-round surveillance - Xiaoling Wan; Jia Li; Renmao Tian; Richard William McLaughlin; Yujiang Hao; Junyi Wu; Zhengyang Wang; Fei Fan; Ding Wang; Jinsong Zheng (Frontiers in Marine Science, 2022)
Understanding the effects of human care on the dynamics of the host-associated microbiota is critical for the health management of dolphins living in an aquarium. Yet this aspect remains relatively unexplored. Here, by utilizing 16S rRNA gene sequencing, we profiled the blowhole and gut bacterial communities of two bottlenose dolphins ( Tursiops truncatus ) and a Chinese white dolphin ( Sousa chinensis ) reared in the same indoor pool, based on year-round surveillance. In addition, we compared these dolphin microbiotas with those previously published datasets from wild dolphins. Our results showed that both the blowhole and the gut of the two dolphin species under human care shared a more similar microbiome than members of the same dolphin species across different habitats (human care vs wild). However, the effects of human care on the dolphin microbiome from the two body sites varied. In the aquarium, bacterial alpha diversities differed significantly between the two body sites, and the seasonal stability of the bacterial community was more evident in the gut than in the blowhole. Additionally, the blowhole bacterial composition and the predicted functional capacity from the two dolphin species showed differences and were less convergent than their gut microbiota over a decade-long cohabitation. Further analyses showed that heterogeneous and homogeneous selections (i.e., deterministic processes) contributed more to the blowhole than to the gut bacterial communities, while a dispersal limitation (i.e., a stochastic process) was more important for the gut microbiota. The present study provides the first comparative evidence that the gut microbiota may be more plastic in response to the human care environment than the blowhole microbiota. This improves our understanding of dolphin health management under human care and helps to predict their microbial responses to environmental changes.

The recombinant subunit vaccine encapsulated by alginate‐chitosan microsphere enhances the immune effect against Micropterus salmoides rhabdovirus - Fei‐Fan Xu; Fu‐Yi Jiang; Guo‐Qing Zhou; Jun‐Yao Xia; Fei Yang; Bin Zhu (Journal of Fish Diseases, 2022)
The disease caused by Micropterus salmoides rhabdovirus (MSRV) has brought substantial economic losses to the largemouth bass aquaculture industry in China. Vaccination was considered as a potential way to prevent and control this disease. As a kind of sustained and controlled release system, alginate and chitosan microspheres (SA‐CS) are widely used in the development of oral vaccination for fish. Here, we prepared a king of alginate‐chitosan composite microsphere to encapsulate the second segment of MSRV glycoprotein (G2 protein) and then evaluated the immune effect of the microsphere vaccine on largemouth bass. Largemouth bass were vaccinated via intragastric immunization by different treatments (PBS, SA‐CS, G2 and SA‐CS‐G2). The results showed that a stronger immune response including serum antibody levels, immune‐related physiological indexes (acid phosphatase, alkaline phosphatase, superoxide dismutase and total antioxidant capacity) and the expression of immune‐related gene ( IgM、IL‐8、IL‐1β、CD4、TGF‐β、TNF‐α ) can be induced obviously with SA‐CS‐G2 groups compared with G2 groups when fish were vaccinated. Furthermore, fish were injected with a lethal dose of MSRV after immunization for 28 days, and the highest relative percentage survival (54.8%) was observed in SA‐CS‐G2 group (40 μg per fish), which is significantly higher than that of G2 group (25.8%). This study showed that alginate‐chitosan microspheres as the vaccine carrier can effectively improve the immune effect of oral vaccination and induce better immune protection effect against MSRV infection.

An “Eddy β-Spiral” mechanism for vertical velocity dipole patterns of isolated oceanic mesoscale eddies - Yinglin Hou; Fei-Fei Jin; Shan Gao; Jun Zhao; Kai Liu; Tangdong Qu; Fan Wang (Frontiers in Marine Science, 2022)
Oceanic eddies accompanied by a significant vertical velocity ( w ) are known to be of great importance for the vertical transport of various climatically, biologically or biogeochemically relevant properties. Using quasi-geostrophic w -thinking to extend the classic “ β -spiral” w -theory for gyre circulations to isolated and nearly symmetric oceanic mesoscale eddies, we propose that their w motion will be dominated by a strong east-west dipole pattern with deep ocean penetrations. Contrasting numerical simulations of idealized isolated eddies together with w -equation diagnostics confirm that the w -dipole is indeed dominated by the “eddy β -spiral” mechanism in the β -plane simulation, whereas this w -dipole expectedly disappears in the f -plane simulation. Analyses of relatively isolated warm and cold eddy examples show good agreement with the proposed mechanism. Our studies further clarify eddy vertical motions, have implications for ocean mixing and vertical transport, and inspire further studies.

Two new monoterpenoid indole alkaloids from Mappianthus iodoides stems - Lan Zhou; Pian-Chou Gongpan; Qing-Fei Fan; Zhi Na; Feng-Mei Huang; Kai-Long Ji; Qi-Shi Song (Natural Product Research, 2022)

Physical-mechanical properties of microbially induced calcite precipitation-treated loess and treatment mechanism - Hao-nan Zhang; Cang-qin Jia; Gui-he Wang; Fei Su; Yong-shuai Sun; Chang-yi Fan (Journal of Mountain Science, 2022)

A real-time passive acoustic monitoring system to detect Yangtze finless porpoise clicks in Ganjiang River, China - Weilun Li; Jiansong Qiu; Peiyu Lei; Xiaohong Chen; Fei Fan; Xiaojun Deng; Yingen Dai; Yanqing Deng; Kexiong Wang; Zhigang Mei (Frontiers in Marine Science, 2022)
Phocoenidae live in fresh, coastal waters where they often share a significant portion of their habitat with humans. As a result, local activities (e.g., coastal fisheries and shipments) cause underwater noise pollution and threaten their ecosystem. To better conserve the habitat of porpoises, we aimed to study their activities in these waters by recording their echolocation clicks using a passive acoustic monitoring (PAM) system. However, because the off-line PAM instruments were often used in the past that need to be periodically deployed and recovered, data acquisition is typically obtained and analyzed in batches, rather than in real-time. A real-time PAM detection system would help minimize the impact of underwater noise on approaching porpoises. Furthermore, issues of bad quality data–with gaps due to loss or damage of the off-line PAM instruments–could be avoided with a real-time detection system. Therefore, in this study, we developed the Real-time Porpoise Click Detector-II (RPCD-II), equipped with a digital hydrophone, main memory (2 TB storage), a central processing unit, and a wireless transmission module. We deployed the RPCD-II under a docked fishing vessel at the Ganjiang River in Yangzi Zhou Town Fisheries Village, Nanchang City (8–9 December 2021), where it recorded signals of Yangtze finless porpoise and produced a real-time report. To validate the results of RPCD-II, another underwater sound recorder, the SoundTrap 300HF (ST), was also set up (as a control device) under the docked fishing vessel. Both devices recorded consistent results of 9330 clicks, further demonstrating RPCD-II’s ability for the real-time detection of Yangtze finless porpoise in the field.

Responses of absorptive root and mycorrhizal colonization of Chinese fir (Cunninghamia lanceolata) to varied environmental conditions - Ying-Chun Liao; Hou-Bao Fan; Liang Li; Xiao-Hua Wei; Hui-Min Wang; Hong-Lang Duan; Wen-Fei Liu; Jia-Li Liu (Plant Ecology, 2022)

Monitoring glaciers in the Chenab basin with SBAS InSAR technology - Yue-kai Ding; Rui Liu; Yi-fei Fan; Ling-xiang Zhou; Qin Ji; Hong Zhang; Zuo-lin Xiao (Journal of Mountain Science, 2022)

Soil causes gut microbiota to flourish and total serum IgE levels to decrease in mice - Dongrui Zhou; Na Li; Fan Yang; Honglin Zhang; Zhimao Bai; Yangyang Dong; Mengjie Li; Wenyong Zhu; Zhongjie Fei; Pengfeng Xiao; Xiao Sun; Zuhong Lu (Environmental Microbiology, 2022)
Summary Traditional farm environments induce protection from allergic diseases. In this study, farm environmental factors were classified into three categories, environmental microbes, soil, and organic matter. To explore the impact of soil and environmental microorganisms on gut microbiota and immune function, mice were fed sterilized soil and inhaling microbes, soil microbes, or non‐sterilized soil. Metagenomic sequencing results showed the intake of sterile soil, that is, inhaling a small amount of soil microbes in the air increased gut microbial diversity and the abundance of type III secretion system (T3SS) genes, and decreased serum immune IgE levels induced by 2‐4‐dinitrofluorobenzene (DNFB). The intake of soil microbes increased the abundance of genes involved in the metabolism of short‐chain fatty acids and amino acid biosynthesis. Meanwhile, the intake of soil increased gut microbial diversity, the abundance of T3SS genes and related infectious elements, and genes associated with the metabolism of short‐chain fatty acids and amino acid biosynthesis, and decreased serum IgE levels. Therefore, soil may be useful as a potential ‘prebiotic’ promoting the reproduction and growth of some intestinal microorganisms that harbour bacterial secretion system genes, especially those of T3SS, whose abundance was positively and significantly correlated with innate immune function of mice.

Feed types affect the growth, nutrient utilization, digestive capabilities, and endocrine functions of Megalobrama amblycephala: a comparative study between pelleted and extruded feed - Chao-Fan He; Xiang-Fei Li; Guang-Zhen Jiang; Ling Zhang; Miao Sun; Ya-Ping Ge; Wei-Liang Chen; Wen-Bin Liu (Fish Physiology and Biochemistry, 2022)

Can collaborative innovation constrain ecological footprint? Empirical evidence from Guangdong-Hong Kong-Macao Greater Bay Area, China - Xiaojun You; Qixiang Li; Kyle M. Monahan; Fei Fan; Haiqian Ke; Na Hong (Environmental Science and Pollution Research, 2022)

The Impact of Economic Development of the Guangdong-Hongkong-Macao Greater Bay Area on Air Pollution: Investigation Based on Remote Sensing Data of Nighttime Lights and Air Pollution - Xiaole Ji; Shaoxing Li; Na Jiang; Fei Wang; Liya Fan; Xiao Niu (Frontiers in Marine Science, 2022)
Whether the Guangdong-Hongkong-Macao Greater Bay Area (GBA) can achieve the goal of environmental protection at the same time as its rapid economic development is an important issue that deserves attention. In this paper, we obtained remote sensing data on air pollution including CO, NO 2 , SO 2 , PM 10 , PM 2.5 , and nighttime light data. We combined the remote sensing data with county-level economic statistics to study economic development and air pollution in the Guangdong-Hongkong-Macao GBA. Our research showed that the economic development in the Guangdong-Hongkong-Macao GBA significantly increased the emissions of NO 2 , PM 10 , and PM 2.5 and did not have significant effects on CO and SO 2 . We constructed an emission intensity indicator of pollutants per unit of luminance. We found that the unit emission intensity of four categories of pollutants, PM 10 , PM 2.5 , SO 2 , and CO, showed a significant decreasing trend in line with economic development. The emission intensity of NO 2 showed a trend of first decreasing and then increasing. The conclusion of this research illustrates that the emission intensity of pollutants per unit of luminosity in the Guangdong-Hongkong-Macao GBA is continuously reducing. The emission of pollutants will gradually change from slow growth to zero growth. However, the emission of NO 2 pollution should be an area of focus in achieving the dual goals of economic development and environmental protection.

Microbial composition and nitrogen removal pathways in a novel sequencing batch reactor integrated with semi-fixed biofilm carrier: evidence from a pilot study for low- and high-strength sewage treatment - Peng-fei Chen; Rui-jian Zhang; Zhi-li Du; Guang-hua Wang; Hao-tao Dong; Bin Cui; Ru-pei Fan; Lu-xin Li; Qian-bin Wang; Ying-shi Liu; Zhi-min Sun (Environmental Science and Pollution Research, 2022)

Characteristics and influencing factors of frontal upwelling in the Yellow Sea in summer - Fan Sun; Fei Yu; Guangcheng Si; Jianfeng Wang; Anqi Xu; Jun Pan; Ying Tang (Acta Oceanologica Sinica, 2022)

Behaviour Impact Analysis of Tuna Purse Seiners in the Western and Central Pacific Based on the BRT and GAM Models - Shenglong Yang; Han Zhang; Wei Fan; Huimin Shi; Yingjie Fei; Sanling Yuan (Frontiers in Marine Science, 2022)
Understanding the spatial pattern of human fishing activity is very important for fisheries resource monitoring and spatial management. To understand the spatial distribution of tuna purse seiner operations in the western and central Pacific Ocean and its relationship with the marine environment, this paper uses the AIS data of the western and central Pacific Tuna purse seiners from 2015 to 2020 to excavate spatial fishing effort information, which is combined with 24 marine environmental factors in the same period, including sea surface and subsurface levels using the boosted regression trees (BRT) model and general additive model (GAM) to construct the nonlinear relationship between the spatial distribution of fishing effort and marine ecological environmental factors and to discuss and analyse the niche of tuna purse seiners in the high seas. The results show that the average score of cv-AUC (cross-validated area under the curve) obtained by the BRT model training reaches 0.93, the average accuracy rate is 0.84, and the explained deviance is 43%; the average score of AUC (area under the curve) obtained by the GAM model training reaches 0.81, the average accuracy rate is 0.77, and the explained deviance is 34%. The results of BRT prior to GAM model. Using the BRT model for prediction, the results show that the average cv-AUC score for forecasting fishing effort in 2020 reaches 0.83, and the average accuracy rate of overall classification reaches 0.77. The results of factor analysis show that the water temperature at 100 m depth and longitude are the most important factors affecting the fishing effort of tuna purse seiners, and their contribution rates to the fishing effort of vessels are 12.38% and 9.76%, respectively, followed by sea surface temperature, latitude and DSH. The contribution to the fishing effort of tuna purse seiners was also large, accounting for 9.57%, 8.75%, and 7.11%, respectively; the 100-meter-deep chlorophyll and temperature gradient value contributed the least, 1.44% and 1.16%, respectively; tuna purse seiners are more likely to operate in the 100-metre water temperature of 25-29°C and sea surface temperature of 29-31°C. In terms of space, tuna purse seiners are more likely to operate in the 5°S-5°N latitudinal region and near the western sea area of 180°E. It is predicted that the modelled fishing effort of fishing vessels in 2020 and the actual fishing effort of fishing vessels have a relatively good spatial distribution. Research helps to understand the environmental impact of changes in the spatial distribution of tuna purse seiners and provides support for the management of tuna purse seine vessels in the western and central Pacific.

Geophysical Well-Log Evaluation in the Era of Unconventional Hydrocarbon Resources: A Review on Current Status and Prospects - Jin Lai; Guiwen Wang; Qixuan Fan; Xiaojiao Pang; Hongbin Li; Fei Zhao; Yuhang Li; Xin Zhao; Yidi Zhao; Yuyue Huang; Meng Bao; Ziqiang Qin; et al. (Surveys in Geophysics, 2022)

Controlling average number of photons received per biomass to promote the growth of Synechocystis sp. PPC 6803 - Jiangong Zhang; Fei Fan; Tao Yu; Jianpei Chen; Minxi Wan; Yuanguang Li (Biotechnology Letters, 2022)

Anti-hyperglycaemic effect of labdane diterpenes isolated from the rhizome of Amomum maximum Roxb., an edible plant in Southwest China - Chuan-Li Lu; Li-Ning Wang; Ya-Jun Li; Qing-Fei Fan; Qing-Hua Huang; Jun-Jia Chen (Natural Product Research, 2022)

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

Rapid LC–MS/MS detection of different carbapenemase types in carbapenemase-producing Enterobacterales - Gen Li; Zhihan Ye; Wenyan Zhang; Nianzhen Chen; Yangqin Ye; Yuchao Wang; Fei Wu; Keli Wang; Lieying Fan (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Relationship between the Spatial and Temporal Distribution of Squid-Jigging Vessels Operations and Marine Environment in the North Pacific Ocean - Yingjie Fei; Shenglong Yang; Wei Fan; Huimin Shi; Han Zhang; Sanling Yuan (Journal of Marine Science and Engineering, 2022)
Information and understanding of fishing activities at sea is important to fisheries science, public authorities and policy-makers. To understand the spatial–temporal distribution characteristics of squid-jigging vessels and how the marine environment affects the distribution of squid-jigging vessels in the North Pacific Ocean, operation behavior of the squid-jigging vessels was analysed by using spatial–temporal factors and marine environmental factors. The fishing effort (FE) information was calculated based on automatic identification system (AIS) data of squid-jigging fishing vessels in the North Pacific Ocean from July to November in 2017 to 2020, and the overlay maps of the spatial distribution of environmental factors and fishing effort were plotted together with four environmental variables (sea surface temperature (SST), sea surface height (SSH), sea surface salinity (SSS), and concentration of chlorophyll-a (Chla)). A generalized additive model (GAM) was used to investigate the nonlinear influence of the marine environment on squid-jigging fishing vessel activity in the North Pacific Ocean. The results show that fishing effort increased from July to August and then decreased from September to November. The fishing effort was highest in August. The intensity of the fishing effort suggests squid-jigging vessel operations had significant seasonal variations. The overlay maps suggest that the fishing effort of squid-jigging vessels was mainly located in areas where SST was between 10∘C and 20∘C, SSH was between −0.3m and 0.2m, SSS was between 32×10−3 and 34×10−3, and Chla was between 0.1mg·m−3 and 0.4mg·m−3. The generalized additive model indicated evidence of nonlinear relationships between fishing effort and the three environmental factors. The favorable ranges of SST, SSH, SSS and Chla for fishing effort were 15∘C∼18∘C, 0∼0.2m, 33×10−3∼34×10−3 and 0.2mg·m−3∼0.4mg·m−3, respectively. Moreover, the area beneficial to fishing effort was in 41∘N∼44∘N, 152∘E∼165∘E.

The solar wind plasma upstream of Mars observed by Tianwen-1: Comparison with Mars Express and MAVEN - Kai Fan; Limei Yan; Yong Wei; Aibing Zhang; Linggao Kong; Markus Fränz; Fei He; Lihui Chai; Chongjing Yuan; Yuqi Wang; Jun Zhong; Zhaojin Rong; et al. (Science China Earth Sciences, 2022)

Genomic analysis of Acinetobacter phage BUCT629, a newly isolated member of the genus Obolenskvirus - Ke Han; Yinuo Zhu; Fei Li; Mengzhe Li; Xiaoping An; Lihua Song; Huahao Fan; Yigang Tong (Archives of Virology, 2022)

Middle Triassic volcanic rocks from the Gangdese belt, southern Tibet: petrogenesis and implications for Tethys tectonic evolution - Jingui Wang; Fan Yang; M. Santosh; Xinquan Zhang; Wentong Wei; Shaopeng Zhuan; Juquan Zhang; Chao Chen; Shuo Wang; Xinpeng Yang; Fei Xue (International Geology Review, 2022)

Vermicompost Application Enhances Halophyte Suaeda salsa Performance and Improves Coastal Saline Soil Quality - Jing-Fang Cai; Xuan-Shao Liu; Kai Sun; Fan Jiang; Ming-Xiang Zhang; Hong-Li Li; Fei-Hai Yu (Journal of Soil Science and Plant Nutrition, 2022)

Delineating the Decussating Dentato-rubro-thalamic Tract and Its Connections in Humans Using Diffusion Spectrum Imaging Techniques - Si-Qi Ou; Peng-Hu Wei; Xiao-Tong Fan; Yi-He Wang; Fei Meng; Mu-Yang Li; Yong-Zhi Shan; Guo-Guang Zhao (The Cerebellum, 2022)

Will the artificial populations be sustainable? A genetic assessment on Caragana korshinskii afforestation in the semiarid regions of North China - Xiaoyue Yin; Chaoju Qian; Xia Yan; Tingzhou Fang; Xingke Fan; Shanshan Zhou; Xiao-Fei Ma (European Journal of Forest Research, 2022)

Taxonomical and functional bacterial community selection in the rhizosphere of the rice genotypes with different nitrogen use efficiencies - Wei Chen; Yan Gao; Jie Yang; Fangjun Fan; Weiguo Zhang; Jiangye Li; Cong Zhou; Gaoling Shi; Fei Tong; Guangping Fan (Plant and Soil, 2022)

Effect of Sodium Salicylate on Calcium Currents and Exocytosis in Cochlear Inner Hair Cells: Implications for Tinnitus Generation - Ting Fan; Meng-Ya Xiang; Ruo-Qiao Zhou; Wen Li; Li-Qin Wang; Peng-Fei Guan; Geng-Lin Li; Yun-Feng Wang; Jian Li (Neuroscience Bulletin, 2022)

Retraction Note to: Revisiting the male genetic landscape of China: a multi-center study of almost 38,000 Y-STR haplotypes - Michael Nothnagel; Guangyao Fan; Fei Guo; Yongfeng He; Yiping Hou; Shengping Hu; Jiang Huang; Xianhua Jiang; Wook Kim; Kicheol Kim; Chengtao Li; Hui Li; et al. (Human Genetics, 2022)

Paracoccus shandongensis sp. nov., Isolated from Activated Sludge - Xiao-Fan Gong; Fang Wang; Dong Meng; Yu-Ling Liu; Peng-Fei Gu; Xiang-Yu Fan; Zhao-Song Huang; Zong-Jun Du; Qiang Li (Current Microbiology, 2022)

Mesorhizobium xinjiangense sp. nov., isolated from rhizosphere soil of Alhagi sparsifolia - Dong Meng; Yu-Ling Liu; Jun-Jie Zhang; Peng-Fei Gu; Xiang-Yu Fan; Zhao-Song Huang; Yan Ji; Heng Meng; Zong-Jun Du; Wei-Min Li; Qiang Li (Archives of Microbiology, 2022)

A Review of Methods for Ship Detection with Electro-Optical Images in Marine Environments - Liqian Wang; Shuzhen Fan; Yunxia Liu; Yongfu Li; Cheng Fei; Junliang Liu; Bohan Liu; Yakui Dong; Zhaojun Liu; Xian Zhao (Journal of Marine Science and Engineering, 2021)
The ocean connects all continents and is an important space for human activities. Ship detection with electro-optical images has shown great potential due to the abundant imaging spectrum and, hence, strongly supports human activities in the ocean. A suitable imaging spectrum can obtain effective images in complex marine environments, which is the premise of ship detection. This paper provides an overview of ship detection methods with electro-optical images in marine environments. Ship detection methods with sea–sky backgrounds include traditional and deep learning methods. Traditional ship detection methods comprise the following steps: preprocessing, sea–sky line (SSL) detection, region of interest (ROI) extraction, and identification. The use of deep learning is promising in ship detection; however, it requires a large amount of labeled data to build a robust model, and its targeted optimization for ship detection in marine environments is not sufficient.

Ferroptosis inhibitory constituents from the fruits of Cullen corylifolium - Aftab Yaseen; Fan Yang; Xia Zhang; Fu Li; Bin Chen; Ahmed Hassan Ibrahim Faraag; Ming-Kui Wang; Xiao-Fei Shen; Lun Wang (Natural Product Research, 2021)

The role of earthquake-induced landslides in erosion and weathering from active mountain ranges: Progress and perspectives - Zhangdong Jin; Robert G. Hilton; A. Joshua West; Gen K. Li; Fei Zhang; Jin Wang; Gaojun Li; Xuanmei Fan; Meng-Long Hsieh (Science China Earth Sciences, 2021)

Evaluation of the antiviral activity of naringenin, a major constituent of Typha angustifolia , against white spot syndrome virus in crayfish Procambarus clarkii - Zhong‐Chen Sun; Cheng Chen; Fei‐Fan Xu; Bing‐Ke Li; Jing‐Lei Shen; Tao Wang; Hai‐Feng Jiang; Gao‐Xue Wang (Journal of Fish Diseases, 2021)
White spot syndrome virus (WSSV) is a serious pathogen threatening global crustacean aquaculture with no commercially available drugs. Herbal medicines widely used in antiviral research offer a rich reserve for drug discovery. Here, we investigated the inhibitory activity of 13 herbal medicines against WSSV in crayfish Procambarus clarkii and discovered that naringenin (NAR) has potent anti‐WSSV activity. In the preliminary screening, the extracts of Typha angustifolia displayed the highest inhibitory activity on WSSV replication (84.62%, 100 mg/kg). Further, NAR, the main active compound of T. angustifolia, showed a much higher inhibition rate (92.85%, 50 mg/kg). NAR repressed WSSV proliferation followed a dose‐dependent manner and significantly improved the survival of WSSV‐challenged crayfish. Moreover, pre‐ or post‐treatment of NAR displayed a comparable inhibition on the viral loads. NAR decreased the transcriptional levels of vital genes in viral life cycle, particularly for the immediately early‐stage gene ie1 . Further results showed that NAR could decrease the STAT gene expression to block ie1 transcription. Besides, NAR modulated immune‐related gene Hsp70 , antioxidant ( cMnSOD, mMnSOD, CAT, GST ), anti‐inflammatory ( COX‐1 , COX‐2 ) and pro‐apoptosis‐related factors (Bax and BI‐1) to inhibit WSSV replication. Overall, these results suggest that NAR may have the potential to be developed as preventive or therapeutic agent against WSSV.

Vertical Fine-Scale Distribution of Calanus sinicus in the Yellow Sea Cold Water Mass During the Over-Summering Process - Jun Pan; Fangping Cheng; Fei Yu; Yongqiang Shi; Fan Sun; Guangcheng Si; Chuanjie Wei; Xinyuan Diao; Yongfang Zhao (Frontiers in Marine Science, 2021)
Calanus sinicus , a temperate copepod with a lethal temperature >27°C, is one of the key species in Chinese coastal marine ecosystems. The C. sinicus population increases in spring and declines in early summer annually due to increasing water temperature. Numerous C. sinicus individuals then congregate in the Yellow Sea Cold Water Mass (YSCWM) and remain under the thermocline from early summer to early autumn. Development and reproduction is halted in this cold and foodless bottom water and they avoid ascending to the hot surface water, which is regarded as an over-summering strategy. Based on discrete water sampling approaches, previous studies demonstrated that higher chlorophyll a (Chl a) levels appeared in the mixed hot surface water layer; however, the subsurface chlorophyll a maximum layer (SCML) has seldom been described. In the present study, various probes and a visual plankton recorder (VPR) were used to determine the fine vertical distributions of environmental factors and C. sinicus . VPR observations showed the ecological responses in fine scale and indicated that few C. sinicus individuals ascend at night, the main population preferred to remain below the SCML all day long. The results demonstrated that a constant thin SCML existed in the YSCWM area, and that the SCML location coincided with or was beneath the thermocline and halocline layers, where the temperature was suitable for C. sinicus . The relationship between abundance and Chl a, showed the diel vertical migration trend of C. sinicus to feed at night in the YSCWM area. In addition to temperature as a main influencing factor, dissolved oxygen concentrations and column depth were also influencing factors. Therefore, in addition to avoiding high surface temperature, energy supplement may be an important driving force confining the diel vertical migration of C. sinicus in the Yellow Sea in summer.

Magnetic Resonance Imaging-Guided and Navigated Individualized Repetitive Transcranial Magnetic Stimulation for Cognitive Impairment in Schizophrenia - Xu-Sha Wu; Tian-Cai Yan; Xian-Yang Wang; Yang Cao; Xiao-Fan Liu; Yu-Fei Fu; Lin Wu; Yin-Chuan Jin; Hong Yin; Long-Biao Cui (Neuroscience Bulletin, 2021)

Study on the comprehensive utilization of solid residues of Flammulina velutipes and vinegar and their application as feed in Eisenia fetida earthworm culture - Tong Xu; Fan Fei; Yangyang Ding; Yongchao Liu; Guanghua Mao; Liuqing Yang; Ting Zhao; Taotao Liao; Weiwei Feng; Xiangyang Wu (Environmental Science and Pollution Research, 2021)

The hidden mediating role of innovation efficiency in coordinating development of economy and ecological environment: evidence from 283 Chinese cities - Song Wang; Jiexin Wang; Fei Fan (Environmental Science and Pollution Research, 2021)

Has ridesourcing reduced haze? An analysis using the Didi app - Xueli Wang; Song Wang; Lei Wang; Fei Fan (Environmental Science and Pollution Research, 2021)

Organic acid metabolites involved in local adaptation to altitudinal gradient in Agriophyllum squarrosum, a desert medicinal plant - Shanshan Zhou; Jian Yang; Chaoju Qian; Xiaoyue Yin; Xia Yan; Xingke Fan; Tingzhou Fang; Yuan Gao; Yuxiao Chang; Xiao-Fei Ma (Journal of Plant Research, 2021)

Two-dimensional dynamic walking stability of elderly females with a history of falls - Xing GAO; Fei SHEN; Li WANG; Yingnan MA; Haijun NIU; Yubo FAN (Medical & Biological Engineering & Computing, 2021)

Porcine circovirus type 2 (PCV2) infection in Hebei Province from 2016 to 2019: a retrospective study - Lei Han; Guang-fu Yuan; Shao-jie Chen; Fei Dai; Lin-shan Hou; Jing-hui Fan; Yu-zhu Zuo (Archives of Virology, 2021)

Paracoccus binzhouensis sp. nov., isolated from activated sludge - Fang Wang; Xiao-Fan Gong; Dong Meng; Yu-Ling Liu; Peng-Fei Gu; Xiang-Yu Fan; Zhao-Song Huang; Zong-Jun Du; Qiang Li (Archives of Microbiology, 2021)

Coupling urban 3‐D information and circuit theory to advance the development of urban ecological networks - Fanhua Kong; Ding Wang; Haiwei Yin; Iryna Dronova; Fan Fei; Jiayu Chen; Yingxia Pu; Manchun Li (Conservation Biology, 2021)
Ongoing, rapid urban growth accompanied by habitat fragmentation and loss challenges biodiversity conservation and leads to decreases in ecosystem services. Application of the concept of ecological networks in the preservation and restoration of connections among isolated patches of natural areas is a powerful conservation strategy. However, previous approaches often failed to objectively consider the impacts of complex 3‐D city environments on ecological niches. We used airborne lidar‐derived information on the 3‐D structure of the built environment and vegetation and detailed land use and cover data to characterize habitat quality, niche diversity, and human disturbance and to predict habitat connectivity among 38 identified habitat core areas (HCAs) in Nanjing, China. We used circuit theory and Linkage Mapper to create a landscape resistance layer, simulate habitat connectivity, and identify and prioritize important corridors. We mapped 64 links by using current flow centrality to evaluate each HCA's contribution and the links that facilitate intact connectivity. Values were highest for HCA links located in the west, south, and northeast of the study area, where natural forests with complex 3‐D structures predominate. Two smaller HCA areas had high centrality scores relative to their extents, which means they could act as important stepping stones in connectivity planning. The mapped pinch‐point regions had narrow and fragile links among the HCAs, suggesting they require special protection. The barriers with the highest impact scores were mainly located at the HCA connections to Purple Mountain and, based on these high scores, are more likely to indicate important locations that can be restored to improve potential connections. Our novel framework allowed us to sufficiently convey spatially explicit information to identify targets for habitat restoration and potential pathways for species movement and dispersal. Such information is critical for assessing existing or potential habitats and corridors and developing strategic plans to balance habitat conservation and other land uses based on scientifically informed connectivity planning and implementation.

Coupling loss characteristics of N-P-C through runoff and sediment in the hilly region of SE China under simulated rainfall - Longzhou Deng; Tianyu Sun; Kai Fei; Liping Zhang; Xiaojuan Fan; Yanhong Wu; Liang Ni; Rui Sun (Environmental Science and Pollution Research, 2021)

Microwave irradiation coupled with zero-valent iron that enhances the composite geopolymerization of chromite ore processing residue and its mechanisms - Tao Huang; Zhen-Xing Cao; Xin-Chuan Fan; Jun-Xun Jin; Chun-Hai Yang; Long-Fei Liu; Shu-Wen Zhang (Environmental Science and Pollution Research, 2021)

Molecular mechanisms of heavy metals resistance of Stenotrophomonas rhizophila JC1 by whole genome sequencing - Shang-Chen Sun; Ji-Xiang Chen; Yong-Gang Wang; Fei-Fan Leng; Jian Zhao; Kai Chen; Qing-Chun Zhang (Archives of Microbiology, 2021)

Administration of a recombinant ALDH7A1 (rA7) indicates potential regulation of the metabolite and immunology pathways in Atlantic salmon infected with Aeromonas salmonicida - Xiaohao Li; Kunpeng Fan; Yafang Liu; Ying Liu; Peng‐fei Liu (Journal of Fish Diseases, 2021)
The bacterium Aeromonas salmonicida is the pathogen responsible for furunculosis, which is a serious disease of salmonids. This disease has a significant economic impact on the economic benefits of the global salmon farming industry. However, the pathogenesis of this disease in fish is still unknown. Members of the aldehyde dehydrogenase gene (ALDH) superfamily play a key role in the enzyme detoxification of endogenous and exogenous aldehydes. In this study, we obtained a recombinant aldehyde dehydrogenase 7A1 (ALDH7A1) protein to find its functions on Atlantic salmon infected by A. salmonicida . The transcriptional response in the liver of Atlantic salmon ( Salmo salar ) with differing levels of A. salmonicida infection was analysed and compared in order to reveal mechanisms by which ALDH7A1 may confer infection resistance. With the addition of ALDH7A1 protein, it was found that a total of 13,369 genes were annotated with one or more KEGG and localized to 360 KEGG pathways in the high concentration infection group. The differential expression genes were more enriched in immune signalling pathways such as the Toll‐like receptor signalling pathway, NF‐kappa B signalling pathway and TNF signalling pathway. On the other hand, at low concentrations of infection, KEGG enriched a smaller number of differential expression genes. However, these differential genes were more concentrated in immune signalling pathways such as the PI3K‐Akt signalling pathway, JAK‐STAT signalling pathway and complement and coagulation cascades. In addition, several known immune‐related genes including HSP90α , HSP70 , DNA damage‐inducible transcript 4 , integrin alpha 5 and microtubule‐associated protein 2 were among the differentially expressed transcripts. These data provide the first insights into the host–ALDH7A1 vaccine interactome. The results of this study contribute to identifying the potential resistance mechanisms of Atlantic salmon to A. salmonicida infection and determining future treatment strategies.

Behavior and mechanism of different fraction lead leach with several typical sulfate lixiviants in the weathered crust elution-deposited rare earth ore - Jie Tang; Jiyang Qiao; Qiang Xue; Fei Liu; Xin Fan; Siwen Liu; Yuanying Huang (Environmental Science and Pollution Research, 2021)

The effect of organic solvent washing on the structure of hydrochar-based dissolved organic matters and its potential environmental toxicity - Guangping Fan; Fei Tong; Weiguo Zhang; Gaoling Shi; Wei Chen; Lizhu Liu; Jiangye Li; Zhenhua Zhang; Yan Gao (Environmental Science and Pollution Research, 2021)

Effects of high temperature on the mechanical behaviors of sandstone under true-triaxial unloading conditions - Fan Xiao; Deyi Jiang; Fei Wu; Quanle Zou; Jie Chen; Bo Chen; Zhongguang Sun (Bulletin of Engineering Geology and the Environment, 2021)

Comparative transcriptome analysis to identify genes involved in terpenoid biosynthesis in Agriophyllum squarrosum, a folk medicinal herb native to Asian temperature deserts - Xiaoyue Yin; Xia Yan; Chaoju Qian; Shanshan Zhou; Tingzhou Fang; Xingke Fan; Yuan Gao; Yuxiao Chang; Jian Yang; Xiao-Fei Ma (Plant Biotechnology Reports, 2021)

Cytotoxic meroterpenoids from the marine sponge Dactylospongia elegans - Hao-Bing Yu; Zi-Fei Yin; Bin-Bin Gu; Jian-Peng Zhang; Shu-Ping Wang; Fan Yang; Hou-Wen Lin (Natural Product Research, 2021)

Study on the oxidation and acidification characteristics of the sulfur-containing tailings material - Wenzhao Chen; Gang Wang; Xiqi Liu; Jiaqing Fan; Mingnan Xu; Botao Fei; Hui Long (Arabian Journal of Geosciences, 2021)

Chelativorans alearense sp. nov., A Novel Bacterial Species Isolated From Soil in Alear, China - Dong Meng; Yu-Ling Liu; Peng-Fei Gu; Xiang-Yu Fan; Zhao-Song Huang; Yan Ji; Wei-Min Li; Zong-Jun Du; Qiang Li (Current Microbiology, 2021)

Chelativorans xinjiangense sp. nov., a novel bacterial species isolated from soil in Xinjiang, China - Dong Meng; Yu-Ling Liu; Peng-Fei Gu; Xiang-Yu Fan; Zhao-Song Huang; Yan Ji; Wei-Min Li; Zong-Jun Du; Qiang Li (Archives of Microbiology, 2021)

Propylenella binzhouense gen. nov., sp. nov. isolated from activated sludge, and proposal of Propylenellaceae fam. nov. - Yu-Ling Liu; Dong Meng; Fang Wang; Xiao-Fan Gong; Peng-Fei Gu; Xiang-Yu Fan; Zong-Jun Du; Ji-Dong Zou; Qiang Li (Antonie van Leeuwenhoek, 2021)

Mechanisms underlying altitudinal and horizontal range contraction: The western black crested gibbon - Li Yang; Kai‐Chong Shi; Chi Ma; Guo‐Peng Ren; Peng‐Fei Fan (Journal of Biogeography, 2021)
Aim Species ranges in mountain areas may shift both horizontally and altitudinally, resulting from climate change and anthropogenic impact. Two hypotheses (the abundant centre hypothesis and the contagion hypothesis) have been proposed to account for patterns of horizontal range contraction. However, undulating topograph causes a mosaic of unsuitable habitats, which may complicate the spatial pattern of range contraction. We develop a framework incorporating horizontal and altitudinal range contraction patterns of a species living in mountain areas, to better understand the underlying mechanisms of species range contraction. Location China, Northern Laos and Northern Vietnam Taxon Western black crested gibbon, Nomascus concolor Methods We collected occurrence data of the gibbons from various sources and modelled their potential distribution range in the 1950s, 1980s and 2010s, using ecological niche modelling. We compared distances from the centre point of the potential range in the 1950s to centre points of the largest 100 patches in the 1950s and the 2010s to understand the patterns of horizontal range contraction. We also calculated potential distributions within different altitudinal ranges for six populations in each period to understand the patterns of altitudinal range contraction. Results Potential horizontal distribution of the gibbons decreased by 69% from the 1950s to the 2010s. The centre point of the 100 largest patches in the 2010s was further apart than in the 1950s, supporting the contagion hypothesis. No populations extended their range to higher altitude, suggesting climate change did not have a profound effect on altitudinal shifts in gibbon range. All populations lost a substantial proportion of their ranges at lower altitudes (500–1,500 m) but to different degrees, suggesting that populations experienced different anthropogenic pressures. Main conclusions Anthropogenic threats including human population increase, agricultural expansion and hunting, were more likely than climate change to have caused range contraction in western black‐crested gibbons. This study highlights the importance of studying horizontal and altitudinal range contraction simultaneously.

Income inequality and growth from functional orientation and spatial policy: Case study of Tibet, China - Yan-nan Zhao; Jie Fan; Ya-fei Wang; Bo Liang; Lu Zhang (Journal of Mountain Science, 2021)

Influence of the Eastern Pacific and Central Pacific Types of ENSO on the South Asian Summer Monsoon - Fangxing Fan; Renping Lin; Xianghui Fang; Feng Xue; Fei Zheng; Jiang Zhu (Advances in Atmospheric Sciences, 2021)

Increased Seizure Susceptibility for Rats Subject to Early Life Hypoxia Might Be Associated with Brain Dysfunction of NRG1-ErbB4 Signaling in Parvalbumin Interneurons - Dong Liang; Fei Fan; Wei Ding; Yuan Fang; Lan Hu; Bibo Lei; Mingqiang Zhang (Molecular Neurobiology, 2020)

Evaluation of crustal inhomogeneity parameters in the southern Longmenshan fault zone and adjacent regions - Xiao-Ping Fan; Yi-Cheng He; Cong-Jie Yang; Jun-Fei Wang (Journal of Seismology, 2020)
Broadband teleseismic waveform data from 13 earthquakes recorded by 70 digital seismic stations were selected to evaluate the inhomogeneity parameters of the crustal medium in the southern Longmenshan fault zone and its adjacent regions using the teleseismic fluctuation wavefield method. Results show that a strong inhomogeneity exists beneath the study region, which can be divided into three blocks according to its structure and tectonic deformation features. These are known as the Sichuan-Qinghai Block, the Sichuan-Yunnan Block, and the Mid-Sichuan Block. The velocity fluctuation ratios of the three blocks are approximately 5.1%, 3.6%, and 5.1% in the upper crust and 5.1%, 3.8%, and 4.9% in the lower crust. The inhomogeneity correlation lengths of the three blocks are about 10.1 km, 14.0 km, and 10.7 km in the upper crust and 11.8 km, 17.0 km, and 11.8 km in the lower crust. The differences in the crustal medium inhomogeneity beneath the Sichuan-Yunnan Block, the Sichuan-Qinghai Block, and the Mid-Sichuan Block may be related to intensive tectonic movement and material flow in the crust and upper mantle.

Association of in-hospital intensive statins dosage and death in arteriosclerotic cardiovascular disease with percutaneous coronary intervention: insights of multicentre cohort from China - Peng-yuan Chen; Yuan-hui Liu; Chong-yang Duan; Hua-lin Fan; Li-huan Zeng; Wei Guo; Lei Jiang; Xue-biao Wei; Wen-fei He; Sha Tao; Zhi-qiang Guo; Ji-yan Chen; et al. (European Journal of Clinical Pharmacology, 2020)

Enzymatic hydroxylation of L-pipecolic acid by L-proline cis-4-hydroxylases and isomers separation - Fan Lu; Jiao Chen; Hai Ye; Hongli Wu; Feng Sha; Fujun Huang; Fei Cao; Ping Wei (Biotechnology Letters, 2020)

Correction of seismic attribute-based small-structure prediction errors using GPR data—A case study of the Shuguang Coal Mine, Shanxi - Cui Fan; Zhao Zhi-Rong; Du Yun-Fei; Bai Yu; Xu Chang-Qing; Jia Xiao-Feng (Applied Geophysics, 2020)

High-precision downward continuation of potential fields algorithm utilizing adaptive damping coefficient of generalized minimal residuals - Zhi-Hou Zhang; Xiao-Long Liao; Ze-Yu Shi; Anthony R. Lowry; Yu Yao; Run-Qi Lu; Xiang-Tai Fan; Peng-Fei Liu; Si-Wei Zhao (Applied Geophysics, 2020)

Prediction and Identification of Epitopes in the Emy162 Antigen of Echinococcus multilocularis - Ming-Quan Pang; Feng Tang; Hai-Jiu Wang; Ying Zhou; Li Ren; Run-Le Li; Hu Zhou; Chen-Fei Wan; Chuan-Chuan Liu; Cai-Rang Yangdan; Hai-Ning Fan (Acta Parasitologica, 2020)

Novel homozygous SPG7 missense mutation in a Chinese hereditary spastic paraplegia family - Fei Mao; Mengxin Bao; Youfei Fan; Meijia Zhu; Xiuhua Li (Acta Neurologica Belgica, 2020)

Characteristics and Health Risk Assessment of Organochlorine Pesticides (OCPs) Residues Along Sino-Russian Boundary River - Fei Xie; Zhilei Xie; Bin Zhou; Liang Li; Xingjun Zhou; Qingyun Fan; Changwei Lü (Water, Air, & Soil Pollution, 2020)

Transcription Factors Phox2a/2b Upregulate Expression of Noradrenergic and Dopaminergic Phenotypes in Aged Rat Brains - Yan Fan; Fei Zeng; Russell W. Brown; Jennifer B. Price; Thomas C. Jones; Meng-Yang Zhu (Neurotoxicity Research, 2020)

Cao Vit Gibbons (Nomascus nasutus) Sing at Higher Elevation but Not in Peripheral Areas of Their Home Range in a Karst Forest - Haigang Ma; Changyong Ma; Hanlan Fei; Li Yang; Pengfei Fan (International Journal of Primatology, 2020)

Correction to: Characteristics of phosphorus adsorption and desorption in erosive weathered granite area and effects of soil properties - Tianyu Sun; Longzhou Deng; Kai Fei; Liping Zhang; Xiaojuan Fan (Environmental Science and Pollution Research, 2020)

Characteristics of phosphorus adsorption and desorption in erosive weathered granite area and effects of soil properties - Tianyu Sun; Longzhou Deng; Kai Fei; Liping Zhang; Xiaojuan Fan (Environmental Science and Pollution Research, 2020)

Transcriptomic Profiling of the Immune Response to Crowding Stress in Juvenile Turbot (Scophthalmus maximus) - Huanhuan Huo; Xiaoqiang Gao; Fan Fei; Fei Qin; Bin Huang; Baoliang Liu (Journal of Ocean University of China, 2020)

Gastric smooth muscle cells manifest an abnormal phenotype in Parkinson’s disease rats with gastric dysmotility - Xiao-Lin Xiu; Li-Fei Zheng; Xiao-Yu Liu; Yan-Yan Fan; Jin-Xia Zhu (Cell and Tissue Research, 2020)

Low-frequency Stimulation at the Subiculum is Anti-convulsant and Anti-drug-resistant in a Mouse Model of Lamotrigine-resistant Temporal Lobe Epilepsy - Yeping Ruan; Cenglin Xu; Jile Lan; Jiazhen Nao; Shuo Zhang; Fei Fan; Yi Wang; Zhong Chen (Neuroscience Bulletin, 2020)

Conspicuous temperature extremes over Southeast Asia: seasonal variations under 1.5 °C and 2 °C global warming - Shoupeng Zhu; Fei Ge; Yi Fan; Ling Zhang; Frank Sielmann; Klaus Fraedrich; Xiefei Zhi (Climatic Change, 2020)

Research Progress on Estimation of the Atmospheric Boundary Layer Height - Hongsheng Zhang; Xiaoye Zhang; Qianhui Li; Xuhui Cai; Shaojia Fan; Yu Song; Fei Hu; Huizheng Che; Jiannong Quan; Ling Kang; Tong Zhu (Journal of Meteorological Research, 2020)

Reverse time migration imaging of tunnels via the finite element method using an unstructured mesh - Jing Wang; Jiang-Ping Liu; Fei Cheng; Huai-Jie Yang; Yi-Fan Huang (Applied Geophysics, 2020)

The oxidation of cyclo-olefin by the S = 2 ground-state complex [FeIV(O)(TQA)(NCMe)]2+ - Zixian Li; Yi Wang; Wenzhi Li; Qingyue Li; Fan Li; Ziqing Gao; Xu Fei; Jing Tian; Liang Dong (JBIC Journal of Biological Inorganic Chemistry, 2020)

Epidural Spinal Cord Stimulation Promotes Motor Functional Recovery by Enhancing Oligodendrocyte Survival and Differentiation and by Protecting Myelin after Spinal Cord Injury in Rats - Gang Li; Zhong-Kai Fan; Guang-Fei Gu; Zhi-Qiang Jia; Qiang-Qiang Zhang; Jun-Yu Dai; Shi-Sheng He (Neuroscience Bulletin, 2020)

MiR-125a-5p Regulates Vitamin D Receptor Expression in a Mouse Model of Experimental Autoimmune Encephalomyelitis - Han-Chun Long; Rui Wu; Chun-Feng Liu; Fei-Long Xiong; Zu Xu; Dian He; Yi-Fan Zhang; Bing Shao; Ping-An Zhang; Guang-Yin Xu; Lan Chu (Neuroscience Bulletin, 2020)

Banana MaBZR1/2 associate with MaMPK14 to modulate cell wall modifying genes during fruit ripening - Wei Shan; Yu-Fan Guo; Wei Wei; Jian-Ye Chen; Wang-Jin Lu; De-Bao Yuan; Xin-Guo Su; Jian-Fei Kuang (Plant Cell Reports, 2020)

RBM4 modulates the proliferation and expression of inflammatory factors via the alternative splicing of regulatory factors in HeLa cells - Wei-Yang Wang; Weili Quan; Fan Yang; Ya-Xun Wei; Jia-Jun Chen; Han Yu; Jie Xie; Yi Zhang; Zhan-Fei Li (Molecular Genetics and Genomics, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Molecular Cloning and Expression Analysis of Ethylene-Insensitive3-Like 1 (ScEIL1) Gene in Sugarcane - Fan-Wei Wang; Jian-Bin Yu; Dong Xiao; Yang-Rui Li; Long-Fei He; Ai-Qin Wang (Sugar Tech, 2019)

Contribution of skeletal muscular glycine to rapid antidepressant effects of ketamine in an inflammation-induced mouse model of depression - Niannian Huang; Yue Wang; Gaofeng Zhan; Fan Yu; Shan Li; Dongyu Hua; Riyue Jiang; Shiyong Li; Yeshun Wu; Ling Yang; Bin Zhu; Fei Hua; et al. (Psychopharmacology, 2019)

Metabolomic profiling on rat brain of prenatal malnutrition: implicated for oxidative stress and schizophrenia - Fei Xu; Xin Li; Weibo Niu; Gaini Ma; Qianqian Sun; Yan Bi; Zhenming Guo; Decheng Ren; Jiaxin Hu; Fan Yuan; Ruixue Yuan; Lei Shi; et al. (Metabolic Brain Disease, 2019)

Effects of calcium-binding sites in the S2–S3 loop on human and Nematostella vectensis TRPM2 channel gating processes - Yu-huan Luo; Xia-fei Yu; Cheng Ma; Fan Yang; Wei Yang (Journal of Zhejiang University-SCIENCE B, 2019)

Comparative transcriptome analysis of male and female gonads reveals sex-biased genes in spotted scat (Scatophagus argus) - Fei-Xiang He; Dong-Neng Jiang; Yuan-Qing Huang; Umar Farouk Mustapha; Wei Yang; Xue-Fan Cui; Chang-Xu Tian; Hua-Pu Chen; Hong-Juan Shi; Si-Ping Deng; Guang-Li Li; Chun-Hua Zhu (Fish Physiology and Biochemistry, 2019)

The chloroplast genome of Chunia bucklandioides (Hamamelidaceae): a rare tree endemic to Hainan, China - Qiujie Zhou; Yongmei Chen; Jinhong Dai; Fei Wang; Wei Wu; Qiang Fan; Renchao Zhou; Wei Lun Ng (Conservation Genetics Resources, 2019)

Effects of stocking density on stress response, innate immune parameters, and welfare of turbot (Scophthalmus maximus) - Baoliang Liu; Fan Fei; Xiaotian Li; Xinyi Wang; Bin Huang (Aquaculture International, 2019)

Incorporating nocturnal UAV side-view images with VIIRS data for accurate population estimation: a test at the urban administrative district scale - Wenyuan Kong; Jingyi Cheng; Xin Liu; Fan Zhang; Teng Fei (International Journal of Remote Sensing, 2019)

Rethinking labelling in road segmentation - Man Yuan; Zhi Liu; Fan Wang; Fei Jin (International Journal of Remote Sensing, 2019)

Effects of rainfall intensity and slope gradient on runoff and sediment yield from hillslopes with weathered granite - Longzhou Deng; Liping Zhang; Xiaojuan Fan; Tianyu Sun; Kai Fei; Liang Ni (Environmental Science and Pollution Research, 2019)

A new abietane diterpenoid glycoside from ajuga ovalifolia var. calantha - Fan Yang; Hong-Ping Chen; Xiao-Fei Shen; Hu-Lan Chen; Yin Chen; Li-Xia Wang; Hai Zhang; Wen-Ji Zhao; Mei Zhang; Yu-Zhu Tan (Natural Product Research, 2019)

A preliminary study on diet of the Yangtze finless porpoise using next‐generation sequencing techniques - Jiwei Yang; Xiaoling Wan; Xianyuan Zeng; Jinsong Zheng; Yi Han; Fei Fan; Yujiang Hao; Kexiong Wang; Zhigang Mei; Ding Wang (Marine Mammal Science, 2019)

Optically stimulated luminescence ages of the Hengyu site and their implications for anthropogenic activities in the Fuzhou Basin, South China - Jianhui Jin; Yunming Huang; Yong Zhang; Zhizhong Li; Xuechun Fan; Zhiyong Ling; Fei Zheng; Yan Cheng; Xiaolin Xu; Zhixing Li; Wenjing Zhang (Journal of Quaternary Science, 2019)
The chronologies of few Neolithic sites in the lower reaches of the Min River of China have been well investigated for the middle to late Holocene. In this study, the Hengyu Neolithic site in Fujian Province, South China, which has significant archaeological remains, was dated using blue‐stimulated optically stimulated luminescence (OSL) and accelerator mass spectrometry radiocarbon (AMS 14 C) techniques. The results, comprising nine OSL and three AMS 14 C ages through the Neolithic sequence, provide new evidence towards understanding the relationship between environmental evolution and human activities in the middle to late Holocene in the Fuzhou Basin and coastal areas of South China. The ages of the site deposits vary from 6.83 to 1.67 ka and can be divided into two main phases: the Keqiutou–Tanshishan culture period and the Bronze culture period. In contrast, the persistent periods of ancient human activities at the Hengyu site seem to correspond to regional sea‐level changes and the East Asian winter monsoon as a secondary factor, which can affect human activities through sea‐level impacts. The warm and high sea level conditions provided a liveable environment for the ancient humans of Fujian and even South China. The ages of two building column bases are linked to the early stage of the Han dynasty, suggesting a potentially favourable habitation environment; that is, ancient humans occupied and settled this area for the long term within this time period, which is consistent with sea‐level changes and palynology records. Copyright © 2019 John Wiley & Sons, Ltd.

RETRACTED ARTICLE: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2019)

Functional analysis of McSnRK1 (SNF1-related protein kinase 1) in regulating Na/K homeostasis in transgenic cultured cells and roots of halophyte Mesembryanthemum crystallinum - Hau-Hsuan Hwang; Chih-Hao Wang; Hsiao-Wei Huang; Chih-Pin Chiang; Shin-Fei Chi; Fan-Chen Huang; Hungchen E. Yen (Plant Cell Reports, 2019)

Spontaneous Regional Brain Activity in Healthy Individuals is Nonlinearly Modulated by the Interaction of ZNF804A rs1344706 and COMT rs4680 Polymorphisms - Lingling Cui; Fei Wang; Miao Chang; Zhiyang Yin; Guoguang Fan; Yanzhuo Song; Yange Wei; Yixiao Xu; Yifan Zhang; Yanqing Tang; Xiaohong Gong; Ke Xu (Neuroscience Bulletin, 2019)

Finite element reverse time migration imaging in tunnels using an unstructured mesh - Jing Wang; Jiang-Ping Liu; Fei Cheng; Huai-Jie Yang; Yi-Fan Huang (Applied Geophysics, 2019)

Effects of frequency and confining pressure on consolidation drainage behavior of soft marine clays - Yong-Hong Miao; Fan-Bo Zhou; Jie Yin; Yan-Chang Sun; Rui-Bing Li; Jian-Fei Lu (Marine Georesources & Geotechnology, 2019)

Spatiotemporal distributions of Cu, Zn, metribuzin, atrazine, and their transformation products in the surface water of a small plain stream in eastern China - Xiaoyin Sun; Fei Liu; Ruifeng Shan; Yuna Fan (Environmental Monitoring and Assessment, 2019)

Response of the Dominant Modes of Atmospheric Circulation in the Northern Hemisphere to a Projected Arctic Sea Ice Loss in 2007 - Tingting Fan; Fei Huang; Xiao Zhou (Journal of Ocean University of China, 2019)

Complete genome sequence of a divergent strain of Tibetan frog hepatitis B virus associated with a concave-eared torrent frog (Odorrana tormota) - Humberto J. Debat; Terry Fei Fan Ng (Archives of Virology, 2019)

Novel hepacivirus in Asian house shrew, China - Hua Guo; Chunlin Cai; Bo Wang; Fei Zhuo; Rendi Jiang; Ning Wang; Bei Li; Wei Zhang; Yan Zhu; Yi Fan; Wushen Chen; Weihong Chen; et al. (Science China Life Sciences, 2019)

Characteristics of runoff processes and nitrogen loss via surface flow and interflow from weathered granite slopes of Southeast China - Long-zhou Deng; Kai Fei; Tian-yu Sun; Li-ping Zhang; Xiao-juan Fan; Liang Ni (Journal of Mountain Science, 2019)

The phase differences of the interdecadal variabilities of tropical cyclone activity in the peak and late seasons over the western North Pacific - Tingting Fan; Shibin Xu; Fei Huang; Jinping Zhao (Theoretical and Applied Climatology, 2019)

Identification of favorable SNP alleles and candidate genes responsible for inflorescence-related traits via GWAS in chrysanthemum - Xinran Chong; Jiangshuo Su; Fan Wang; Haibin Wang; Aiping Song; Zhiyong Guan; Weimin Fang; Jiafu Jiang; Sumei Chen; Fadi Chen; Fei Zhang (Plant Molecular Biology, 2019)

Genomic sequencing of a virus representing a novel type within the species Dyopipapillomavirus 1 in an Indian River Lagoon bottlenose dolphin - Galaxia Cortés-Hinojosa; Kuttichantran Subramaniam; James F. X. Wellehan; Terry Fei Fan Ng; Eric Delwart; Stephen D. McCulloch; Juli D. Goldstein; Adam M. Schaefer; Patricia A. Fair; John S. Reif; Gregory D. Bossart; Thomas B. Waltzek (Archives of Virology, 2019)

Iron Accumulation Leads to Bone Loss by Inducing Mesenchymal Stem Cell Apoptosis Through the Activation of Caspase3 - Ye Yuan; Fei Xu; Yan Cao; Li Xu; Chen Yu; Fan Yang; Peng Zhang; Liang Wang; Guangsi Shen; Jianrong Wang; Youjia Xu (Biological Trace Element Research, 2019)

Effects of the silencing of CmMET1 by RNA interference in chrysanthemum (Chrysanthemum morifolium) - Shuailei Li; Mangmang Li; Zhongai Li; Yi Zhu; Hongxu Ding; Xiaoxuan Fan; Fei Li; Zicheng Wang (Plant Biotechnology Reports, 2019)

Characterization of milk protein composition of the Yangtze finless porpoise - Xianyuan Zeng; Minmin Chen; Zhigang Liu; Daoping Yu; Shiang‐Lin Huang; Jiwei Yang; Fei Fan; Ding Wang; Yujiang Hao; Ghulam Nabi (Marine Mammal Science, 2019)

Clinical Application of Chromosome Microarray Analysis in Han Chinese Children with Neurodevelopmental Disorders - Mingyu Xu; Yiting Ji; Ting Zhang; Xiaodong Jiang; Yun Fan; Juan Geng; Fei Li (Neuroscience Bulletin, 2018)

LaMIR166a-mediated auxin biosynthesis and signalling affect somatic embryogenesis in Larix leptolepis - Zhe-Xin Li; Yan-Ru Fan; Shao-Fei Dang; Wan-Feng Li; Li-Wang Qi; Su-ying Han (Molecular Genetics and Genomics, 2018)

Quantitative Comparison of Korotkoff Sound Waveform Characteristics: Effects of Static Cuff Pressures and Stethoscope Positions - Fan Pan; Fei Chen; Chen Liu; Zhipeng Yang; Zhihong Liu; Dingchang Zheng (Annals of Biomedical Engineering, 2018)

The different relationship of Pacific interior subtropical cells and two types of ENSO - Junqiao Feng; Dunxin Hu; Fei-fei Jin; Fan Jia; Qingye Wang; Shoude Guan (Journal of Oceanography, 2018)

Taxonomy of the family Arenaviridae and the order Bunyavirales: update 2018 - Piet Maes; Sergey V. Alkhovsky; Yīmíng Bào; Martin Beer; Monica Birkhead; Thomas Briese; Michael J. Buchmeier; Charles H. Calisher; Rémi N. Charrel; Il Ryong Choi; Christopher S. Clegg; Juan Carlos de la Torre; et al. (Archives of Virology, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Exogenous GA3 application altered morphology, anatomic and transcriptional regulatory networks of hormones in Eucalyptus grandis - Qian-Yu Liu; Guang-Sheng Guo; Zhen-Fei Qiu; Xiao-Dan Li; Bing-Shan Zeng; Chun-Jie Fan (Protoplasma, 2018)

Arbuscular mycorrhizal fungi stimulate organic phosphate mobilization associated with changing bacterial community structure under field conditions - Lin Zhang; Ning Shi; Jiequn Fan; Fei Wang; Timothy S. George; Gu Feng (Environmental Microbiology, 2018)
Summary The extraradical hyphae of arbuscular mycorrhizal fungi (AMF) harbour and interact with a microbial community performing multiple functions. However, how the AMF‐microbiome interaction influences the phosphorus (P) acquisition efficiency of the mycorrhizal pathway is unclear. Here we investigated whether AMF and their hyphal microbiome play a role in promoting organic phosphorus (P) mineralizing under field conditions. We developed an AMF hyphae in‐growth core system for the field using PVC tubes sealed with membrane with different size of pores (30 or 0.45 μm) to allow or deny AMF hyphae access to a patch of organic P in root‐free soil. AMF and their hyphae associated microbiome played a role in enhancing soil organic P mineralization in situ in the field, which was shown to be a function of the change in bacteria community on the hyphae surface. The bacterial communities attached to the AMF hyphae surface were significantly different from those in the bulk soil. Importantly, AMF hyphae recruited bacteria that produced alkaline phosphatase and provided a function that was absent from the hyphae. These results demonstrate the importance of understanding trophic interactions to be able to gain insight into the functional controls of nutrient cycles in the rhizosphere.

LRP16 prevents hepatocellular carcinoma progression through regulation of Wnt/β-catenin signaling - Lijuan Shao; Wei Jing; Lingxiong Wang; Fei Pan; Liangliang Wu; Lijun Zhang; Pan Yang; Minggen Hu; Kexing Fan (Journal of Molecular Medicine, 2018)

Detection and genetic characterization of bovine kobuvirus from calves in Egypt - Fakry F. Mohamed; Shimaa M. G. Mansour; Ahmed Orabi; Iman E. El-Araby; Terry Fei Fan Ng; Sunil K. Mor; Sagar M. Goyal (Archives of Virology, 2018)

Magnetic nanoparticles based cancer therapy: current status and applications - Huan Zhang; Xiao Li Liu; Yi Fan Zhang; Fei Gao; Ga Long Li; Yuan He; Ming Li Peng; Hai Ming Fan (Science China Life Sciences, 2018)

Differential expression of the PAL gene family in rice seedlings exposed to chromium by microarray analysis - Xiao-Zhang Yu; Wei-Jia Fan; Yu-Juan Lin; Fei-Fei Zhang; Dharmendra K. Gupta (Ecotoxicology, 2018)

PKM2 knockdown influences SREBP activation and lipid synthesis in bovine mammary-gland epithelial MAC-T cells - Bing-Qian Su; Ying-Qian Han; Shuang-Shuang Fan; Sheng-Li Ming; Bo Wan; Wei-Fei Lu; Bei-Bei Chu; Guo-Yu Yang; Jiang Wang (Biotechnology Letters, 2018)

Geochronology, geochemistry, and Sr–Nd–Pb–Hf isotopes of the Zhunsujihua granitoid intrusions associated with the molybdenum deposit, northern Inner Mongolia, China: implications for petrogenesis and tectonic setting - Xiaojun Zhang; David R. Lentz; Chunliang Yao; Rui Liu; Zhen Yang; Yanxiong Mei; Xianwang Fan; Fei Huang; Ying Qin; Kun Zhang; Zhenfei Zhang (International Journal of Earth Sciences, 2018)

Heterogeneous activation of peroxymonosulfate by hierarchical CuBi2O4 to generate reactive oxygen species for refractory organic compounds degradation: morphology and surface chemistry derived reaction and its mechanism - Yiping Wang; Fan Li; Tianshan Xue; Chao Liu; Donghai Yuan; Fei Qi; Bingbing Xu (Environmental Science and Pollution Research, 2018)

Multiple correlation analyses revealed complex relationship between DNA methylation and mRNA expression in human peripheral blood mononuclear cells - Fang-Fei Xie; Fei-Yan Deng; Long-Fei Wu; Xing-Bo Mo; Hong Zhu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiao-Wei Zhu; Wei Xia; Lan Wang; et al. (Functional & Integrative Genomics, 2018)

A new immunosuppressive pregnane glycoside from aqueous fraction of Epigynum cochinchinensis - Zong Wan; Yuan-Cheng Yao; Fei Gao; Sheng-Bao Cai; Afsar Khan; Tian-Rui Zhao; Xiao-Yan Yang; Jian Fan; Sheng-Yan Qian; Jian-Xin Cao; Gui-Guang Cheng (Natural Product Research, 2017)

Genomic characterization of a novel calicivirus, FHMCV-2012, from baitfish in the USA - Sunil Kumar Mor; Nicholas B. D. Phelps; Terry Fei Fan Ng; Kuttichantran Subramaniam; Alexander Primus; Anibal G. Armien; Rebekah McCann; Corey Puzach; Thomas B. Waltzek; Sagar M. Goyal (Archives of Virology, 2017)

Genome-wide characterization of the WRKY gene family in radish (Raphanus sativus L.) reveals its critical functions under different abiotic stresses - Bernard Kinuthia Karanja; Lianxue Fan; Liang Xu; Yan Wang; Xianwen Zhu; Mingjia Tang; Ronghua Wang; Fei Zhang; Everlyne M’mbone Muleke; Liwang Liu (Plant Cell Reports, 2017)

Efficacy and safety of probiotic-supplemented triple therapy for eradication of Helicobacter pylori in children: a systematic review and network meta-analysis - Jue-Rong Feng; Fan Wang; Xiao Qiu; Lynne V. McFarland; Peng-Fei Chen; Rui Zhou; Jing Liu; Qiu Zhao; Jin Li (European Journal of Clinical Pharmacology, 2017)

Numerical modeling of local scour around hydraulic structure in sandy beds by dynamic mesh method - Fei Fan; Bingchen Liang; Yuchuan Bai; Zhixia Zhu; Yanjun Zhu (Journal of Ocean University of China, 2017)

Sodium Tanshinone IIA Sulfonate Enhances Effectiveness Rt-PA Treatment in Acute Ischemic Stroke Patients Associated with Ameliorating Blood-Brain Barrier Damage - Biying Ji; Fei Zhou; Lijuan Han; Jun Yang; Haijian Fan; Shanshan Li; Jingwei Li; Xin Zhang; Xiaoying Wang; Xiangyan Chen; Yun Xu (Translational Stroke Research, 2017)

Antipredation Sleeping Behavior of Skywalker Hoolock Gibbons (Hoolock tianxing) in Mt. Gaoligong, Yunnan, China - Han-Lan Fei; Dao Zhang; Sheng-Dong Yuan; Lu Zhang; Peng-Fei Fan (International Journal of Primatology, 2017)

Seasonal-related effects on ammonium removal in activated carbon filter biologically enhanced by heterotrophic nitrifying bacteria for drinking water treatment - Wen Qin; Wei-Guang Li; Xu-jin Gong; Xiao-Fei Huang; Wen-biao Fan; Duoying Zhang; Peng Yao; Xiao-ju Wang; Yang Song (Environmental Science and Pollution Research, 2017)

Spatio-temporal variations of Arctic amplification and their linkage with the Arctic oscillation - Yanshuo Wang; Fei Huang; Tingting Fan (Acta Oceanologica Sinica, 2017)

The epigenetic modifications and the anterior to posterior characterization of meiotic entry during mouse oogenesis - Xia-Fei Fu; Fan Yang; Shun-Feng Cheng; Yan-Ni Feng; Lan Li; Paul W. Dyce; Wei Shen; Xiao-Feng Sun (Histochemistry and Cell Biology, 2017)

Seco-pregnane glycosides from the stems of Epigynum auritum - Fei Gao; Yuan-Cheng Yao; Zong Wan; Sheng-Bao Cai; Jian Fan; Tian-Rui Zhao; Jian-Xin Cao; Gui-Guang Cheng (Natural Product Research, 2017)

SDF1-CXCR4 Signaling Contributes to the Transition from Acute to Chronic Pain State - Fei Yang; Wei Sun; Wen-Jun Luo; Yan Yang; Fan Yang; Xiao-Liang Wang; Jun Chen (Molecular Neurobiology, 2017)

RETRACTED ARTICLE: Revisiting the male genetic landscape of China: a multi-center study of almost 38,000 Y-STR haplotypes - Michael Nothnagel; Guangyao Fan; Fei Guo; Yongfeng He; Yiping Hou; Shengping Hu; Jiang Huang; Xianhua Jiang; Wook Kim; Kicheol Kim; Chengtao Li; Hui Li; et al. (Human Genetics, 2017)

Integrative multi-omics analysis revealed SNP-lncRNA-mRNA (SLM) networks in human peripheral blood mononuclear cells - Wei Xia; Xiao-Wei Zhu; Xin-Bo Mo; Long-Fei Wu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiang Lin; Ying-Hua Qiu; Lan Wang; Pei He; et al. (Human Genetics, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Blood Flow and Oxygen Transport in Descending Branch of Lateral Femoral Circumflex Arteries After Transfemoral Amputation: A Numerical Study - Fei Yan; Wen-Tao Jiang; Rui-Qi Dong; Qing-Yuan Wang; Yu-Bo Fan; Ming Zhang (Journal of Medical and Biological Engineering, 2017)

Effects of freeze-thaw cycle on engineering properties of loess used as road fills in seasonally frozen ground regions, North China - Guo-yu Li; Wei Ma; Yan-hu Mu; Fei Wang; Shan-zhi Fan; Ya-hu Wu (Journal of Mountain Science, 2017)

Integrative analysis for identification of shared markers from various functional cells/tissues for rheumatoid arthritis - Wei Xia; Jian Wu; Fei-Yan Deng; Long-Fei Wu; Yong-Hong Zhang; Yu-Fan Guo; Shu-Feng Lei (Immunogenetics, 2017)

CNOP-based sensitive areas identification for tropical cyclone adaptive observations with PCAGA method - Lin-Lin Zhang; Shi-Jin Yuan; Bin Mu; Fei-Fan Zhou (Asia-Pacific Journal of Atmospheric Sciences, 2017)

A highly Selective Fluorescent Sensor for Monitoring Cu2+ Ion: Synthesis, Characterization and Photophysical Properties - Stephen Opeyemi Aderinto; Yuling Xu; Hongping Peng; Fei Wang; Huilu Wu; Xuyang Fan (Journal of Fluorescence, 2017)

Environmental Enrichment Prevent the Juvenile Hypoxia-Induced Developmental Loss of Parvalbumin-Immunoreactive Cells in the Prefrontal Cortex and Neurobehavioral Alterations Through Inhibition of NADPH Oxidase-2-Derived Oxidative Stress - Mingqiang Zhang; Jing Wu; Lan Huo; Liang Luo; Xi Song; Fei Fan; Yiming Lu; Dong Liang (Molecular Neurobiology, 2016)

Numerical simulation on the effects of drug-eluting stents with different bending angles on hemodynamics and drug distribution - Yu Chen; Yan Xiong; Wentao Jiang; Man Sang Wong; Fei Yan; Qingyuan Wang; Yubo Fan (Medical & Biological Engineering & Computing, 2016)

Nuclear import of Maize chlorotic mottle virus capsid protein is mediated by importin-α - Binhui Zhan; Fei Lang; Tao Zhou; Zaifeng Fan (European Journal of Plant Pathology, 2016)

Identification and transcript profiles of citrus growth-regulating factor genes involved in the regulation of leaf and fruit development - Xiao Liu; Ling-Xia Guo; Long-Fei Jin; Yong-Zhong Liu; Tao Liu; Yu-Hua Fan; Shu-Ang Peng (Molecular Biology Reports, 2016)

High-pressure behavior of natural single-crystal epidote and clinozoisite up to 40 GPa - Fei Qin; Xiang Wu; Ying Wang; Dawei Fan; Shan Qin; Ke Yang; Joshua P. Townsend; Steven D. Jacobsen (Physics and Chemistry of Minerals, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Identification of antigenic domains in the non-structural protein of Muscovy duck parvovirus - Tian-fei Yu; Ming Li; Bing Yan; Shu-li Shao; Xing-dong Fan; Jia Wang; Dan-na Wang (Archives of Virology, 2016)

Effects of silicon on morphology, ultrastructure and exudates of rice root under heavy metal stress - Xueying Fan; Xiaohui Wen; Fei Huang; Yixia Cai; Kunzheng Cai (Acta Physiologiae Plantarum, 2016)

Comparative analysis of essential oil composition from flower and leaf of Magnolia kwangsiensis Figlar & Noot. - Yan-Fei Zheng; Fan Ren; Xiong-Min Liu; Fang Lai; Li Ma (Natural Product Research, 2016)

Learning curves of percutaneous endoscopic lumbar discectomy in transforaminal approach at the L4/5 and L5/S1 levels: a comparative study - Xin-bo Wu; Guo-xin Fan; Xin Gu; Tu-gang Shen; Xiao-fei Guan; An-nan Hu; Hai-long Zhang; Shi-sheng He (Journal of Zhejiang University-SCIENCE B, 2016)

Energy-Use Efficiency and Economic Analysis of Sugar Beet Production in China: A Case Study in Xinjiang Province - Fan Hua; Li Yangyang; Fei Cong; Huo Peishu; Wang Kaiyong (Sugar Tech, 2016)

Application of Minimum Reward Risk Model in Reservoir Generation Scheduling - Ming Zhang; Fei Yang; Jing-Xiu Wu; Zi-Wu Fan; Ying-Ying Wang (Water Resources Management, 2016)

Reorganization and expansion of the nidoviral family Arteriviridae - Jens H. Kuhn; Michael Lauck; Adam L. Bailey; Alexey M. Shchetinin; Tatyana V. Vishnevskaya; Yīmíng Bào; Terry Fei Fan Ng; Matthew LeBreton; Bradley S. Schneider; Amethyst Gillis; Ubald Tamoufe; Joseph Le Doux Diffo; et al. (Archives of Virology, 2016)

Gabapentinoid Insensitivity after Repeated Administration is Associated with Down-Regulation of the α2δ-1 Subunit in Rats with Central Post-Stroke Pain Hypersensitivity - Yan Yang; Fei Yang; Fan Yang; Chun-Li Li; Yan Wang; Zhen Li; Yun-Fei Lu; Yao-Qing Yu; Han Fu; Ting He; Wei Sun; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2016)

bmo-miR-0001 and bmo-miR-0015 down-regulate expression of Bombyx mori fibroin light chain gene in vitro - Chen Chen; Yang-yang Fan; Xin Wang; Fei Song; Tao Jiang; Ping Qian; Shun-ming Tang; Xing-jia Shen (Journal of Zhejiang University-SCIENCE B, 2016)

Low-Dose Topical 5-Aminolevulinic Acid Photodynamic Therapy in the Treatment of Different Severity of Acne Vulgaris - Shi-qin Tao; Fei Li; Lei Cao; Ru-shan Xia; Hua Fan; Ying Fan; Hui Sun; Cheng Jing; Li-jia Yang (Cell Biochemistry and Biophysics, 2015)

One new flavonoid from Oroxylum indicum - Qing-Fei Fan; Zu-Yan Hu; Zhi Na; Hua-Shu Tang; Guo-Ying Zuo; Qi-Shi Song (Natural Product Research, 2015)

Feeding Postures of Cao Vit Gibbons (Nomascus nasutus) Living in a Low-Canopy Karst Forest - Hanlan Fei; Changyong Ma; Thad Q. Bartlett; Ran Dai; Wen Xiao; Pengfei Fan (International Journal of Primatology, 2015)

Rabovirus: a proposed new picornavirus genus that is phylogenetically basal to enteroviruses and sapeloviruses - Terry Fei Fan Ng; Jana Sachsenröder; Gábor Reuter; Nick J. Knowles; Eric Delwart; Reimar Johne (Archives of Virology, 2015)

Characterization and profiling of MicroRNAs in posterior silk gland of the silkworm (Bombyx mori) - Fei Song; Xin Wang; Chen Chen; Yangyang Fan; Shunming Tang; Jinshan Huang; Xijie Guo; Xingjia Shen (Genes & Genomics, 2015)

A tortoise-infecting picornavirus expands the host range of the family Picornaviridae - Terry Fei Fan Ng; James F. X. Wellehan; James K. Coleman; Nikola O. Kondov; Xutao Deng; Thomas B. Waltzek; Gábor Reuter; Nick J. Knowles; Eric Delwart (Archives of Virology, 2015)

A review of seasonal climate prediction research in China - Huijun Wang; Ke Fan; Jianqi Sun; Shuanglin Li; Zhaohui Lin; Guangqing Zhou; Lijuan Chen; Xianmei Lang; Fang Li; Yali Zhu; Hong Chen; Fei Zheng (Advances in Atmospheric Sciences, 2015)

Effect of exogenous salicylic acid on manganese toxicity, mineral nutrients translocation and antioxidative system in polish wheat (Triticum polonicum L.) - Huajin Sheng; Jian Zeng; Fei Yan; Xiaolu Wang; Yi Wang; Houyang Kang; Xing Fan; Lina Sha; Haiqin Zhang; Yonghong Zhou (Acta Physiologiae Plantarum, 2015)

Effects of insect infestation on Quercus aliena var. acuteserrata acorn dispersal in the Qinling Mountains, China - Fei Yu; Xiaoxiao Shi; Dexiang Wang; Xianfeng Yi; Defang Fan; Tingdong Guo; Yuangen Lou (New Forests, 2015)

Identification of several clades of novel single-stranded circular DNA viruses with conserved stem-loop structures in pig feces - Andrew K. Cheung; Terry Fei Fan Ng; Kelly M. Lager; David P. Alt; Eric Delwart; Roman M. Pogranichniy (Archives of Virology, 2015)

Genome re-sequencing suggested a weedy rice origin from domesticated indica-japonica hybridization: a case study from southern China - Jie Qiu; Jinwen Zhu; Fei Fu; Chu-Yu Ye; Weidi Wang; Linfeng Mao; Zhangxiang Lin; Li Chen; Haiqiang Zhang; Longbiao Guo; Shen Qiang; Yongliang Lu; et al. (Planta, 2014)

Post-stroke pain hypersensitivity induced by experimental thalamic hemorrhage in rats is region-specific and demonstrates limited efficacy of gabapentin - Fei Yang; Han Fu; Yun-Fei Lu; Xiao-Liang Wang; Yan Yang; Fan Yang; Yao-Qing Yu; Wei Sun; Jia-Shuang Wang; Michael Costigan; Jun Chen (Neuroscience Bulletin, 2014)

TGF-β1 enhances SDF-1-induced migration and tube formation of choroid-retinal endothelial cells by up-regulating CXCR4 and CXCR7 expression - Yi-fan Feng; Fei Yuan; Hua Guo; Wei-zhong Wu (Molecular and Cellular Biochemistry, 2014)

Integration of metal chemical forms and subcellular partitioning to understand metal toxicity in two lettuce (Lactuca sativa L.) cultivars - Cheng-Cheng Li; Fei Dang; Long Cang; Chui-Fan Zhou; Dong-Mei Zhou (Plant and Soil, 2014)

Inhibition of acid-sensing ion channel 1a in hepatic stellate cells attenuates PDGF-induced activation of HSCs through MAPK pathway - Fan-rong Wu; Chun-xiao Pan; Chao Rong; Quan Xia; Feng-lai Yuan; Jie Tang; Xiao-yu Wang; Nan Wang; Wen-lin Ni; Fei-hu Chen (Molecular and Cellular Biochemistry, 2014)

Expression of bioactive porcine interferon-alpha in Lactobacillus casei - Shi-jie Ma; Kun Li; Xin-Sheng Li; Xiao-Qing Guo; Peng-Fei Fu; Ming-Fan Yang; Hong-Ying Chen (World Journal of Microbiology and Biotechnology, 2014)

Integrated microRNA–mRNA analysis of coronary artery disease - Fei Chen; Xin Zhao; Juan Peng; LinPing Bo; Bing Fan; Duan Ma (Molecular Biology Reports, 2014)

The influence of new herbicide ZJ0273 on the total- and branched-chain amino acids in oilseed rape (Brassica napus L.) leaves as revealed by near-infrared spectroscopy - Tian Tian; Zonglai Jin; Basharat Ali; Xiang Guo; Fei Liu; Fan Zhang; Wenfang Zhang; Yong He; Weijun Zhou (Acta Physiologiae Plantarum, 2014)

Role of Interleukin-22 in liver diseases - Chun-xiao Pan; Jie Tang; Xiao-yu Wang; Fan-rong Wu; Jin-fang Ge; Fei-hu Chen (Inflammation Research, 2014)

Effects of WT1 gene downregulation on apoptosis in porcine fetal fibroblasts - Peipei An; Yu Ding; Aibing Wang; Wentao Tan; Fei Gao; Anran Fan; Bo Tang; Xueming Zhang; Ziyi Li (In Vitro Cellular & Developmental Biology - Animal, 2014)

The measure and characteristics of spatial-temporal evolution of China’s science and technology resource allocation efficiency - Fei Fan; Debin Du; Xinzhu Wang (Journal of Geographical Sciences, 2014)

Ranging behavior of eastern hoolock gibbon (Hoolock leuconedys) in a northern montane forest in Gaoligongshan, Yunnan, China - Dao Zhang; Han-Lan Fei; Sheng-Dong Yuan; Wen-Mo Sun; Qing-Yong Ni; Liang-Wei Cui; Peng-Fei Fan (Primates, 2014)

Nuclear factor-κB signaling pathway is involved in phospholipase Cε-regulated proliferation in human renal cell carcinoma cells - Hong-fei Du; Li-ping Ou; Xue-dong Song; Yan-ru Fan; Xue Yang; Bing Tan; Zhen Quan; Chun-Li Luo; Xiao-hou Wu (Molecular and Cellular Biochemistry, 2014)

Induction of autophagy-dependent cell death by the survivin suppressant YM155 in salivary adenoid cystic carcinoma - Yu-Fan Wang; Wei Zhang; Ke-Fei He; Bing Liu; Lu Zhang; Wen-Feng Zhang; Ashok B. Kulkarni; Yi-Fang Zhao; Zhi-Jun Sun (Apoptosis, 2014)

Domestic Water Consumption under Intermittent and Continuous Modes of Water Supply - Liangxin Fan; Guobin Liu; Fei Wang; Coen J. Ritsema; Violette Geissen (Water Resources Management, 2014)

MicroRNA-124 reduces caveolar density by targeting caveolin-1 in porcine kidney epithelial PK15 cells - Songbai Yang; Xiangdong Liu; Xinyun Li; Shufeng Sun; Fei Sun; Bin Fan; Shuhong Zhao (Molecular and Cellular Biochemistry, 2013)

Evaluation of the sedative and hypnotic effects of Eucommiol in Eucommia - Xin Li; Wenxue Zhu; Lipeng Yang; Dongqing Fei; Jinling Fan; Lin Du; Yan Liu (Natural Product Research, 2013)

Vascular endothelial growth factor regulates primate choroid-retinal endothelial cell proliferation and tube formation through PI3K/Akt and MEK/ERK dependent signaling - Jing Jin; Fei Yuan; Min-qian Shen; Yi-fan Feng; Qi-liu He (Molecular and Cellular Biochemistry, 2013)

O-glycan profiling of serum glycan for potential renal cancer biomarkers - Yi Gao; Fei Ma; Wei Zhang; Fan Zhong; HaiLin Tang; DanFeng Xu; Liang Zhao (Science China Life Sciences, 2013)

Seasonal variation of diet and time budget of Eastern hoolock gibbons (Hoolock leuconedys) living in a northern montane forest - Peng-Fei Fan; Huai-Sen Ai; Han-Lan Fei; Dao Zhang; Sheng-Dong Yuan (Primates, 2013)

Establishment of SYBR green-based qPCR assay for rapid evaluation and quantification for anti-Hantaan virus compounds in vitro and in suckling mice - Fei Wei; Jin-lin Li; Jia-xin Ling; Liang-Jun Chen; Ning Li; Yuan-Yuan Liu; Fan Luo; Hai-Rong Xiong; Wei Hou; Zhan-Qiu Yang (Virus Genes, 2013)

Complete nucleotide sequence of a Chinese isolate of Grapevine leafroll-associated virus 3 reveals a 5′ UTR of 802 nucleotides - Fei Fei; Mu-Di Lyu; Jie Li; Zai-Feng Fan; Yu-Qin Cheng (Virus Genes, 2013)

Compressibility and structural properties of jadeite, NaAlSi2O6 at high pressure - Xiuling Wu; Xiaoyu Fan; Fei Qin; Dawei Meng; Xiaoling Zhang; Long Chen; Weiping Liu; Jianping Zheng (Journal of Earth Science, 2013)

Molecular cloning, characterization, and expression analysis of a cytosolic HSP90 gene from Haematococcus pluvialis - Lei Zhang; Yinmao Fan; Fei Shi; Song Qin; Bing Liu (Journal of Applied Phycology, 2012)

Traditional Chinese medicines benefit to nonalcoholic fatty liver disease: a systematic review and meta-analysis - Ke-Qing Shi; Yu-Chen Fan; Wen-Yue Liu; Ling-Fei Li; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

The detection of EBP50 expression using quantum dot immunohistochemistry in pancreatic cancer tissue and down-regulated EBP50 effect on PC-2 cells - Meng-Yao Ji; Di-kun Fan; Xiao-Guang Lv; Xiu-Lan Peng; Xiao-Fei Lei; Wei-Guo Dong (Journal of Molecular Histology, 2012)

Genetic characterization of a new subtype of Hantaan virus isolated from a hemorrhagic fever with renal syndrome (HFRS) epidemic area in Hubei Province, China - Jin-lin Li; Jia-xin Ling; Dong-ying Liu; Jing Liu; Yuan-yuan Liu; Fei Wei; Fan Luo; Wen Chen; Yi-hui Zhang; Hai-rong Xiong; Wei Hou; Zhan-qiu Yang (Archives of Virology, 2012)

Characterization of an Ac transposon system based on apt1-m1 (Ac) on the long arm of maize chromosome 9 - Fei Wang; Pengfei Li; Yuanping Tang; Jun Fan; Dabin Xu; Shengming Guo; Zhengkai Xu; Rentao Song (Genetica, 2012)

An Excellent Delivery System for Improving the Oral Bioavailability of Natural Vitamin E in Rats - Yinhua Gong; Yunkai Wu; Chunli Zheng; Liya Fan; Fei Xiong; Jiabi Zhu (AAPS PharmSciTech, 2012)

Recombinant human endostatin inhibits adjuvant arthritis by down-regulating VEGF expression and suppression of TNF-α, IL-1β production - Wei Hu; Li-Juan Xia; Fei-Hu Chen; Fan-Rong Wu; Jie Tang; Cun-Zhi Chen; Sheng Jiang; Hui-Hui Chen (Inflammation Research, 2012)

Expression profile analysis of the polygalacturonase-inhibiting protein genes in rice and their responses to phytohormones and fungal infection - Liaoxun Lu; Fei Zhou; Yong Zhou; Xiaolei Fan; Shuifeng Ye; Lei Wang; Hao Chen; Yongjun Lin (Plant Cell Reports, 2012)

Environmental and health challenges of the global growth of electronic waste - Qiang Liu; Shu Juan Shi; Li Qing Du; Yan Wang; Jia Cao; Chang Xu; Fei Yue Fan; John P. Giesy; Markus Hecker (Environmental Science and Pollution Research, 2012)

Land surface emissivity change in China from 2001 to 2010 - Xinsheng Wang; Jiangwen Fan; Jing Xu; Fei Liu; Shoujie Gao; Xincai Wei (Journal of Geographical Sciences, 2012)

A first set of polymorphic microsatellite loci isolated from Rhinogobio cylindricus - Hong Yan Liu; Fei Xiong; Xin Bin Duan; Da Qing Chen; Shao Ping Liu; Fan Rrong Zhang; Dong Yang; Lai Ning Yu (Conservation Genetics Resources, 2012)

Role of mitochondrial pathway in compression-induced apoptosis of nucleus pulposus cells - Fan Ding; Zeng-Wu Shao; Shu-Hua Yang; Qiang Wu; Fei Gao; Li-Ming Xiong (Apoptosis, 2012)

Genetic diversity analysis of Rhododendron aureum Georgi (Ericaceae) located on Changbai Mountain using ISSR and RAPD markers - Yan-Fei Liu; Ming Xing; Wei Zhao; Rong-Jun Fan; Su Luo; Xia Chen (Plant Systematics and Evolution, 2012)

Risk stratification of spontaneous bacterial peritonitis in cirrhosis with ascites based on classification and regression tree analysis - Ke-Qing Shi; Yu-Chen Fan; Li Ying; Xian-Feng Lin; Mei Song; Ling-Fei Li; Xie-Yan Yu; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

Exocytosis of SH-SY5Y single cell with different shapes cultured on ITO micro-pore electrode - Hui Zhao; Ling Li; Hua-Jun Fan; Fei Wang; Li-Ming Jiang; Pin-Gang He; Yu-Zhi Fang (Molecular and Cellular Biochemistry, 2012)

Blockade of acid-sensing ion channels protects articular chondrocytes from acid-induced apoptotic injury - Wei Hu; Fei-Hu Chen; Feng-Lai Yuan; Teng-Yue Zhang; Fan-Rong Wu; Chao Rong; Sheng Jiang; Jie Tang; Cheng-Cheng Zhang; Mei-Ying Lin (Inflammation Research, 2012)

Correlation of antibody production rate with glucose and lactate metabolism in Chinese hamster ovary cells - Fei Chen; Zhaoyang Ye; Liang Zhao; Xuping Liu; Li Fan; Wen-Song Tan (Biotechnology Letters, 2012)

Interleukin-23 as a potential therapeutic target for rheumatoid arthritis - Chao Rong; Wei Hu; Fan-rong Wu; Xiao-juan Cao; Fei-hu Chen (Molecular and Cellular Biochemistry, 2012)

Selecting the optimum location of the corner using gravity gradient method - Peng-Fei Sun; Yan-Gang Wu; Chun-Cheng Yang; Zhao-Hong Han; Mei-Ning Fan (Applied Geophysics, 2011)

Detection of porcine circovirus type 1 in commercial porcine vaccines by loop-mediated isothermal amplification - Chun Wang; Victor Fei Pang; Chian-Ren Jeng; Fan Lee; Yu-Wen Huang; Yeou-Liang Lin; Shih-Hsuan Hsiao; Shiow-Suey Lai (Folia Microbiologica, 2011)

Antimicrobial peptides derived from different animals: comparative studies of antimicrobial properties, cytotoxicity and mechanism of action - Fei-Fei Han; Yi-Fan Liu; Yong-Gang Xie; Yan-Hua Gao; Chao Luan; Yi-Zhen Wang (World Journal of Microbiology and Biotechnology, 2011)

Pathogen-induced MdWRKY1 in ‘Qinguan’ Apple Enhances Disease Resistance - Hongke Fan; Fei Wang; Hua Gao; Leicun Wang; Jihua Xu; Zhengyang Zhao (Journal of Plant Biology, 2011)

Interdecadal and decadal variation of temperature over North Pole area and the relation with solar activity - Weizheng Qu; Jinping Zhao; Ling Du; Fei Huang; Tingting Fan (Acta Oceanologica Sinica, 2011)

Metabolomics study on the synergistic interaction between Salvia miltiorrhiza and Lignum dalbergiae odoriferae used as ‘Jun-Shi’ herbs in a S. miltiorrhiza recipe - Shi-Xiang Wang; Kai Luo; Jing Liang; Fei Fan; Hua Li; Jian-Bin Zheng; Xiao-Hui Zheng (Medicinal Chemistry Research, 2011)

Erratum to: Exploitation of patchy soil water resources by the clonal vine Ficus tikoua in karst habitats of southwestern China - Chang-Cheng Liu; Yu-Guo Liu; Ke Guo; Da-Yong Fan; Li-Fei Yu; Rui Yang (Acta Physiologiae Plantarum, 2011)

Exploitation of patchy soil water resources by the clonal vine Ficus tikoua in karst habitats of southwestern China - Chang-Cheng Liu; Yu-Guo Liu; Ke Guo; Da-Yong Fan; Li-Fei Yu; Rui Yang (Acta Physiologiae Plantarum, 2011)

Reproductive failure in wild boars associated to porcine parvovirus infection and in vivo and in vitro characterization of the causal isolate - Chao-fan Zhang; Cui-Ping Song; Chang-mu Chen; Shang-jin Cui; Lan-fei Miao (Tropical Animal Health and Production, 2010)

Hydrolysis of DNA by a Dipeptides Containing Histidine - Xiao-fei Zhu; Min Fan; Xu-bin Wang; Bao-bao Guo; Cun-jiang Liu; Yong Ye; Yu-fen Zhao (International Journal of Peptide Research and Therapeutics, 2010)

An Ac transposon system based on maize chromosome 4S for isolating long-distance-transposed Ac tags in the maize genome - Fei Wang; Zhaoying Li; Jun Fan; Pengfei Li; Wei Hu; Gang Wang; Zhengkai Xu; Rentao Song (Genetica, 2010)

Expression pattern and core region analysis of AtMPK3 promoter in response to environmental stresses - Fei Gao; Qi Su; YunLiu Fan; Lei Wang (Science China Life Sciences, 2010)

Inhibition of acid-sensing ion channels in articular chondrocytes by amiloride attenuates articular cartilage destruction in rats with adjuvant arthritis - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Jian-ping Li; Cheng-Wan Li; Rui-Sheng Xu; Fan-Rong Wu; Wei Hu; Teng-Yue Zhang (Inflammation Research, 2010)

β-catenin signaling involves HGF-enhanced HepG2 scattering through activating MMP-7 transcription - Fei-Yan Pan; Sheng-Zhou Zhang; Na Xu; Fan-Li Meng; Hong-Xia Zhang; Bin Xue; Xiao Han; Chao-Jun Li (Histochemistry and Cell Biology, 2010)

Effect of glycyrrhizin on the activity of CYP3A enzyme in humans - Jiang-Hua Tu; Yi-Jing He; Yao Chen; Lan Fan; Wei Zhang; Zhi-Rong Tan; Yuan-Fei Huang; Dong Guo; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2010)

Acid-sensing ion channel 1a mediates acid-induced increases in intracellular calcium in rat articular chondrocytes - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Fan-Rong Wu; Jian-Ping Li; Cheng-Wan Li; Yu Wang; Teng-Yue Zhang; Wei Hu (Molecular and Cellular Biochemistry, 2010)

Notch signaling maintains proliferation and survival of the HL60 human promyelocytic leukemia cell line and promotes the phosphorylation of the Rb protein - Guo-Hui Li; Yu-Zhen Fan; Xiao-Wei Liu; Bing-Fang Zhang; Dan-Dan Yin; Fei He; Si-Yong Huang; Zhi-Jie Kang; Heng Xu; Qiang Liu; Yan-Lan Wu; Xiao-Li Niu; et al. (Molecular and Cellular Biochemistry, 2010)

Effect of volcanic activities and CO2 concentration on summer temperature in middle stratosphere, North Hemisphere - Weizheng Qu; Shenggui Deng; Fei Huang; Yingchen Liu; Ting Fan; Yan Bai (Journal of Earth Science, 2010)

Identification of QTLs for yield and yield components of barley under different growth conditions - Da-wei Xue; Mei-xue Zhou; Xiao-qin Zhang; Song Chen; Kang Wei; Fan-rong Zeng; Ying Mao; Fei-bo Wu; Guo-ping Zhang (Journal of Zhejiang University-SCIENCE B, 2010)

Maintenance of Multifemale Social Organization in a Group of Nomascus concolor at Wuliang Mountain, Yunnan, China - Peng-Fei Fan; Xue-Long Jiang (International Journal of Primatology, 2010)

Sex ratio deviation of offspring in the area where exposure to the processing of electronic wastes - Qiang Liu; Ke Qiu Li; Jia Cao; Hui Zhao; Guang Li; Fei Yue Fan (Environmental Science and Pollution Research, 2010)

The application of geostatistics in grain size trend analysis: A case study of eastern Beibu Gulf - Fei Ma; Yaping Wang; Yan Li; Changjiang Ye; Zhiwei Xu; Fan Zhang (Journal of Geographical Sciences, 2010)

Type IV Pili of Acidithiobacillus ferrooxidans Are Necessary for Sliding, Twitching Motility, and Adherence - Yong-Quan Li; Dong-Shi Wan; Shuang-Sheng Huang; Fei-Fan Leng; Lei Yan; Yong-Qing Ni; Hong-Yu Li (Current Microbiology, 2010)

Anti-influenza-virus activity of total alkaloids from Commelina communis L. - Fei-Hong Bing; Jun Liu; Zhi Li; Guo-Bin Zhang; Yi-Fan Liao; Jing Li; Chang-Yuan Dong (Archives of Virology, 2009)

Proteomic analysis of cold stress-responsive proteins in Thellungiella rosette leaves - Fei Gao; Yijun Zhou; Weiping Zhu; Xiaofeng Li; Liumin Fan; Genfa Zhang (Planta, 2009)

Hydraulic pressure inducing renal tubular epithelial-myofibroblast transdifferentiation in vitro - Fei-yan Li; Xi-sheng Xie; Jun-ming Fan; Zi Li; Jiang Wu; Rong Zheng (Journal of Zhejiang University-SCIENCE B, 2009)

Properties Influencing the Relative Binding Affinity of Pteroate Derivatives and Drug Conjugates Thereof to the Folate Receptor - Christopher P. Leamon; Fei You; Hari Krishna Santhapuram; Mingjin Fan; Iontcho R. Vlahov (Pharmaceutical Research, 2009)

The global challenge of electronic waste management - Qiang Liu; Ke Qiu Li; Hui Zhao; Guang Li; Fei Yue Fan (Environmental Science and Pollution Research, 2009)

Chromosomal aberrations and DNA damage in human populations exposed to the processing of electronics waste - Qiang Liu; Jia Cao; Ke Qiu Li; Xu Hong Miao; Guang Li; Fei Yue Fan; Yong Cheng Zhao (Environmental Science and Pollution Research, 2009)

An unannotated α/β hydrolase superfamily member, ABHD6 differentially expressed among cancer cell lines - Fan Li; Xiangwei Fei; Jiaxi Xu; Chaoneng Ji (Molecular Biology Reports, 2009)

Genetic variation in the long terminal repeat associated with the transition of Chinese equine infectious anemia virus from virulence to avirulence - Lili Wei; Xiujuan Fan; Xiaoling Lu; Liping Zhao; Wenhua Xiang; Xiaoyan Zhang; Fei Xue; Yiming Shao; Rongxian Shen; Xiaojun Wang (Virus Genes, 2009)

The molecular characterization of the brain protein 44-like (Brp44l) gene of Gekko japonicus and its expression changes in spinal cord after tail amputation - Maorong Jiang; Xiaosong Gu; Xiao Feng; Zheng Fan; Fei Ding; Yan Liu (Molecular Biology Reports, 2009)

Short hairpin RNA targeting NP mRNA inhibiting Newcastle disease virus production and other viral structural mRNA transcription - Hua Yue; Shu Deng; Fa-long Yang; Ding-fei Li; An-jing Fu; Fan Yang; Cheng Tang (Virus Genes, 2009)

Predation on giant flying squirrels (Petaurista philippensis) by black crested gibbons (Nomascus concolor jingdongensis) at Mt. Wuliang, Yunnan, China - Peng-fei Fan; Xue-long Jiang (Primates, 2009)

Seasonal Variations in the Activity Budget of Nomascus concolor jingdongensis at Mt. Wuliang, Central Yunnan, China: Effects of Diet and Temperature - Peng-Fei Fan; Qing-Yong Ni; Guo-Zheng Sun; Bei Huang; Xue-Long Jiang (International Journal of Primatology, 2008)

Molecular cloning and tissue specific expression of an elongation factor 1A gene in sugarcane stalks - Ai-Qin Wang; Ying-Zhi Qin; Xing-Zhi Ye; Ye-Geng Fan; Long-Fei He; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2008)

Rapid clonal propagation of Dioscorea zingiberensis - Yongqin Chen; Jinyu Fan; Fei Yi; Zhongxun Luo; Yunsheng Fu (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)